Mechanical property of red mud-slag-fly ash based alkali-activated mortar with recycled waste glass aggregate - Ting-Ting Tang; Lan-Ping Qian; Hai-Tao Wang; Dong Guo; Kai-Di Peng; Jun-Qi Huang (European Journal of Environmental and Civil Engineering, 2026)

Promoting the terminal zero-pollution goal of hydrogen fuel cell vehicles: A stochastic evolutionary game analysis - Dan Zhao; Ya Zhang; Ye-kai Li; He-ping Wang; Jin-huan Tang; Jian Wang (Fuel, 2026)

Clear water but contaminated sediment: Heavy metal risks in suspended sediments of the Three Gorges Reservoir, China - Bingyan Li; Jie Wei; Xiubin He; Yuhai Bao; Qiang Tang; Ping Huang; Shengjun Wu; Jinlin Li (Ecohydrology & Hydrobiology, 2026)

UFMylation in lipid metabolism disorders-associated diseases - Zi-Ping Ning; Ya-Ling Tang; Lin Cao; Hong-Feng Gu (Molecular Biology Reports, 2026)

MPP+ disorders Irg1-Itaconate axis to promote M1 polarization of microglia by activating succinate dehydrogenase - Lin-Yu Wang; Yi-Yun Tang; Wei Zou; Ping Zhang; Xiao-Qing Tang; Ping Zhang (Molecular Biology Reports, 2026)

A new KLF13 loss-of-function mutation responsible for sporadic dilated cardiomyopathy - Xiang Tang; Yin Wang; Chen-Xi Yang; Zun-Ping Ke; Fang Yuan; Yi-Qing Yang; Ying-Jie Xu (Molecular Biology Reports, 2026)

Overexpression, clinical significance and potential mechanisms of protein kinase D1 in hepatocellular carcinoma: multi-omic analyses and pharmacological insights - Zhen-dong Chen; Hui-ping Lu; Yan-ting Zhan; Fei-yan He; Liang-qin Zhu; Yu-long Deng; Xi-ni Wei; Min-ying Yang; Kai Qin; Yu-xing Tang; Ke-jun Wu; Zhi-guang Huang; et al. (Functional & Integrative Genomics, 2026)

A pH-responsive, kojic acid-based amphiphilic polymer as a nanocarrier for targeted herbicide delivery - Yuying Xie; Yangchun Ge; Zhuochao Shen; Yupeng Qiu; Haohua Zhang; Changmeng Sun; Jiangkuan Tang; Bingke Li; Junran Xu; Ping Liang; Yubang Tao; Shengtian Wang; et al. (Crop Protection, 2026)

Beyond gastroenteritis: first evidence of systemic biochemical disturbances, predominantly coagulation dysfunction, in Neoboletus poisoning - Jia Li; Yuan-Tian Lu; Xiu-Juan Li; Ming Li; Ping Wei; Tai-Jie Yu; Yu-Xian Gao; Ting Li; Yuan-Yuan Xiong; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Acute liver injury and facial edema following ingestion of mushroom Descolea quercina - Ting Li; Xiu-Juan Li; Tai-Jie Yu; Wen-Hao Zhang; Yuan-Tian Lu; Yu-Xian Gao; Yuan-Yuan Xiong; Jun Gao; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Qianlong Shutong Formula alleviates benign prostatic hyperplasia associated with the regulation of inflammation, fibrosis and the Hippo-YAP/TAZ pathway - Ze-chao Zhang; Xue-jin Ye; Chang-jie Shang; Zhi-feng Wei; Yu Chen; Shu-ping Huang; Min Zhu; Bo-tao Tang; Tai-sheng Liang (Tissue and Cell, 2026)

The Holocene transgression in the Bohai Sea: insights from multi-proxy sedimentary records - Lichao Tang; Ya Ping Wang; Yuanfu Yue; Wei Feng; Fu Wang; Cong-Qiang Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Rapid denudation of a Paleo-Tethyan arc revealed by decoupled O isotopes and elemental compositions in Late Permian Hainan granitic rocks - Xiao-Yan Chen; Xiao-Ping Xia; Touping Peng; Yu Zhu; M.P. Manu Prasanth; Yufan Yue; Feng Guo; Yanjie Tang (Lithos, 2026)

lnc5714 participates in silkworm resistance to Nosema bombycis infection by regulating MRPL4-related host energy metabolism - Li Sui; Qiong Yu; Wangbin Qin; Yujia Fang; Pingyang Wang; Jie Cheng; Xudong Tang; Ping Qian (Journal of Invertebrate Pathology, 2026)

A comparative study on radio frequency inactivation kinetics of Bacillus cereus vegetative cells and A. flavus spores in sunflower seeds: nonlinear modeling and its impact on storage stability - Xuan Ou; Sen Zeng; Jiamin Song; Songlei Wang; Yunyang Wang; Baozhong Cui; Guangxian Wang; Ping Zhang; Qiuyu Deng; Yinghua Tang; Yanan Sun (Food Research International, 2026)

Integrated electronic nose, GC–MS, and metagenomic analyses reveal volatile flavor and microbial community differences in heap-fermented grains of Jiangxiangxing Baijiu across different fermentation degrees - Guiyin Li; Lixia Shen; Lei Nie; Ping Tang; Qimuge Shan; Liqin Qin; Shuangxi Fan; Xuewu Guo (Food Research International, 2026)

Riverine transport dynamics and historical trends of emerging and legacy flame retardants in an urbanized coastal zone: Pollutant management effectiveness in China - Jun-Rong Liang; Hui-Ping Wen; Ting Pan; Rui Tang; Lei Mai; Chen-Chou Wu; Ze-Hua Liu; Eddy Y. Zeng (Environmental Pollution, 2026)

Progressive collapse behaviour of multi-storey reinforced concrete sub-frames with slab strips: Experimental tests and numerical modelling - Hui-Qiang Yan; Yan-Ren Wang; Shao-Bo Kang; Yi Chen; Xing-Ju Yang; Chun-Ping Tang (Engineering Structures, 2026)

Constructing structure-charge dual-regulated nanofiltration membranes via swelling embedding strategy for efficient separation - Ping Li; Yuan Zhou; Chunxi Hai; Wenjie Liu; Ying Cheng; Yu Tang; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu (Desalination, 2026)

Biomass-derived Fe3C@CNT catalyst for catalytic ozonation through confinement-enhanced electron transfer and ozone activation - Tian He; Shaosong Huang; Ping Chen; Guangzheng Zhuang; Bing Tang; Ping Li; Liying Bin; Yunqiang Yi; Weirui Chen; Laisheng Li (Chemical Engineering Journal, 2026)

Highly selective CO2/H2 separation by isomeric CALF-20-based porous slurry - Han Tang; Jin Cai; Zi-Ying Zhao; Long-Long Xie; Ping-Xiang Wang; Yang Meng; Hai-Hang Qin; Peng Xiao; Bei Liu; Yun-Lei Peng; Chang-Yu Sun; Zhi Li; et al. (Chemical Engineering Journal, 2026)

Construction of a rigid–flexible OVS/PHFA interphase on Al–Li alloy fuels for coupled stabilization and efficient energy release - Changsheng Tang; Shixiong Song; Luyang Wang; Pengxiang Li; Yanqiu Jiang; Yulin Yang; Debin Xia; Jian Zhang; Ping Wang; Kaifeng Lin (Chemical Engineering Journal, 2026)

Reducing carbon mineralization and enhancing carbon storage in coastal earth aquaculture pond sediment using Spartina alterniflora-derived biochar - Ping Yang; Junwei Wang; Yongxin Lin; Hong Yang; Wenjing Liu; Qian Zhu; Chuan Tong; Dongyao Sun; Linhai Zhang; Kam W. Tang (Agriculture, Ecosystems & Environment, 2026)

Disruption of progesterone synthesis by PBDEs: Potent inhibition of human and rat placental 3β-hydroxysteroid dehydrogenase by the metabolite 4-Bromodiphenyl ether - Lubin Xie; Qianjin Fei; Ming Su; Yunbing Tang; Yang Zhu; Ren-shan Ge; Ping Duan; Chengshuang Pan (Toxicology and Applied Pharmacology, 2026)

2(3→20)-abeo-taxoids with adipogenesis inhibitory activity from the leaves and twigs of Taxus chinensis var. mairei - Li-Ping Long; Xin-Yu Fan; Yuan-Hui Yu; Yuan-Liang Xu; Lin-Xi Mao; Xue Tang; Kai Guo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Multistage metamorphism recorded by garnet amphibolites from the Xiarihamu area, NW China: Implications for Early Paleozoic tectonic evolution of the East Kunlun Orogenic Belt - Huan Tang; An-Ping Chen; Haibo Zou; Ming-Jie Zhang; Juan Zhang; Hong-Fu Zhang (Lithos, 2026)

Piezoelectric driven ultralow peroxymonosulfate activation over Co3O4/Bi4O7/BiO2-x for rapid degradation of levofloxacin - Chaoqin Zhao; Yigui Tang; Die Yuan; Ping Ning; Shuangyou Bao; Kai Li (Journal of Environmental Chemical Engineering, 2026)

Erosion rates in the northern coast of Southern China Sea: Insights from granitic cosmogenic nuclide depth profiles - Hao Liang; Ying Xu; Ziye Zhou; Zhen Chen; Yongjie Tang; Cong Chen; Ke Zhang; Ping Huang; Zhigang Li; Gege Hui; Yipeng Zhang; Qingying Tian; et al. (Geomorphology, 2026)

Selective enrichment and metabolic characterization of caproate-producing microbes from Baijiu Huangshui - Guida Zhu; Zhangyi Wei; Zhiye Li; Jing Yu; Qiuxiang Tang; Ping Song (Food Bioscience, 2026)

Regulatory mechanisms of N2O emissions from latosolic red soil by different ecotypes of earthworms: Insights from microbial diversity and metagenomic analysis - Chang Wei; Chang-Wen Yun; Xiao-Qing Li; Lang-Hao Lai; Jian-Peng Gao; Meng-Ping Tang; Chun-Na Zhou; Yu-Long Zhang; Hui-Juan Xu (Environmental Pollution, 2026)

Hierarchical core–shell nanoplatforms based on sacrificial template-directed ZnO2@ZIF-8 for spatiotemporally controlled and self-augmented chemodynamic–photothermal antibacterial therapy - Yi-Fei Hui; Duan-Ping Hu; Yi Zhao; Shulin Li; Zhi-Feng Cai; Lin-Yi Li; Yuming Xie; Yong-Nian Zeng; Zu-Jin Lin; Fa-Qiang Tang (Chemical Engineering Journal, 2026)

On-demand localized photodynamic therapy: An aggregation-induced emission photosensitizer-functionalized superhydrophobic patch for oral infectious disease treatment - Weinan Zhao; Xiao Yang; Feng Lou; Shiquan Deng; Ping Shangguan; Meng Suo; Yuchen Jiao; Xinyan Zhu; Junchen Liao; Wang Guo; Zhenlin Chen; Zuankai Wang; et al. (Chemical Engineering Journal, 2026)

A mechanism-guided, low-input Lactiplantibacillus plantarum strategy for attenuating antibiotic resistomes under oxygen re-entry during anaerobic fermentation - Chaosheng Liao; Mingjie Zhang; Wenlong Dai; Xiaolong Tang; Pan Wang; Ning Mao; Ping Li (Chemical Engineering Journal, 2026)

Shifts in organic carbon fractions, chemical functional groups, and mineralization enhance soil carbon storage after restoring earthen aquaculture ponds to wetlands - Ping Yang; Kaiyuan Liu; Junwei Wang; Hong Yang; Dengzhou Gao; Guanpeng Chen; Wenjing Liu; Chuan Tong; Dongyao Sun; Yanxun Xu; Kam W. Tang (CATENA, 2026)

Contributions and mechanisms of bioclogging-induced oxygen-limited microsites to nitrogen removal in porous media - Ping Tang; Hui Shuai; Zuan Yang; Qihang Cen; Yanbin Mao; Junjie Wang; Yongchao Zhou (Bioresource Technology, 2026)

Interannual variability of secondary organic carbon driven by seasonal shifts in formation regimes in southern Taiwan - Jun-Fa Ye; Chih-Yu Chan; Jian-Xian Wu; Shi-Ya Tang; Tse-Lun Chen; Li-Hao Young; Yu-Chieh Ting; Yen-Ping Peng; Wei-Hsiang Chen; Ming-Yeng Lin; Si-Chee Tsay; Neng-Huei Lin; et al. (Atmospheric Environment, 2026)

Assessment of a farmland-constrained deep learning framework for fine-scale extraction of farmland shelterbelts from Sentinel-2 - Yingqi Xu; Ping Lv; Zhuo Zhang; Lanjie Li; Zheng Chai; Cheng Tang; Yuanyuan Li (Agroforestry Systems, 2026)

RBM10 suppresses porcine epidemic diarrhea virus replication by degrading nonstructural protein 3 through selective autophagy - Mingyu Liu; Zhenpeng Tang; Huixin Zhu; Jinxiu Lou; Yangyang Zhang; Mingjun Ye; Yufan Xu; Juan Bai; Ping Jiang; Zhen Yang; Gongguan Liu; Xianwei Wang (Veterinary Microbiology, 2026)

Silica nanoparticles disrupt blood–testis barrier integrity in Sertoli cells by inducing inflammation-mediated p38 MAPK pathway - Ying Wang; Wenpeng Liu; Yichen Wang; Dan Chen; Shoufang Jiang; Jinlong Li; Wenxuan Tang; Ping Lu; Xuan Shang (Reproductive Toxicology, 2026)

Critical review on strategies for the removal of antibiotics from water and wastewater: Present situation, challenges, and perspective - Ruiwu Zhou; Wei Pan; Weichao Huang; Ping Yu; Binrui Chen; Ruizhe Zhao; Lirong Chen; Rui Tang (Process Safety and Environmental Protection, 2026)

Pesticide exposure in Eriocheir sinensis: Oxidative stress, endocrine disruption, gut–hepatopancreas axis impairment, and systems toxicology - Shi-Rong Li; Dan-Dan Bian; Xiang Lu; Shuang-Gui Dai; Bo-Ping Tang; Qiu-Ning Liu (Pesticide Biochemistry and Physiology, 2026)

Screening potential antagonistic strains against tobacco bacterial wilt and evaluating the colonization ability of Bacillus velezensis TS08 - Fang Chen; Yinglong Liu; Pengfei He; Pengbo He; Yixin Wu; Ayesha Ahmed; Guowen Tang; Yining Di; Ping Tang; Yueqiu He; Shahzad Munir (Physiological and Molecular Plant Pathology, 2026)

A self-supervised deep learning method for retrieving historically similar extreme rainfall patterns - Tianyu Wan; Chao Gao; Xiongpeng Tang; Silong Zhang; Xin Yin; Jingjing Tang; Yue-Ping Xu (Environmental Modelling & Software, 2026)

Efficient antibiotic degradation by concentrated solar activation of trichloroisocyanuric acid: The role of triplet-state-mediated singlet oxygen generation - Yue Yang; Li Tang; Kun Chen; Ping Chen; Yixun Zheng; Bingbing Liu; Jin Wu; Shimin Zhou; Yongpeng Zhang; Yuxin Xian; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2026)

Enhanced power factor n-type carbon nanotube thermoelectric films enabled by liquid-crystal ordering for self-powered encrypted signal sensing - Qing-Yi Ma; Wen-Qian Leng; Zi-Yan Li; Fei-Peng Du; Ping Fu; Chak-Yin Tang; Chi-Pong Tsui; Wing-Cheung Law; Yun-Fei Zhang (Chemical Engineering Journal, 2026)

Revisiting the formation and differentiation of Neoproterozoic continental arc crust in the western Yangtze Block, South China - Yu Zhu; Xiao-ping Xia; Feng Guo; Yan-jie Tang; Xin Zhu; Chang-xin Yin; M.P. Manu Prasanth; Ren-zhi Zhu; Min Liu; Zhuang Guo; Jiang-feng Qin; Fang-yi Zhang; et al. (Chemical Geology, 2026)

Multipathway Pesticide Exposure and Cross‐Scale Risk Assessment in Integrated Rice–Crab Aquaculture - Dan‐Dan Bian; Shi‐Rong Li; Bo‐Ping Tang; Qiu‐Ning Liu (Reviews in Aquaculture, 2026)
Integrated rice–crab co‐culture represents a sustainable agroecosystem, yet a critical conflict arises: pesticide applications necessary for rice cultivation undermine the health of the co‐cultured Chinese mitten crab ( Eriocheir sinensis ) and jeopardize system sustainability. To address this challenge, a comprehensive analytical framework is developed, linking multipathway pesticide exposure, molecular toxicity mechanisms, cross‐scale risk assessment, and resilience‐oriented governance. This framework systematically reviews the environmental fate and exposure dynamics of pesticides in paddy fields, as well as their toxicokinetics and tissue‐specific bioaccumulation in E. sinensis . Moving beyond descriptive toxicology, the study integrates “effect hierarchy” and “mechanistic network” perspectives to unravel cascading toxicity pathways, spanning oxidative stress, neuroendocrine disruption, cellular pyroptosis, and immune suppression. The limitations of conventional risk assessment in such a complex system are critically examined, with emphasis on the dual risks to crab population resilience and human food safety. To mitigate these challenges, a novel, mechanism‐informed “Prevent–Intercept–Protect–Adapt (PIPA)” framework is proposed to bolster system resilience, combining green pest control, eco‐engineering, host health enhancement, and smart monitoring. This review enhances theoretical understanding of contaminant impacts in multitrophic systems and offers actionable management strategies to promote the sustainable development of integrated aquaculture.

Two Contributions to the Hypogeous Boletales of China: A Novel Rhizopogon Species and a New National Record of Turmalinea persicina - Jia Li; Chang Xu; Tai‐Jie Yu; Wen‐Hao Zhang; Xiu‐Juan Li; Yu‐Xian Gao; Yuan‐Tian Lu; Li‐Ping Tang (New Zealand Journal of Botany, 2026)
Hypogeous Boletales are ectomycorrhizal fungi with sequestered hymenophores; some species are ecologically valuable as edible mushrooms. Despite their ecological and economical importance, the diversity of this group in China remains poorly understood. In this study, we performed phylogenetic analyses based on four loci (ITS, LSU, TEF1‐α , and RPB2 ) and detailed morphological examinations of specimens belonging to Rhizopogon (Rhizopogonaceae) and Turmalinea (Boletaceae). We describe and illustrate R. sinoevadens , a new species from China, and report the first Chinese record of T. persicina , a species originally described from Japan. These discoveries underscore the previously underestimated diversity of hypogeous Boletales in China and provide a foundation for future taxonomic and ecological studies.

Quantitative evaluation method of dual laterolog for fracture parameters in carbonate reservoirs in the Sichuan Basin - Qiang Lai; Ben-Jian Zhang; Hang Zhang; Yu-Yu Wu; Wei Xu; Jun Tang; Li Shen; Ya-Ping Zheng (Applied Geophysics, 2026)

A study on the inhibitory effect of flaxseed oil emulsion coatings on Tyrophagus putrescentiae and quality of dry-cured ham - Hanlin Wu; Xingzhong Zhang; Xi Wang; Zhimin Cai; Ping Liu; Jie Tang; Tao Wu; M. Wes Schilling; Wenjie Shao (Meat Science, 2026)

Turning ecological nuisance to environmental resource: Use of Spartina alterniflora-derived biochar to decrease N2O production potential and emission in coastal aquaculture pond sediment - Wenjing Tan; Kaiyuan Liu; Ping Yang; Kam W. Tang; Hong Yang; Chuan Tong; Wenjing Liu; Dongyao Sun; Junwei Wang; Yongxin Lin; Yifei Zhang (Journal of Environmental Chemical Engineering, 2026)

Waterfowl's presence enhanced N2O emissions from restored coastal wetlands: Trade-offs between biodiversity and climate - Ping Yang; Wenting Liu; Yifei Zhang; Hong Yang; Siying Li; Wenjing Liu; Chuan Tong; Dongyao Sun; Yongxin Lin; Lihua Wang; Kam W. Tang (Journal of Environmental Management, 2026)

Synergistic H2S production and CO2 capture from copper smelting neutralized gypsum slag: Process optimization, reaction mechanism and CaCO3 crystal regulation - Yuwen Deng; Jiyao Shi; Sisi Chen; Huidong Tang; Xiaofeng Huang; Xin Sun; Kai Li; Lei Shi; Ping Ning (Journal of Environmental Management, 2026)

Long-range transported dust enhances ice nucleating particle abundance in the North China Plain - Yue Sun; Yujiao Zhu; Hengde Liu; Lanxiadi Chen; Hongyong Li; Yujian Bi; Di Wu; Xiangkun Yin; Can Cui; Ping Liu; Yu Yang; Jisheng Zhang; et al. (Journal of Environmental Sciences, 2026)

Trophic state regulates nitrous oxide (N2O) emissions and associated indirect emission factors in coastal creeks - Qian Zhu; Ziyuan Chen; Ping Yang; Hong Yang; Wenjing Liu; Junwei Wang; Chuan Tong; Jujuan Gao; Dongyao Sun; Yongxin Lin; Kam W. Tang (Global and Planetary Change, 2026)

Regulating interfacial electronic structure in Fe2O3/g-C3N4 heterogeneous fenton catalyst for efficient low-temperature flue gas denitrification - Huidong Tang; Chen Liu; Donggou Sun; Wenbo Zhang; Xiaohua Zhu; Yixing Ma; Jiacheng Bao; Kai Li; Xin Sun; Ping Ning (Chemical Engineering Journal, 2026)

A sequential cascaded cGAS–STING amplifier based on hybrid multienzymes for efficient catalytic immunotherapy of hepatocellular carcinoma - Wanying Sun; Yuchen Wang; Juan Song; Xiaolu Guo; Shunxin Tang; Bang-Ping Jiang; Xing-Can Shen (Chemical Engineering Journal, 2026)

An improved method for Gill’s hematoxylin and eosin staining based on the optimal acetic acid ratio - Zhijie Ma; Caixia Sheng; Danju Wu; Huimin An; Wen Tang; Ping Zhao; Guoxiang Fu (Histochemistry and Cell Biology, 2026)

The Contributions of Deep and Shallow Convection to Tropical Precipitation Interannual Variability and Its Changes under Global Warming - Jingling Tang; Ping Huang; Shijie Zhou (Advances in Atmospheric Sciences, 2026)

Chemical speciation, source apportionment, and pollution assessment of phosphorus in sediments from typical urban lakes in Southern China - Tianning Li; Linsen Tang; Huiyang Qiu; Fangwen Zheng; Ping Liu; Jinfu Liu (Environmental Monitoring and Assessment, 2026)

Phytochemicals from the leaves of Staphylea arguta (Turpiniae Folium) and their anti-inflammatory activity - Shumin Wu; Feifei Tang; Xiyu Xu; Xiaoxiang Fan; Danting Luo; Yunqing He; Ping Hai; Shengxiang Yang; Yuan Gao; Jian Yang (Natural Product Research, 2026)

Green and sustainable dual-pathway strategies for high-efficiency photoconversion of ergosterol to vitamin D₂ from agaricus bisporus - Jiahao Yu; Yan Tang; Yang Lin; Simin Feng; Mofei Shen; Ping Shao (Food Chemistry, 2026)

Temperature-dependent regulation of benzeneacetaldehyde formation during black tea drying: Evidence from non-targeted metabolomics and an EGCG-modulated Maillard reaction model - Zisheng Han; Shengxiao Su; Wen Li; Tong Jia; Piaopiao Long; Jia-Ping Ke; Chi-Tang Ho; Liang Zhang (Food Chemistry, 2026)

Structural and rheological modulation of low-oil emulsions by deamidated pea protein–gum arabic coacervates for reduced-fat applications - Lijuan Luo; Ping Li; Yuanyuan Deng; Guang Liu; Yan Zhang; Xiaojun Tang; Pengfei Zhou; Zhihao Zhao; Jiarui Zeng; Mingwei Zhang (Food Chemistry, 2026)

NFIL3-dependent regulation of NF-κB pathway mediates alginic oligosaccharide alleviation of nitrite immunotoxicity in Procambarus clarkii - Xue Zhang; Shuang-Gui Dai; Xiang Lu; Bo-Ping Tang; Dan-Dan Bian; Qiu-Ning Liu (Fish & Shellfish Immunology, 2026)

Direct visual evidence of S-scheme charge transfer: CeO2 quantum dots anchored on CdS nanosheets for synergistically enhanced photocatalysis - Yaodi Fu; Ke Wen; Shimei Liu; Ping Li; Banpeng Cao; Lihong Cheng; Jingjing Liu; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Lingfang Qiu; Shuwang Duo (Environmental Research, 2026)

Nitrogen-vacancy-regulated plasmonic Schottky interfaces on Ag/C3N5 for ultrafast oxygen activation and solar-driven antibiotic degradation - Kaizhou Huang; Wei Qu; Tenghui Jin; Yutong Xie; Zhuoyun Tang; Ming Su; Ping Zhang; J. Paul Chen (Chemical Engineering Journal, 2026)

Multi-dimensional analysis revealing the mechanism of T-2 toxin driving liver fibrosis: integration of network toxicology, machine learning, experimental verification, and molecular docking - Lichun Qiao; Shaoteng Shi; Liangjia Wang; Muhammad Aftab Shafiq; Jing Tang; Miaoqian Li; Ping Wan; Jingxuan Zhou; Xulei Dai; Jing Han; Yijie Guo (Chemico-Biological Interactions, 2026)

LIDAR-based visibility map for plan position indicator (PPI) scans and range height indicator (RHI) scans – methodology and observations in two uncommon haze cases in Hong Kong - Man Lok Chong; Ping Cheung; Wai Ho Tang; Chun Kit Ho; Pak Wai Chan (Atmospheric Environment, 2026)

Investigation of the Regulatory Mechanisms of Gut Microbiota and Metabolites in Colorectal Cancer Development and Progression - Zhonghua Qi; Peng Qi; Huan Tang; Ping Qi (Phenomics, 2026)

Anemoside B4 inhibits mitochondrial dysfunction-related mitophagy in asthma by regulating KAT2B/IRF3 axis - Hao Tang; Ping Li; Mingxia Shang; Zhiping Zhou; Xing Yang; Bin Liu (Molecular and Cellular Biochemistry, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

MiR-29a/DNMT3A axis participates in Dihydroartemisinin's suppression on lung adenocarcinoma: Implications for overcoming acquired resistance to EGFR-TKIs - Yayu Zhu; Ping Qiu; Jing Tang; Renjie Chen; Yaqing Liu; Huijuan Ling; Yu Liu; Liwen Chen (Toxicology and Applied Pharmacology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Pesticide toxicity in Procambarus clarkii: Integrating oxidative stress, immune dysfunction, and gut microbiota disruption - Dan-Dan Bian; Zi-Yi Xing; Xiang Lu; Shuang-Gui Dai; Qiu-Ning Liu; Bo-Ping Tang; Zhi-Gang Wang (Pesticide Biochemistry and Physiology, 2026)

Splicing factor SC35 inhibits Nosema bombycis proliferation by regulating the alternative splicing of Bmupp1 - Qiong Yu; Qingsheng Qu; Shiyi Lu; Pingyang Wang; Li Sui; Jie Cheng; Xudong Tang; Ping Qian (Journal of Invertebrate Pathology, 2026)

Metabolic reconstruction and microbial network assembly immobilised heavy metals during soil function recovery in coal gangue - Pan Wang; Cheng Chen; Yubo Zhang; Chaosheng Liao; Lin Li; Xiaolong Tang; Mingjie Zhang; Guangrou Lu; Xiaokang Huang; Ping Li; Chao Chen (Journal of Hazardous Materials, 2026)

Investigating the influence of BaTiO3 morphology on piezo-photocatalytic antibacterial synergy - Yan Wang; Ping Wang; Yijia Fang; Yuanxiao Wang; Huaying Liu; Huan Li; Xiaoning Tang (Journal of Environmental Chemical Engineering, 2026)

Swelling-thermal crosslinking engineered polyamide nanofiltration membranes for high-performance Mg2+/Li+ separation - Yu Tang; Shengde Dong; Ping Li; Ying Cheng; Wenjie Liu; Chuanjiang Cheng; Yanxia Sun; Qi Xu; Chunxi Hai; Yuan Zhou (Journal of Environmental Chemical Engineering, 2026)

Deep carbon recycling via the Tianshan basalt province and its contribution to Cenozoic elevated atmospheric CO2 concentration - Xiangsong Wang; Jinlong Yao; Guochun Zhao; Peter A. Cawood; Min Sun; Keda Cai; Xiao-Ping Xia; Pengfei Li; Xijun Liu; Ming Li; Yunying Zhang; Kai Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Integrated machine learning assisted multi-objective optimization of spray drying conditions for plant-based probiotic powder: Comparative modelling with GC-MS and FTIR validation - Ping Tang; Siew Young Quek; Aliah Zannierah Mohsin; Nurul Hanisah Juhari; ShuangQuan Huang; Anis Shobirin Meor Hussin (Food Bioscience, 2026)

LSTM-NSGA-II framework for predicting and enhancing the quality of fermented kidney bean milk - Ping Tang; Aliah Zannierah Mohsin; Nurul Hanisah Juhari; Anis Shobirin Meor Hussin (Food Bioscience, 2026)

Operation-resolved VOC emissions from electronics manufacturing: Implications for ozone formation, toxicity, and risk-oriented management - Jun Tao; Rui Xu; Zhisheng Zhang; Zijun Tang; Ping Fang; Leilei Fei; Zhihui Li; Zhihang Chen (Environmental Research, 2026)

Day-night cloud aqueous chemistry diverges organic molecules pathways and health implications - Baichuan Gou; Shuyi Peng; Yaohao Hu; Xiaocong Peng; Wei Sun; Guohua Zhang; Wei Song; Mingjin Tang; Xiaole Pan; Yele Sun; Zifa Wang; Xinming Wang; et al. (Environmental Pollution, 2026)

Geomorphological controls on elevational differentiation of sediment 210Pbₑₓ and 137Cs activities in a water-level fluctuation zone - Jinlin Li; Xiubin He; Jie Wei; Qiang Tang; Yuhai Bao; Ping Huang; Shengjun Wu; Xin Gao; Ziqiang Mao (CATENA, 2026)

Hematopoiesis could be improved by correcting aberrant bone marrow macrophages polarization in aplastic anemia patients - Chen-Yuan Li; Dan-Dan Chen; Xin-Yan Zhang; Shu-Qian Tang; Meng-Zhu Shen; Ya-Ting Yu; Zhi-Wei Zhang; Zheng-Li Xu; Yuan-Yuan Zhang; Jin-Song Jia; Lan-Ping Xu; Yu Wang; et al. (Science China Life Sciences, 2026)

Wear Analysis and Evaluation of Inserted-Tooth Disc Cutters During Shield TBM Tunneling in Soil-Rock Mixed Ground - Hao-Jie Wang; Xiao-Ping Zhang; Quan-Sheng Liu; Shao-Hui Tang (Rock Mechanics and Rock Engineering, 2026)

Root morphological strategies enhance growth of Cunninghamia lanceolata and Schima superba under nitrogen stress in intercropping systems - Xiao-Li Yan; Cong Cheng; Yunhao Xu; Jiaxiang Yu; Zhaozhao Wang; Yanru Wang; Xinghao Tang; Pengfei Wu; Xiangqing Ma; Lu-Ping Qu (Plant and Soil, 2026)

Syn-tectonic emplacement of Li-bearing pegmatites related to detachment faulting in the Dahongliutan pegmatite belt, Western Kunlun, NW China - Tao Hong; Matthieu Harlaux; Ming-Guo Zhai; Yue-Jun Wang; Xing-Wang Xu; Xiao-Ping Xia; Jun Gao; Jun-Lin Tang; Ming-Xi Hu; Huan-Xiang Gao (Mineralium Deposita, 2026)

Identification of Cenozoic Ostracods in the Qaidam Basin Using Convolutional and Transformer-Based Neural Networks - Wenqiang Tang; Hanting Zhong; Zhisong Cao; Kunyu Wu; Dangpeng Xi; Xingxing Zhang; Ping Yang; Yuxuan Zhou; Chao Ma (Journal of Earth Science, 2026)

Osteopontin-driven TGF-β1 signaling via integrin αvβ3-NF-κB axis impairs NK cell function in head and neck squamous cell carcinoma - Zhe Shen; Xin Li; Shi Luo; Yuzhang Gao; Imadoudini Hassimi Safia; Jie Jiang; Xin Qi; Wei Huang; Yalan Liu; Xing Fang; Yaoyun Tang; Ping Wu (Apoptosis, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Overcoming gastrointestinal mucosal barriers: Mechanistic innovations and technical advances in mucosal targeting strategies for animal oral vaccines - Meijun Yu; Yue Li; Zhaojun Wang; Ping Han; Yanping Jiang; Wen Cui; Yijing Li; Lijie Tang; Shuo Jia; Hongzhe Zhao; Yingying Ma; Jiaxuan Li; et al. (Veterinary Microbiology, 2026)

New cutting tool wear testing method for evaluating the influence of foam additive on plowing effect during shield TBM tunnelling in dense sandy gravel ground - Shao-Hui Tang; Xiao-Ping Zhang; Quan-Sheng Liu; Yu-Cong Pan; Wei-Qiang Xie; Xin-Fang Li; Hao-Jie Wang (Tunnelling and Underground Space Technology, 2026)

Triphasic volatile emission dynamics and gene expression in postharvest PGF-lost non-melting peach (Prunus persica) var. RedY - Ping Zhou; Xiaodan Zhang; Xin Feng; Rui Guo; Shaobin Yan; Xiuqing Wei; Liang Li; Yajun Tang; Zhizheng Fang; Yan Lei (Postharvest Biology and Technology, 2026)

Sustainable titanium-tannic acid metal-phenolic network for aqueous Vanadium(V) removal: performance, mechanism, and practical potential - Yang Hu; Qian-xin Zhang; Jin-ping Tang; Peng Liu; Yao-ning Guo (Journal of Cleaner Production, 2026)

An ROS-scavenging dual-network hydrogel for diabetic bone regeneration - Zhengyu Cai; Weizhe Xu; Qingxiang Zhang; Xingwu Zhou; Jiang Zeng; Zhiyong Wang; Peng Deng; Ping Sun; Fan Tang; Xing Jiang; Moyuan Qu; Qianming Chen (Chemical Engineering Journal, 2026)

A glucose-triggered self-reinforcing hydrogel based on carboxymethyl chitosan/oxidized hyaluronic acid/borax for delivering nano-selenium and dynamic diabetic wound management - Wei-Xiong Li; Shanshan Li; Hao Cheng; Yu Chen; Han-Jian Hu; Shipeng Tang; Jian Sun; Xiao-Ping Liao; Gang-Biao Jiang; Hongyan Zhang (Carbohydrate Polymers, 2026)

Activity-tunable bimetallic iron-cobalt nanoflowers integrated with smartphones for rapid detection of human uric acid - Rou Cheng; Ziyi Guo; Zhengyue Xiao; Bowen Yu; Xiaomin Tang; Peng Xu; Ping Qiu (Analytica Chimica Acta, 2026)

Impact of human activities on groundwater biogeochemical cycles and microbial communities: Insights from metagenomic analysis - Zhengxing Chen; Xiufeng Tang; Yirui Su; Tao Liu; Uli Klümper; Feng Ju; Min Liu; Ping Han (Water Research, 2026)

Microplastics promote N2O emissions by enhancing nitrification via ammonia-oxidizing bacteria in estuarine and coastal sediments - Xiufeng Tang; Yingyu Bao; Jun Li; Bolin Liu; Yixuan Huang; Lijun Hou; Patrick K.H. Lee; Ping Han (Water Research, 2026)

Insight into the thermodynamic response characteristics in a liquid helium-4 tank using a modified Lee model: A numerical study - Caigong Zhang; Shaomu Wen; Zhixiang Dai; Changjun Li; Ping Tang; Wenyan Zhang; Xue Zhong; Yang Peng (Process Safety and Environmental Protection, 2026)

Distribution pattern and development of typical antibiotic resistance genes in the continuous-flow aerobic granular sludge-membrane bioreactor system - Yongsheng Jiang; Yu Zeng; Lei Shang; Dehong Bai; Liying Bin; Weirui Chen; Xinyi Chen; Shanglong Wen; Shaosong Huang; Ping Li; Bing Tang (Journal of Environmental Chemical Engineering, 2026)

Persistent site-scale warming associated with solar photovoltaic installations - Chao Zhang; Wanjiao Li; Junjie Tang; Zhe Shi; Fanyu Suo; Shujie Zhang; Yulu Ke; Hongxing Hu; Ning Ai; Yong Gao; Ping Gong; Guo Yu Qiu (Journal of Environmental Management, 2026)

Fe-CN activated peracetic acid system achieving hydroxyl radical-dominated degradation of organic pollutants - Wei Ren; Xiao-Wen Huang; Dongmei Hou; Zhuoyuan Li; Jingenqi Li; Denglong Chen; Yuehong Ma; Chongli Wu; Qian-Qian Tang; Yi Hu; Long-Shuai Zhang; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Efficient depolymerization of polystyrene waste into styrene monomers over the microwave-assisted Zn/b-ZnO catalyst system - Zijian Zhang; Bonan Liu; Li Yang; Jingwen Wang; Yuqing Dong; Chao Tang; Ping Wang; Haijiao Xie; Lei Zhang; Lu Zhang; Jun Zhao; Yu Fan; et al. (Journal of Environmental Chemical Engineering, 2026)

Designing interfacial-engineered S-scheme heterostructures with dual-metal sulfides for efficient solar-to-hydrogen conversion - Xiaofeng Liu; Sihai Cai; Tongyan Ren; Chunrong Li; Geng Tang; Ping He (Fuel, 2026)

Construction of a controllable alkylpyrazines generation system and its role in flavor reconstruction of vinegar - Zhizhi Yang; Qunna Yang; Yingtong Tang; Hongjing Zhang; Hui Xu; Jianyu Huang; Hsiang ping kuo; Jicheng Chen (Food Bioscience, 2026)

Multifunctional nanoemulsion co-delivering Lactobacillus plantarum supernatant and Litsea cubeba essential oil: Construction and application in fiddlehead fern preservation - Jiayue Song; Dengyi Ye; Wenjia Li; Qiao Guo; Yanan Zhang; Xiyu Wang; Ping Tang; Ping Chen; Linlin Xu (Food Bioscience, 2026)

Thin film nanocomposite membrane incorporated with sulfonic acid-based HOFs for efficient reverse osmosis desalination - Yu-ting Liu; Zi-yue Tang; Zi-ao Zong; Wan-zhen Wang; Xiao-yin Zhang; Xin-ping Song; Xiang-min Meng; Rijia Lin; Jingwei Hou (Desalination, 2026)

Glycine betaine-mediated novel Pickering nanoparticles and emulsions: Interfacial engineering, characterization and anti-browning preservation of leafy vegetables - Dengyi Ye; Hao Shen; Jiayue Song; Xiyu Wang; Ping Tang; Wenjia Li; Qi'’ao Guo; Yanan Zhang; Biying Zhang; Ping Chen (Chemical Engineering Journal, 2026)

Flash-spun composite fiber membranes for broadband electromagnetic absorption and multifunctionality - Daixuan Gong; Xincheng Wang; Meijie Qu; Shuhui Li; Ping Tang; Yuezhen Bin (Chemical Engineering Journal, 2026)

USP7 protects histone H1.2 from proteasome-mediated degradation to facilitate DNA repair and pancreatic neuroendocrine neoplasms progression - Mujie Ye; Lin Xu; Ping Yu; Jialing Pan; Xiaoting Shi; Bingyan Xue; Na He; Ping Hu; Min Liu; Xintong Lu; Yuemei Xu; Yanling Xu; et al. (Science China Life Sciences, 2026)

Restoring aquaculture ponds to coastal wetlands using native vegetation reduces methane (CH4) production and emissions - Wenjing Liu; Hong Yang; Ping Yang; Qitao Xiao; Jujuan Gao; Lihua Wang; Chuan Tong; Yingzi Wang; Pingping Guo; Dongyao Sun; Yongxin Lin; Kam W. Tang (Agriculture, Ecosystems & Environment, 2026)

Flexible Ultrasound Patch for Noninvasive, Targeted Anti-Angiogenic Therapy of Unstable Carotid Plaques - Jie Hu; Mingke Jiao; Chenchen Tang; Ping Liang; Jingwei Tang; Li Wan; Jimei Chen; Rui Li (Annals of Biomedical Engineering, 2026)

Soil pH Modulates the Global Stabilized Soil Organic Carbon - Cuijuan Liao; Mengxiao Yu; Ying‐Ping Wang; Philippe Ciais; Rose Z. Abramoff; Wenting Feng; Daniel S. Goll; Yuxin Zhang; Manseng Chio; Fayong Liu; Xuli Tang; Zilong Zhang; et al. (Global Change Biology, 2026)
Soil mineral‐associated organic carbon (MAOC) constitutes over 50% of total soil organic carbon (SOC) and serves as a key determinant of its long‐term stabilization. Although soil pH is recognized as a “master variable” in biogeochemical cycles, it remains unclear how soil pH influences MAOC and SOC at large spatial scales. To address this knowledge gap, we conducted a continental‐scale survey in China and synthesized global observations from literature, totaling 1300 independent observations. We analyzed the relationships between SOC and MAOC across pH gradients and assessed the contributions of other environmental factors to MAOC variability. Our results showed that higher SOC content is generally positively correlated with higher MAOC. However, this relationship is strongly influenced by soil mineralogy, texture, and climatic conditions. We identified distinct pH‐dependent pathways controlling MAOC formation. In acidic soils (pH ≤ 5.5), Fe/Al (hydr)oxides explain most of the variation in MAOC content and in MAOC fraction (the ratio of MAOC to SOC). In neutral‐to‐alkaline soils (pH > 6.5), however, clay content and mean annual temperature emerge as the primary regulators. Net primary productivity (NPP) augments the particulate organic carbon (POC) pool, thereby diluting the MAOC fraction. This divergence challenges the universal applicability of clay‐centric SOC models in acidic soils. Our findings provide a conceptual framework for biogeochemical models, urging the integration of pH‐dependent metal oxide dynamics to improve predictions of SOC persistence under diverse future scenarios.

Moisture-Proof Herbal Extract Pellets Prepared via Asymmetric Liquid Layering Technology Combined with Mesoporous Silica and Magnesium Stearate - Shilin Ma; Yupeng Feng; Panao Yuan; Yunlong Xu; Ping Shao; Lifeng Lin; Zimin Wang; Ling Han; Xing Tang (AAPS PharmSciTech, 2026)

Revealing the unrecognized climate burden of aquaculture systems: A global insight into greenhouse gas emissions and mitigation strategies - Yifei Zhang; Siyue Li; Ping Yang; Yiwen Zhang; Xixi Lu; Kam W. Tang; Hong Yang; Zhihua Wang; Guo Yu; Chuan Tong; Zhijie Zhang; Ping Jiang; et al. (Water Research, 2026)

X-ray CT-based investigation of mesoscopic pore structure and macro-meso coupled damage model for anisotropic lean clay under a freeze–thaw cycle - Yu Tang; Ping Yang; Jiahui Wang; Chang Huo (Transportation Geotechnics, 2026)

High-loading single-atom photocatalysts for high-selectivity conversion of CO2 to ethanol - Long-Shuai Zhang; Feiyao Wu; Shenrui Liang; Qianqian Tang; Hui Li; Huang Zhou; Fanqi Meng; Xunheng Jiang; Haiyan Liu; Qing Sun; Meifeng Wu; Yitao Cui; et al. (Science Bulletin, 2026)

Quantitative analysis and toxicological mechanisms of various male infertility inducers: A network meta-analysis and pharmacological approach - Muhammad Arif Asghar; Ao Zhang; Shixin Tang; Hang Han; Bing Wan; Jingwei Wu; Li Ping Wong; Xiao Zhang; Qinjian Zhao (Reproductive Toxicology, 2026)

Effect of protein–polyphenol interactions on the structural and digestive properties of pork myofibrillar proteins - Yu Chen; Qingyao Jiang; Yan Lu; Qiao Zeng; Ping Liu; Jiaxin Chen; Hongbin Lin; Jie Tang; Jie Zhao (Journal of Food Engineering, 2026)

Self-cleaning nanofiber membrane for efficient oil-water separation and dye degradation - Hai-chao Bai; Zi-yue Tang; Zi-ao Zong; Xin-ping Song; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Rijia Lin; Jingwei Hou (Journal of Cleaner Production, 2026)

Reversible hydrogen storage in Mg-functionalized B-doped graphene: A study based on density functional theory - Xiao Ling Liu; Shun Ping Shi; Lei Lei Tang; Kai Diao; Jia Bao Hu; Yi Liang Liu (Fuel, 2026)

An innovative triple-channel probing strategy for ultrasensitive detection of quercetin in food matrices based on carbon dots - Ping Li; Zhen-quan Yang; Lixia Xiao; Xuechao Xu; Tianzu Guan; Wenyuan Zhou; Xiaowei Tang; Xiaojuan Gong; Qin Hu (Food Chemistry, 2026)

Enhancement of protein gelation and nutritional properties in pea protein gels through enzymatic deamidation - Lijuan Luo; Ping Li; Yuanyuan Deng; Guang Liu; Yan Zhang; Xiaojun Tang; Pengfei Zhou; Zhihao Zhao; Jiarui Zeng; Mingwei Zhang (Food Hydrocolloids, 2026)

Metabolic microenvironment self-adaptive cobalt-based hydrogel dressing sustains spatiotemporal ROS generation for chronic diabetic wound repair - Ping Li; Lu Yang; Yifei Song; Shanshan Li; Wenhong Zheng; Mengteng Tang; Guoyang Xu; Wei Feng; Li-Li Li (Chemical Engineering Journal, 2026)

Dipole-engineered pyridinium iodide passivation for efficient Sn-Pb and all-perovskite tandem solar cells - Ciyu Ge; Chenwei Ni; Qi Xu; Bokai Hao; Wei Ai; Chengjie Deng; Peiyan Zhang; Xinzhi Zu; Hongyan Lu; Zeyu Zhang; Weijun Ke; Haisheng Song; et al. (Chemical Engineering Journal, 2026)

Contrasting biogeography of soil protists with broad versus narrow habitat ranges across forest types and climatic zones - Kai Fang; Yong-Ping Kou; Na Tang; Jia Liu; Xiao-Ying Zhang; Xiao-Hu Wang; Wen-Qiang Zhao; Hai-Jian Bing; Yan-Hong Wu; Qing Liu (CATENA, 2026)

Spring frost frequency increased in North America but decreased in Eurasia from 1948 to 2016 - Wei Guo; Chuhan Lu; Ping Xia; Lijiang Fu; Govindjee Govindjee; Hao Tang; Jian Chen; Li Song; Jinglu Tan; Zhenyu Xu; Ya Guo (Theoretical and Applied Climatology, 2026)

Changes and attribution of irrigation water demand in Central Asia - Shijia Wang; Jing Tian; Yongqiang Zhang; Xuanze Zhang; Haoshan Wei; Ping Miao; Hongli Ma; Xian Wang; Zixuan Tang (Regional Environmental Change, 2026)

Comprehensive genomic analysis of the maize ACP gene family reveals ZmACP1-mediated salt stress tolerance in Arabidopsis - Yunhao Wu; Junyu Chen; Hanqiu Ge; Xing Rong; Yuchen Wang; Meiwang Zhang; Zhigang Li; Yingrui Xi; Junfeng Tang; Junyi Li; Ping Li; Baohua Wang; et al. (Plant Cell Reports, 2026)

A multifunctional 5-fluorouracil prodrug: synthesis, biological evaluation, and antitumor mechanism investigation - Ran Zhang; Liqing Tang; Jianglong He; Guanyu Jiang; Yingfei Su; Xueping Jiang; Ping Wu; Dongyang Zhang; Sitong Chen; Hao Li; Zhongzheng Gui (Molecular Diversity, 2026)

A mixed mushroom poisoning in humans associated with the ingestion of Collybiopsis orientisubnuda - Xiu-Juan Li; Chang Xu; Wen-Hao Zhang; Jing Ma; Han-Chi Lei; Jia Li; Yu-Xian Gao; Xing Xia; Ping Wei; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Study on the dynamic interaction between buried bent pipes and soil under the influence of oblique incidence of SV waves - Chang-lu Xu; De-long Huang; Hui-yue Wang; Sha-sha Yu; Huan-qing Song; Hang Cen; Zi-yuan Huang; Qiang Liu; Ai-ping Tang (Soil Dynamics and Earthquake Engineering, 2026)

Educational tourism and environmental sustainability in China: A blessing or a burden? - Hui Min Li; Li Ping Lan; Chor Foon Tang (Journal of Environmental Management, 2026)

Lattice engineering of Li1.6Mn1.6O4 adsorbent materials mitigates Jahn-Teller distortion for efficient and stable lithium extraction from brine - Lu-Ri Bao; Zhi Ai Huang; Ling Zang; Wei Ping Tang; Shu-Ying Sun (Chemical Engineering Journal, 2026)

Isolation and characterization of a novel reassortant H3N8 avian influenza virus from chickens in Eastern China - Ping Wang; Jiamin Fu; Han Wu; Linwei Zhu; Taoming Tang; Zhigang Wu; Linfang Cheng; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Virus Genes, 2026)

Virgibacillus aidingensis sp. nov., a bacterium isolated from a hypersaline sediment in Xinjiang Province, North-west China - Li Yang; Hua-Wei Huang; Juan Wang; Cui-Ping Miao; Yi-Qing Li; Xiang-Tao Cen; Li-Xing Zhao; Wen-Yong Zhu; Shu-Kun Tang (Antonie van Leeuwenhoek, 2026)

Caffeoylquinic acid derivatives (CQAs) from Daphne gemmata and their antimicrobial activities - Lin Li; Fu-Qiang Song; Ping-Jing Yu; Li-Ping Tang; Xian Li (Natural Product Research, 2026)

Dual-function cytokines as modulators of autophagy: reprogramming inflammatory resolution in severe COVID-19 - Sohrab Khan; Ping Tang; Pingchang Yang; Jing Li; Haiqiang Wu (Inflammation Research, 2026)

Performance, metabolism, and resistance of an SMX-stressed continuous-flow AGS-MBR system: Microscopic mechanism of macroscopic instability phenomena - Yu Zeng; Haowei Gao; Huiya Huang; Wenqiang Xiong; Liying Bin; Bingda Liao; Weirui Chen; Xinyi Chen; Shanglong Wen; Ping Li; Shaosong Huang; Bing Tang (Water Research, 2026)

Efficient charge carrier separation over [Mo7O24]6- polyanions-intercalated porous graphitic carbon nitride for remarkably enhanced photocatalytic performance - Jiajia Liu; Yaodi Fu; Shimei Liu; Ping Li; Banpeng Cao; Lihong Cheng; Jingjing Liu; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Lingfang Qiu; Shuwang Duo (Process Safety and Environmental Protection, 2026)

Responses of mesozooplankton to extreme positive Indian Ocean Dipole (pIOD) and cold-core eddy in the eastern Equatorial Indian Ocean and southern Bay of Bengal during 2019/2020 winter - Ping Du; Xiao Ma; Yuanli Zhu; Ruijie Ye; Shenran Zhang; WNC Priyadarshani; P.A.K.N. Dissanayake; Haifeng Zhang; Yibo Liao; Yanbin Tang; Zhibing Jiang; Hongliang Li; et al. (Progress in Oceanography, 2026)

High-throughput screening identifies paullinic acid as an antiviral agent against Bombyx mori nucleopolyhedrovirus - Zhenwei Jia; Xiaoli Mo; Shidong Jiang; Li Sui; Yiling Zhang; Xueyang Wang; Jie Cheng; Ping Qian; Xudong Tang (Pesticide Biochemistry and Physiology, 2026)

Insights into pesticides-induced toxicity in the silkworm (Bombyx mori) from physiological responses to molecular mechanisms - Dan-Dan Bian; Shuang-Gui Dai; Bo-Ping Tang; Qiu-Ning Liu (Pesticide Biochemistry and Physiology, 2026)

Comparative machine learning strategies for improving antioxidant properties and aroma quality in fermented mung bean milkby Lactobacillus plantarum PC4 - Ping Tang; Aliah Zannierah Mohsin; Nurul Hanisah Juhari; Anis Shobirin Meor Hussin (International Journal of Food Microbiology, 2026)

Ammonia-oxidizing archaea as dominant and active ammonia oxidizers in agricultural soils from Yangtze River estuary by DNA-SIP - Xiufeng Tang; Lingyu Guo; Shijie Hua; Xiangyang Zhao; Tianjiao Zhang; Xingpan Guo; Ping Han; Chao Xue; Jun Yuan (International Biodeterioration & Biodegradation, 2026)

Benzofuran-based covalent organic framework with regular fiber-rod structure for efficient photocatalytic H2O2 production under broad visible light - Ting Xu; Zhongxing Zhang; Zijing Wang; Yihao Zhang; Yayang Wang; Yaowen Wang; Liguang Lin; Ping Xue; Jiming Huang; Mi Tang; Lingjun Kong; Xiangcheng Li; et al. (Chemical Engineering Journal, 2026)

Longitudinal decoupling between sedimentary phosphorus concentrations and sediment sorting in the Three Gorges Reservoir, China - Jinlin Li; Pingsheng He; Xiubin He; Jie Wei; Qiang Tang; Xiaoya Tang; Xin Gao; Ziqiang Mao; Ping Huang; Shengjun Wu (CATENA, 2026)

Antarctic sea ice anomaly: Its influence on interannual summer rainfall variability in East Asia and Adjacent Seas - Chunyan Xiao; Anmin Duan; Guoxiong Wu; Yuheng Tang; Qilu Wang; Ping Zhang (Atmospheric Research, 2026)

Cloning and functional study of NADPH-cytochrome P450 reductases and ent-kaurene oxidase from Rhododendron Molle G. Don - Xinmeng Wang; Zheng Liu; Rongfeng Wang; Hao Tang; Ping Su; Xianan Zhang; Xiaoyi Wu; Shurui Zhao; Jiadian Wang; Yating Hu; Luqi Huang (Physiology and Molecular Biology of Plants, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Therapeutic Effects of Low-Intensity Treadmill Exercise on Motor and Non-Motor Symptoms in a 6-Hydroxydopamine (OHDA) Rat Model of Parkinson’s Disease via Gut–Brain Axis Modulation - Yu-Tang Tung; Tu-Hsueh Yeh; Shu-Ping Tsao; Chun-Hsu Pan; Wen-Chao Chen; Wei-Ting Shih; Chih-Hsuan Lou; Hui-Yu Huang (Molecular Neurobiology, 2026)

Seismic Response of Utility Tunnels Under Oblique SV Wave Incidence in Horizontally Nonhomogeneous Sites - De-long Huang; Hui-yue Wang; Yang Ding; Hang Cen; Qiang Liu; Zhong-ling Zong; Dian-rui Mu; Ai-ping Tang (Geotechnical and Geological Engineering, 2026)

Toxicological Insights Into Multiple Pesticide Exposures in Red Swamp Crayfish ( Procambarus clarkii ): Molecular Mechanisms, Risk Assessments, and Future Perspectives for Aquaculture - Dan‐Dan Bian; Zi‐Yi Xing; Shuang‐Gui Dai; Xiang Lu; Dai‐Zhen Zhang; Bo‐Ping Tang; Bao‐Jian Zhu; Qiu‐Ning Liu (Reviews in Aquaculture, 2026)
The rice–crayfish integrated system (RCIS) is vital to Asian aquaculture, yet its sustainability is threatened by a critical paradox: pesticides used in rice cultivation jeopardize the health of the red swamp crayfish ( Procambarus clarkii ) and the safety of its products. This review systematically synthesizes evidence establishing oxidative stress as the central hub linking pesticide exposure to multilevel toxicity in P. clarkii . We delineate how pesticides dysregulate key pathways (PI3K/AKT/mTOR, MAPK, NF‐κB), triggering apoptosis, metabolic disruption, and immunosuppression. A pivotal mechanism involves pesticide‐induced gut microbiota dysbiosis, which diminishes beneficial short‐chain fatty acids and enriches pathogens, thereby amplifying intestinal barrier damage and host vulnerability. These interconnected processes collectively stunt growth and heighten susceptibility to pathogens like white spot syndrome virus (WSSV). Beyond organismal effects, we evaluate environmental pesticide fate and propose a novel risk assessment framework integrating these sublethal endpoints. Our proposed mitigation strategies include eco‐friendly pesticides, ecological engineering, and microbiome‐directed interventions. We advocate for future research prioritizing multi‐omics and mixture toxicity assessment. By deciphering this toxicity cascade and translating insights into practice, this review aims to protect the productivity, ecological integrity, and food safety of integrated aquaculture systems for long‐term sustainability.

Asymmetry of Tropical Pacific Precipitation Responses to El Niño and La Niña in a Changing CO 2 Pathway - Wen Zhang; Weichen Tao; Gang Huang; Ping Huang; Kaiming Hu; Ya Wang; Haosu Tang; Suqin Zhang (International Journal of Climatology, 2025)
In the tropical Pacific, El Niño (EN) typically causes positive precipitation anomalies further east than La Niña (LN)'s negative anomalies. This study constructs an idealised scenario of symmetrical CO 2 ramp‐up (RU) and ramp‐down (RD) phases to analyse the changes in asymmetric precipitation response to EN and LN. The results reveal that, during the CO 2 RD phase, tropical Pacific precipitation anomalies in EN and LN both shift more eastward and southward compared to the RU phase, but with more pronounced shifts in EN than LN. These structural changes in precipitation anomalies are primarily driven by the dynamic component associated with changes in circulation anomalies, which cannot be explained by variations in sea surface temperature (SST) anomalies. The spatial pattern of climatological SST changes between the CO 2 RD and RU phases exhibits an EN‐like warming structure, particularly extending southward, which enhances low‐level moisture and weakens atmospheric stability. Consequently, precipitation during EN responds more strongly to SST anomalies in this region, accompanied by eastward and southward shifts. While LN partially offsets the impact of the climatological warming pattern and results in less pronounced shifts, thereby contributing to the structural changes in the EN–LN asymmetry of precipitation anomalies.

Ferroptosis at the intersection of radiotherapy and immunotherapy - Gui-Xia Wei; Ya-Qin Zhao; Rong Tang; Hua-Shan Shi; Zhi-Ping Li (Cancer and Metastasis Reviews, 2025)

Generation and distribution of cyanide in rats and humans following sodium cyanoborohydride exposure - Zhenshuo Guo; Yiling Tang; Ruilin Zhang; Yu Ma; Ruxin Luo; Ping Xiang; Hui Yan; Wenjia Duan (Toxicology and Applied Pharmacology, 2025)

Rational tailoring of Li2MnO3 nanodomains for Li-Rich Mn-based cathodes - Shuangshuang Zhang; Xiaowen Zhao; Ping Wu; Xiyan Yue; Yawen Tang; Xin Cao; Haoshen Zhou (Science Bulletin, 2025)

Enantioselective study of hexythiazox in earthworms (Eisenia fetida): Bioaccumulation, degradation, enantiomer-specific profiling and perturbed metabolic pathways - Mengting Zhang; Yiyun Cai; Qixing Tang; Cancan Yang; Xiaojiang Ke; Jirui Wang; Lin He; Ping Zhang (Pesticide Biochemistry and Physiology, 2025)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Simulating and predicting lake dynamics by fusing HBV modeling, machine learning approach and remote sensing data - Muhammad Naeem; Yongqiang Zhang; Ning Ma; Zixuan Tang; Ping Miao; Xiaoqiang Tian; Congcong Li; Qi Huang; Zhenwu Xu; Longhao wang; Zhen Huang (Journal of Hydrology, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Metallurgical organic pollutants assisted source apportionment of mobile heavy metals on artisanal non-ferrous metal processing contamination - Li-Rong Liu; Junyao Yan; Lei Xiang; Ting Liu; Ye Xiao; Wen-Shen Liu; Wen-Jun Wu; Ping Li; Miaoyue Zhang; Yuan-Qing Chao; Ye-Tao Tang; Rong-Liang Qiu (Journal of Hazardous Materials, 2025)

Fabrication of S-scheme NiFe-LDH/Zn2In2S5 heterojunction for boosting photocatalytic hydrogen evolution - Xiaofeng Liu; Sihai Cai; Chunrong Li; Geng Tang; Tongyan Ren; Ping He (Journal of Environmental Chemical Engineering, 2025)

Quercetin alleviates ethanol-induced hepatocyte senescence by interacting with glycinamide ribonucleotide transformylase - Chen Huimin; Peng Shufen; Cui Zhaoyu; Liu Jiaxin; Chen Li; Yin Xingzhu; Wu Bangfu; Zhao Ying; Wang Yu; Mo Li; Liang Chanhua; Li Dongyan; et al. (Food Research International, 2025)

Fabrication of oil-in-natural deep eutectic solvents Pickering interfacial catalysis: Boosting a sustainable platform for enzymatic esterification of high-acid oil - Liyan Pan; Weiqi Liu; Yuanyuan Deng; Guang Liu; Yan Zhang; Xiaojun Tang; Ping Li; Zhihao Zhao; Jiarui Zeng; Mingwei Zhang; Pengfei Zhou (Food Chemistry, 2025)

Revealing the polyphenol modulation mechanism for in vitro gastric digestion properties of myofibrillar proteins via noncovalent interaction - Yan Lu; Chaoqun Chen; Yu Chen; Shuaiqian Wang; Yanping Hu; Ping Liu; Hongbin Lin; Jie Tang; Jie Zhao (Food Chemistry, 2025)

Electrostatic spray drying enhances transferrin hydrophilicity for improved rosmarinic acid binding: Insights into biological activity and molecular mechanism - Ru-yi Zhang; Zhi-shuo Zhang; Ting-ting Tang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Yan-jun Yang; Cui-hua Chang (Food Chemistry, 2025)

Low−temperature fabrication of highly reactive Al–Li alloy powders with enhanced HTPB compatibility and improved propellant combustion performance - Luyang Wang; Jiahe Li; Changsheng Tang; Pengxiang Li; Yulin Yang; Debin Xia; Jian Zhang; Ping Wang; Kaifeng Lin (Chemical Engineering Journal, 2025)

Enhanced piezoelectric demulsification for high-efficiency separation of water-in-oil (W/O) emulsions based on biomimetic PVDF/liquid metal nanofiber membranes - Wen-Qiang Qiu; Jia-Qi Luo; Qing-Ke Luo; Yan-Ping Zhao; Zhi-Yu Xue; Jing-Song Tang; Hai-Feng Lu; Yi Zhang; Da-Wei Fu (Chemical Engineering Journal, 2025)

Investigation on the strength characteristics of frozen lean clay influenced by anisotropy - Yu Tang; Jiahui Wang; Ping Yang (Cold Regions Science and Technology, 2025)

Ginkgetin inhibits the proliferation and migration of lung cancer cells via FAK/STAT3/AKT pathway - Longhua Sun; Wen Chen; Wenxin Yuan; Qianwen Huang; Hong Yang; Wei Zhang; Jianjun Tang; Ping Hu (Molecular Biology Reports, 2025)

Human umbilical cord mesenchymal stem cells improve the ovarian function through oxidative stress-mediated PERK/eIF-2α/ATF4/CHOP signaling in premature ovarian insufficiency mice - Pei-Ling Wu; Shi-Huan Tang; Han-Yue Wang; Hong-Mei Zhang; Lu Peng; Yao Liu; Yuan Yang; Chun-Bing Zheng; Xian-ping Zhang (Molecular Biology Reports, 2025)

The role of NLRP3 inflammasome-mediated pyroptosis in astrocytes during hyperoxia-induced brain injury - Qiao Liu; Yan Tan; Zhan-Wei Zhang; Wang Tang; Lei Han; Ke-Ping Peng; Ming-Hui Liu; Gui-Xiang Tian (Inflammation Research, 2025)

Comparative chloroplast genomic analysis: uncovering variations and phylogenetic relationships in tea plants from Shaoyang, Hunan Province, China - Jin Li; Yu Qin; Jun Tang; Xiao-Yan Qiu; Chang-Qing Xie; Han Tang; Ai-Ming Tang; Xiao Chen; Jun-Ping Xie; Hua Luo (Genetic Resources and Crop Evolution, 2025)

Genome-wide analysis and functional validation of the GH1 gene family in cotton under salt stress - Liting Zhang; Junfeng Tang; Xiaoyu Tian; Hui Fang; Yifan Xu; Yiming Qian; Mengxue Jia; Ping Li; Baohua Wang; Zhimin Zhuang (Functional & Integrative Genomics, 2025)

Experimental investigation on the influence of tunneling parameters on the test results of new soil abrasion testing method - Shao-Hui Tang; Xiao-Ping Zhang; Wei-Qiang Xie; Wei Sun (Bulletin of Engineering Geology and the Environment, 2025)

Dual-Aircraft Joint Observation of Cloud Microphysics in Typhoon Trami (2024) over the South China Sea - Shuai Zhang; Yufan Dai; Pak-Wai Chan; Ping Cheung; Jie Tang (Journal of Meteorological Research, 2025)

Robust and Explainable Objective Classification of Extreme Precipitation Events Using Machine Learning - Tao Tang; Ping He; Wenqiang Shen; Hao Qian; Junping Zhao; Xiaofen Lou; Ling Luo (Journal of Meteorological Research, 2025)

CPT1A facilitated ferroptosis by forming feedback loop with Nrf2 via PI3K/AKT pathway in colorectal cancer - Xiao-huan Li; Feng Lv; Si-qi Li; Hao-wei Deng; Li-ping Tang; Ke-zhi Li; Li-ye Xie; Bang-li Hu; Shu-fang Ning (Apoptosis, 2025)

Wind-tunnel simulation study of shelter effects of farmland shelterbelts with different configurations - Xiaoqian Li; Ping Lv; Zhuo Zhang; Lanjie Li; Xue Yang; Cheng Tang (Agroforestry Systems, 2025)

S100A11 mediates the protective effects of edaravone dexborneol on docetaxel-induced cognitive impairment in rats by inhibiting the MAPK signaling pathway - Ping Liu; Jiantao Jia; Yinliang Lu; Hanmin Tang; Chengyi Gao; Suxia Han (Toxicology and Applied Pharmacology, 2025)

Crude vs. condensate: Contrasting pollution trajectories and management implications from two major oil spills in China's marine ecosystems - Chuanyuan Wang; Ping Guo; Jianhui Tang; Haijiang Zhang (Marine Environmental Research, 2025)

Assessing the effectiveness of non-point source pollution models in data-limited urban areas - Fangze Shang; Sijie Tang; Hantao Wang; Ruiyi Yang; Zhiqiang Hou; Yang Ping; Zhenzhou Zhang; Huayu Chen; Yange Yu; Ashantha Goonetilleke; Changhyun Jun; Xin Tian; et al. (Journal of Hydrology, 2025)

Occurrence, distribution, and ecological risks of organic pollutants in global mangrove sediments - Yejiao Sun; Jiangwei Miao; Renjun Huang; Wangqing Tang; Sai Wang; Ping Li; Wei Qian; Jae-Seong Lee; Tuantuan Wang; Xiaoshan Zhu (Journal of Hazardous Materials, 2025)

Chaotic circuit-enhanced electrokinetic leaching of ionic rare earth ores with (NH4)2SO4-MgSO4 compound salt - Yu Wan; Anqi Li; Xin Zhang; Shiliang Gu; Guocan Zheng; Qian Zhan; Jinjing Tang; Changyuan Tao; Jinhui Li; Ping Li; Zuohua Liu (Journal of Cleaner Production, 2025)

Effect of fish skin gelatin on gluten proteins during freeze-thaw cycles - Mengjuan Li; Shangyuan Sang; Chin Ping Tan; Lijie Zhu; Xiaojuan Tang; Xin Zhang; Zixuan Yang; Xueming Xu (Journal of Cereal Science, 2025)

Enhancing electrochemical performance of BaCe0.3Fe0.7O3-δ cathodes via fluorine doping for proton-conducting solid oxide fuel cells - Qian Wang; Jiasheng Tang; Kai Luo; Junjie Wen; Ping Zhang; Zetian Tao (Fuel, 2025)

UPLC-Q-TOF-MS/MS driven quality characterization of market-dominant Huajiao cultivars: Varietal heterogeneity of amide compounds and drying process response pattern - Ping Xiang; Zhen-Ning Wu; Jin-Ming Gao; Jiang-Jiang Tang (Food Chemistry, 2025)

Microbiomics and machine learning-assisted approaches reveal amino acid patterns in high-temperature Daqu - Chao Fang; Gailing Shi; Qing He; Shuang Xing; Peng Chen; Feng Shi; Zhiguo Liu; Ping Tang; Liangcai Lin; Cuiying Zhang (Food Chemistry, 2025)

Analysis and formation mechanism of Key aroma compounds with ammonia-like off-flavors in Jiang-flavored high-temperature daqu: Substances composition and main microorganisms - Ping Tang; Qingliang Li; Changwen Li; Dongguang Xiao; Xiaodan Wang; Xuewu Guo (Food Bioscience, 2025)

Self-nanoemulsifying delivery system of PEITC ameliorates DSS-induced ulcerative colitis by regulating NF-κB pathway, modulating oxidative stress, and barrier repair - Haibo Huang; Changlong Ouyang; Haoxi Ma; Ping Tang; Zijun Wang; Yiyang Hou; Lijuan Zhu; Xiaojing Ma (Food Bioscience, 2025)

Sedimentation substantially buries more carbon than nitrogen or phosphorus in the Three Gorges Reservoir, China - Jinlin Li; Xiubin He; Jie Wei; Qiang Tang; Yuhai Bao; Xin Gao; Ziqiang Mao; Xiaoya Tang; Ping Huang; Shengjun Wu (Environmental Research, 2025)

Development of novel smartphone-based micro-electrochemical immunosensors for the point of care testing and typing of Helicobacter pylori in serum and whole blood - Yuhan Wang; Ping Zhang; Wei Fang; Chuxian Zhou; Gengzhou Yang; Wenwei Huang; Lijie Zhang; Xiaoli Zhang; Bing Gu; Minmin Li; Jiajie Liang; Yong Tang (Chemical Engineering Journal, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Seismic vulnerability analysis of utility tunnel with oblique incidence of SV waves based on IDA method in horizontal non-homogeneous field - Hui-yue Wang; De-long Huang; Hai-ruo Wang; Yang Ding; Hang Cen; Zi-Yuan Huang; Ai-ping Tang; Xia-xin Tao (Soil Dynamics and Earthquake Engineering, 2025)

Multi-grained estimation of nighttime light dynamics during the COVID-19 surge in Shanghai with SDGSAT-1 GIU imagery and point of interest data - Zheng Zhang; Huadong Guo; Dongmei Yan; Zhiqiang Liu; Weixiong Zhang; Jun Yan; Ping Tang (Remote Sensing of Environment, 2025)

Furofuran and tetrahydrofuran lignans from Lancea tibetica - Wenbo Li; Fuhua Zhu; Lu Tang; Jun Xu; Xiaoying Zhang; Zhicheng Duan; Wei Zhang; Ping Hai; Yongbiao Zheng; Haiqing Liu; Xia Li; Yanfang Su (Phytochemistry, 2025)

Extraction of lithium from cookeite-bearing claystone by chlorination roasting: From thermodynamic calculation to experimental practice - Ya Chen; Penghui Ping; Huoqiang Tang; Renlong Liang; Yongfeng Huang; Xilong Gu; Jiaqing Fan; Jiuqing Liu; Xichang Shi (Minerals Engineering, 2025)

Experimental study on photodynamic therapy of CCA assisted by electrolytic oxygen supply based on black phosphorus nanocomposites - Xinqiang Wu; Xiaofeng Jiang; Zhaoyuan Liu; Yuanfeng Gong; Ping Xue; Yunqiang Tang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Adsorption behavior and mechanism of VOCs on vinasse-derived biochar: Experimental and molecular simulation - Xiuwei Ma; Junjie Liu; Jie Zhou; Ping Tang; Yujia Wu (Journal of Environmental Chemical Engineering, 2025)

Piezoelectric polarization-induced electric field in Co-Co2P/BNT composite for enhanced peroxymonosulfate activation and rapid degradation of sulfamethoxazole - Xunwu Yang; Xiaomei Ma; Haodi Yang; Jie Zhao; Yigui Tang; Ping Ning; Chi Wang; Guijian Zhang; Shuangyou Bao; Kai Li (Journal of Environmental Chemical Engineering, 2025)

Enhanced aerobic granular sludge cultivation in continuous-flow membrane bioreactors: Evaluating a novel vertical circulation configuration and multi-mechanism approach - Tenglong Dai; Mengci Ni; Liying Bin; Weirui Chen; Ping Li; Xinyi Chen; Shanglong Wen; Shaosong Huang; Bing Tang (Journal of Environmental Chemical Engineering, 2025)

Experimental study on the mechanism of CO2/external fluid interaction in shale pore structure - Jianguang Wei; Qiuyu Lu; Ao Zhang; Zhejun Pan; Guo Li; Chao Tang; Ping Fu; Haoran Cheng; Ying Yang (Fuel, 2025)

Kinetics of MnO2-catalyzed combustion of carbonaceous materials in mold flux - Peng Cheng; Qiuping Li; Zerong Duan; Guanghua Wen; Ping Tang; Zibing Hou; Bingzhou He (Fuel, 2025)

Black rice stepwise fermentation enhances yogurt gel quality: Solidification rate, texture, LAB distribution and viability persistence - Jiarui Zeng; Zhiming Wang; Guang Liu; Xuchao Jia; Pengfei Zhou; Ping Li; Zhihao Zhao; Yan Zhang; Xiaojun Tang; Dong Liu; Yuanyuan Deng; Mingwei Zhang (Food Chemistry, 2025)

Synergistic neurotoxicity of polystyrene nanoparticles and MEHP in zebrafish (Danio rerio) - Yiyun Liu; Qi-Ping Tang; Si-Jia Zuo; Yuan Ding; Feng-Yi Guo; Bao-Fu Zhang; Qin-Hong Zhou; Dongmei Xie; De-Sheng Pei (Environmental Pollution, 2025)

Cosolvent-modulated polyamide nanostructures enable precise Mg2+/Li+ separation for lithium recovery from brines - Ping Li; Yuan Zhou; Chunxi Hai; Ying Cheng; Yu Tang; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu (Desalination, 2025)

Metagenomics-metabolomics integration reveals the impacts and action mechanisms of sulfamethoxazole in a continuous-flow aerobic granular sludge membrane bioreactor: System performance and microbial functional shifts - Wenqiang Xiong; Yu Zeng; Liying Bin; Weirui Chen; Xinyi Chen; Shanglong Wen; Shaosong Huang; Ping Li; Bing Tang (Chemical Engineering Journal, 2025)

Laser-free 'smart bomb': self-adaptive nanozyme for the treatment of multidrug-resistant Helicobacter pylori - Chao Sun; Yaya Bai; Rui Shen; Ping Yue; Jia Huang; Ziyun Yang; Jiani Song; Yixun Jin; Yunlong Yang; Yuming Tang; Weiyan Yao (Chemical Engineering Journal, 2025)

Design and performance of moisture-responsive piezoelectric nanogenerators based on electrospinning poly(vinylidene fluoride) films - Shuhui Li; Meijie Qu; Yonghao Chen; Ping Tang; Xiaobin Liang; Ken Nakajima; Yuezhen Bin (Chemical Engineering Journal, 2025)

Electrically driven single-atom Mo enhances support effect for efficient PMS activation to degrade high-concentration sulfanilamide - Yun Li; Yanjing Yang; Zan Gong; Liuyue Xiao; Siyi Chen; Ping Chen; Yalan Tang; Guowen He; Shian Zhong (Chemical Engineering Journal, 2025)

Targeted gene therapy for intracranial aneurysm using SOX17-CRISPRa - Dujie Xie; Yi Yuan; Panyao Long; Juan Huang; Mi Jiang; Yongzhong Tang; Yuanqiang Luo; Cancan Zhang; Ping Zheng; Liang Yang; Yiwei Chen; Xiaobo Li; et al. (Chemical Engineering Journal, 2025)

Chemical constituents of Engleromyces sinensis and their chemotaxonomic significance - Xiao-Xue Jiang; Lai-Wei Li; Xing-Ping Zhang; Ke-Pu Huang; Wen-Jie Ma; Li-Ping Tang; Kou Wang (Biochemical Systematics and Ecology, 2025)

Unlocking the power of sesquiterpenoids: phytochemistry and bioactivities in Artemisia (2017–2023) - Li Ping Tang; Tao Liu; Xiao Yu Han; Bin Li; Hong Dong Liu; Xue Mei Gao (Phytochemistry Reviews, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

The oncogenic role of NSUN2 in lung adenocarcinoma by stabilizing CCT5 mRNA via a YBX1-dependent m5C modification - Minxia Li; Ning Du; Ping Tang (Molecular and Cellular Biochemistry, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Novel genetically engineered silk materials for recycling polyethylene terephthalate (PET) plastic waste - Chi Tian; Yuancheng Wang; Dihua Yuan; Yanglin Li; Xinyu Tang; Yinlin Chen; Tinghao Luo; Guanwang Shen; Ping Zhao; Qingyou Xia (Journal of Hazardous Materials, 2025)

Comparative analysis of microplastic and microbial communities in varied aquatic environments: Disparities in occurrence, interconnections, and ecological implications - Lingfang Fu; Yongxin Guo; Jialiang Tang; Mengdi Yang; Lu Huang; Jieer Xiao; Zhongya Fan; Zhongyang Wang; Jiangyu Zhi; Zhiwei Huang; Huaiyang Fang; Ping Li (Journal of Hazardous Materials, 2025)

Ultrastable high internal phase Pickering emulsions stabilized by deamidated pea protein: Formation mechanisms and applications in 3D printing - Lijuan Luo; Ping Li; Yuanyuan Deng; Guang Liu; Yan Zhang; Xiaojun Tang; Pengfei Zhou; Zhihao Zhao; Mingwei Zhang (Food Chemistry, 2025)

Deciphering early molecular responses to benzotriazole ultraviolet stabilizers-induced toxicity using a dose-dependent yeast functional genomics approach - Xinyuan Xu; Linhao Zong; Shasha Zhang; Dake Cao; Ziqi Tang; Dong Chen; Ying Peng; Luhang She; Ping Jin; Xiaowei Zhang; Miao Guan (Environmental Pollution, 2025)

Cascade regulatory mechanism of soil organic phosphorus mineralization mediated by quorum sensing signal molecules C4/C6/C8-HSL: Dynamic response based on phosphatase secretion of core species - Zhenchao Wu; Jie Kang; Liangyang Mao; Yueyi Liu; Shuo Li; Weige Yao; Ying Yang; Xiujun Tu; Yuhao Guo; Jinyu Du; Xuan Tang; Tong Yang; et al. (Chemical Engineering Journal, 2025)

In situ microRNA-triggered self-assembled nano-lanterns with confinement effect for imaging-guided dual-enhanced gene therapy - Xianlan Wu; Hanqing Xu; Xiaoqi Tang; Jiangbo Liu; Qingxiang Yang; Qian Liu; Ping Huang; Shuang Zhao; Ming Chen; Kai Chang (Chemical Engineering Journal, 2025)

Logic-gate nanocompiler for oxidative/reductive molecular parallel detection during hepatic ischemia-reperfusion injury - Tao Tang; Fushou Liu; Longshua Qin; Hao Li; Wen-Ping Lin; Yi-Ping Gu; Fangtao Tan; Linfeng Wang; Huan Liu; Mingxi Zhang; Ran Cui (Chemical Engineering Journal, 2025)

A flexible self-powered multimodal sensor with low-coupling temperature, pressure and humidity detecting for physiological monitoring and human-robot collaboration - Long Ye; Zhenhua Tang; Junshu Feng; Yan-Ping Jiang; Xin-Gui Tang; Yi-Chun Zhou; Xiangjun Xing; Ju Gao (Chemical Engineering Journal, 2025)

Self-cleaning nanofiber membranes for sustainable dual removal of oils and dyes from wastewater - Hai-chao Bai; Yu-kun Sun; Zi-yue Tang; Zi-ao Zong; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Jingwei Hou; Rijia Lin (Chemical Engineering Journal, 2025)

Long-Term Fertilization Effects on Forms and Availability of Phosphorus Associated with Humic Substance Fractions in a Mollisol in Northeast China - Jinjing Zhang; Yuanhong Sun; Yuhan Yuan; Hongbin Ma; Yanhui Feng; Zhihan Zhang; Jiayi Tang; Cuilan Li; Mo Zhu; Ping Zhu (Journal of Soil Science and Plant Nutrition, 2025)

Influences of Long-Term Fertilization on Phosphorus Forms and Availability Within Particle-Size Fractions in a Mollisol - Jinjing Zhang; Yuanhong Sun; Jiayi Tang; Cuilan Li; Mo Zhu; Ping Zhu (Journal of Soil Science and Plant Nutrition, 2025)

Impact of Spartina alterniflora invasion and aquaculture reclamation on soil aggregate stability and carbon sequestration in Chinese coastal wetlands - Yanxun Xu; Wenjing Liu; Yule Lin; Hong Yang; Ping Yang; Guanpeng Chen; Dongyao Sun; Chuan Tong; Linhai Zhang; Wanyi Zhu; Kam W. Tang (Soil Ecology Letters, 2025)

MOF-on-MOF nanomaterial (Fe-MOF@UiO-66)-based ratiometric fluorescence/colorimetric dual-mode sensor for ultrasensitive detection of uric acid - Tao Lian; Rui Peng; Zhengyue Xiao; Xiaomin Tang; Peng Xu; Yu Hu; Ping Qiu (Analytica Chimica Acta, 2025)

Nitrite Toxicity in Shrimp Aquaculture: Mechanisms, Health Impacts, and Sustainable Mitigation Strategies - Dan‐Dan Bian; Yan‐Xia Shi; Xue Zhang; Xin Liu; Jun‐Jie Jiang; Xi‐Rong Zhu; Dai‐Zhen Zhang; Qiu‐Ning Liu; Bao‐Jian Zhu; Bo‐Ping Tang (Reviews in Aquaculture, 2025)
The rapid expansion of intensive aquaculture systems has caused escalating environmental challenges due to excessive nitrogenous waste accumulation, which surpasses the metabolic capacity of aquatic microbiota and elevates nitrite concentrations. As a pervasive environmental toxin, nitrite induces oxidative stress, disrupts metabolic homeostasis, and compromises gut microbiota and immune function in shrimp, leading to mass mortality, economic losses, and ecological disruption. These impacts threaten both aquaculture productivity and ecological sustainability. This review synthesizes three decades of research to elucidate the multifactorial mechanisms of nitrite toxicity, including genotoxicity, apoptosis, growth impairment, and dysregulated cellular signaling pathways. Key findings highlight that nitrite overload impairs mitochondrial function, dysregulates apoptosis pathways, and interferes with growth and reproductive processes, thereby undermining shrimp development and reproduction. To address these challenges, the review evaluates emerging mitigation strategies such as antioxidant‐enriched feeds, probiotic modulation, and biofloc technology, which optimize nitrogen cycling, enhance detoxification capacity, restore microbial equilibrium, and improve survival rates in experimental trials. Unlike prior fragmented studies, this review integrates mechanistic insights into nitrite toxicity with scalable interventions, proposing a novel decision framework for system‐specific nitrite management. This framework offers actionable recommendations for policymakers and industry stakeholders to balance aquaculture productivity with ecological sustainability. By advancing the understanding of nitrite's ecotoxicological impacts, this review charts a path toward resilient and sustainable aquaculture systems, transforming mechanistic insights into preventive protocols and offering a holistic perspective on nitrite pollution control that reconciles economic objectives with ecological sustainability.

Temporal and spatial pattern, sources, and main controlling factors of odor compounds in Qiandaohu Reservoir - Yi Chi; Zhanpu Tang; Yingjun Zhu; Lingjia Wang; Tianli Chen; Ping He; Yuxin Chen; Tong Sun; Siying Cai; Weijun zhang (Environmental Monitoring and Assessment, 2025)
The ubiquitous presence of algal-derived odors in large lakes and reservoirs constitutes a critical environmental concern. Particularly during the high-temperature summer months, localized regions of Qiandaohu Reservoir have exhibited markedly elevated concentrations of odor compounds. To investigate the intricate relationships among odor compounds, algae communities, and environmental factors in Qiandaohu Reservoir, and to forestall the impact of odor compounds on the quality of drinking water, this research implemented a systematic monthly survey to monitor several types of odor compounds, algal communities, physicochemical factors, and associated synthetases. The result demonstrated that the odor issue in Qiandaohu Reservoir is not yet severe. Among the detected compounds, dimethyl sulfide, dimethyldisulfide, and β-cyclocitral were all below the odor threshold, while dimethyl trisulfide, 2-methylisoborneol, geosmin, and β-ionone exceeded the odor threshold in some samples. The odor compounds are jointly influenced by abiotic environmental conditions and algae, presenting conspicuous horizontal, vertical, and seasonal distribution disparities. Notably, total nitrogen, total phosphorus, and the TN/TP ratio exert a substantial influence. Algae play a pivotal role in contributing to these odor compounds, warranting particular attention to the composition and dynamic alterations of the algal community during the summer and autumn seasons. This research comprehensively investigates the spatiotemporal patterns, sources, and controlling factors of odor compounds in a large drinking water source reservoir with relatively lower trophic status, providing new insights into odor management in such ecosystems.

A prospective study on the regulation of osteoarthritis risk through inflammatory pathways in clonal hematopoiesis - Ping Li; Zijian Kang; Ruiqi Ma; Chen Zhu; Ying Zhu; Iris Tang; Jianzheng Zhang; Kai Li; Qiang Tong (GeroScience, 2025)

The role of lactate metabolism in retinoblastoma tumorigenesis and ferroptosis resistance - Zhihui Zhang; Junjie Tang; Yaoming Liu; Yinghao Wang; Jinmiao Li; Yang Gao; Chao Cheng; Shicai Su; Shuxia Chen; Siming Ai; Ping Zhang; Rong Lu (Tissue and Cell, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A symbiotic bacterium regulates the detoxification metabolism of deltamethrin in Aedes albopictus - Si-jia Deng; Lei Tu; Lin Li; Ju-ping Hu; Ju-lin Li; Jian-xia Tang; Mei-chun Zhang; Guo-ding Zhu; Jun Cao (Pesticide Biochemistry and Physiology, 2025)

Oleanane-type triterpenoids from Sabia limoniacea with nitric oxide inhibitory activity - Ping Hou; Liwei Pan; Liuting Peng; Chunqiu Gan; Chenyang Ren; Ruiyun Yang; Weifeng Xu; Chaowen He; Yanlin Cui; Wen Tang; Jun Li; Yan Huang (Phytochemistry, 2025)

Machine learning analysis: Environmental and operational factors' influence on decay rate and organic sludge yield in full-scale wastewater treatment plants - Jinze Li; Lizhan Tang; Junyan Liu; Li-ping He; Li Gu; Shang Cheng; Yiyuan Wei; Binquan Jiao; Yongdong Chen (Journal of Water Process Engineering, 2025)

Optimizing storage-based reservoir operation schemes for enhanced large-scale hydrological modeling: A comprehensive sensitivity analysis - Li Tang; Guoqing Liu; Xiaohui Sun; Ping Liu (Journal of Hydrology, 2025)

Hydrodynamic and geomorphological responses of tidal flats to extreme climate events - Renzhi Li; Ya Ping Wang; Rui Yuan; Ning Zhao; Bixuan Tang; Zhixuan Feng; Bruno Castelle (Journal of Hydrology, 2025)

Fe-Ce synergy and oxygen vacancy activation: Engineering iron-based sorbents for gaseous arsenic capture - Yue Zhang; Zhiheng Niu; Deao Kong; Zhichao Tang; Guoqing Huang; Ruikun Wang; Ping Xiao; Shiqing Wang; Yutong Wang; Chunbo Wang (Journal of Environmental Chemical Engineering, 2025)

Molecular characterization and expression analysis of IL-21 and its four receptor genes in yellow catfish (Pelteobagrus fulvidraco) in response to Edwardsiella ictaluri infection - Zhang-Ping Li; Xin-Xin Jiang; Zi-Rui Tang; Mao-Mao Dong; Ping Jiang; Gui-Rong Zhang; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2025)

Extending CO2 and CH4 footprints of created habitats through drainage ditches in a subtropical coastal region of southeastern China - Yan Zhang; Yule Lin; Ping Yang; Hong Yang; Guanpeng Chen; Wenjing Liu; Chuan Tong; Yongxin Lin; Dongyao Sun; Wenbo Lin; Kam W. Tang (Environmental Research, 2025)

Bioluminescent fungi-inspired room temperature phosphorescence mycelia - Xin Li; Jin-Xin Ma; Ping Wu; Qian Gao; Hao Wang; Lu-Xin Tang; Feng Peng; Bao-Zhong Lü; Jing Si; Bao-Kai Cui (Chemical Engineering Journal, 2025)

Genome-wide identification and expression analysis of RWP-RK genes in Pyropia haitanensis reveals their roles in gametogenesis - Hong‑Chang Ding; Hui-Ping Ma; Long-Chen Tang; Xing‑Hong Yan (Journal of Applied Phycology, 2025)

Predation efficacy of Neoseiulus bicaudus on a prey mixture of Frankliniella occidentalis and Tetranychus turkestani - An-Di Zhu; Xin-Qi Liang; Si-Qiong Tang; Jie Su; Jing Chen; Zhi-Ping Cai; Jian-Ping Zhang (BioControl, 2025)

Chemical constituents of Penicillium ferraniaense GE-7 and their cytotoxicities - Yan Wang; Shao-Hua Song; Lei-Ming Wu; Xue Zhou; Qing-Ren Lu; Ai-Ping Yin; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2025)

Baoslingzhines Q−X: Structurally previously undescribed trace phenolic meroterpenoids from Ganoderma lucidum and their biological activities toward renal fibrosis and cytotoxicity - Yun-Yun Liu; Dan Cai; Xin-Ping Tang; Yong-Xian Cheng (Phytochemistry, 2025)

Biodegradation of polystyrene by Spodoptera litura and Spodoptera frugiperda larvae (Lepidoptera: Noctuidae): Insights into the frass characterization and responses of gut microbiomes - Ya-Yuan Tang; Jian-Ming Chen; Juan Zhang; Hong Wu; Yi-Ping Wang; Jue-Feng Zhang (Journal of Hazardous Materials, 2025)

Addressing challenges and advancing solutions: Enhancing semi-coking wastewater treatment for a sustainable prospect - Tingting Cui; Chunhui Zhang; Bingxu Quan; Liwei Wang; Zhao Zhang; Peidong Su; Yuanhui Tang; Guifeng Zhao; Ping Qiao; Junqiang Guo; Rui Zhang (Journal of Environmental Management, 2025)

A sensitive humidity-responsive actuator based on dispersing graphene oxide into chitosan- sodium alginate nanofibers - Yonghao Chen; Meijie Qu; Chenshen Liu; Shuhui Li; Xincheng Wang; Daixuan Gong; Ping Tang; Yuezhen Bin (Chemical Engineering Journal, 2025)

Study on the high-efficiency CO2 mineralization reaction mechanism of thermally modified materials from neutralized gypsum residue driven by sulfur vacancies in an aqueous environment - Yuwen Deng; Sisi Chen; Huidong Tang; Fei Wang; Yixing Ma; Lei Shi; Fan Du; Xin Sun; Kai Li; Ping Ning (Chemical Engineering Journal, 2025)

Preparation and combustion behavior of stabilized Al-Li compound fuel via mixing with ammonium perchlorate and metal oxides - Jiahe Li; Changsheng Tang; Luyang Wang; Yulin Yang; Debin Xia; Jian Zhang; Ping Wang; Kaifeng Lin (Chemical Engineering Journal, 2025)

Enhancing flood susceptibility predictions by using certainty factor in non-flood selection: a case study of Guangdong Province with four tree-based machine learning models - Jian Yang; Sixiao Chen; Zhongdong Duan; Yanan Tang; Ping Lu (Stochastic Environmental Research and Risk Assessment, 2025)

Dynamic changes in DNA methylation and correlated expressing genes during somatic embryogenesis in Hevea brasiliensis - Ling Li; Jia Miao; Jin Liu; Ming-Chun Gui; Min Tang; Hai Tian; Wan-Yuan Shi; Guo-Ping Liang; Xiao-Long Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

A systematic review of efgartigimod as an effective treatment for myasthenic crisis - Ping Tang; Yi He; Kaiqiang Xiao; Liang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Dual soil–rice interventions of silicon–selenium–calcium composites mitigate cadmium and arsenic accumulation in rice grains - Yang Ping; Zhenzhou Zhang; Jingwen Yu; Xiaofeng Zhai; Cuihong Yang; Peicheng Huang; Qi Liao; Mengying Si; Qingzhu Li; Chongjian Tang; Zhihui Yang (Environmental Geochemistry and Health, 2025)

Spring Rapid Temperature Variability in Southern China: Characteristics, Decadal Trend and Associated Climate Impacts on Crop Yield - Xianke Yang; Yixuan Zhang; Haosu Tang; Ping Huang; Xiaoxia Ling; Shaobing Peng; Dongliang Xiong (International Journal of Climatology, 2025)
Climate‐related risks are shaped not only by changes in mean temperatures, but also by temperature variability, which raises the likelihood of extreme weather events with profound impacts on society and ecosystems. Previous studies have documented contrasting seasonal trend differences in summer and winter temperature variability across most land areas. However, spring—a phenologically sensitive season for agricultural systems—has received limited attention for its temperature variability. Focusing on the major rice‐growing regions in southern China, this study employs three indices—daily temperature standard deviation (STD), day‐to‐day temperature variability (DTD) and rapid cooling events (RCE)—to analyse the decadal trends and causes of spring temperature variability and assess its climate effects on rice yield anomalies. Our results reveal decadal trends in the spatial distribution of temperature variability, with increasing frequency and intensity in the Yangtze River Basin and Yunnan Province, and a decreasing trend across much of South China, closely following regional climatological patterns. Overall, the frequency and intensity of RCE trend exhibit a “strong gets weaker, weak gets stronger” pattern, likely linked to increased STD trends caused by spatial non‐uniformity of warming. Through a multiple regression statistical model employing dominance analysis, we find that climate factors, including both mean climate and climate variability, explained 19%–45% of the variance in provincial rice yield anomalies, with up to 13% of the explained variance attributable to spring climate factors related to temperature variability. This study underscores the critical role of spring temperature variability in climate resilience, highlights the urgent need to enhance the adaptability of agricultural systems to extreme climate events.

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Tanshinone IIA inhibits neuronal ferroptosis and relieves cerebral ischemia‒reperfusion injury by regulating miR-449a/ACSL4 - Huimin Yu; Yili Li; Yuehong Yang; Yanjin Qian; Xia Gao; Xichan Wang; Ping Zhan; Dekun Tang; Mei Qin; Yan Qian (Metabolic Brain Disease, 2025)

Cepharanthine mitigates NIBV-induced pyroptosis via the MDA5/NF-κB/NLRP3 signaling pathway - Zhenni Liu; Ruoyun Tang; Mengbing Ding; Meiqin Wu; Ying Li; Cheng Huang; Qiurong Qi; Ping Liu; Xiaona Gao; Xiaoquan Guo (Veterinary Microbiology, 2025)

High-value use of whole plants of Eupatorium Adenophora Spreng for aluminium in hydrochloric acid anti-corrosion - Yun Gao; Ping Zhu; Xianghong Li; Liqing Tang; Yongqiang Chen; Yi Zhang; Juan Xu (Sustainable Chemistry and Pharmacy, 2025)

Great Oxidation Event was caused by Neoarchean global cratonization: opportunity and challenge from rock and sedimentary records in China - Li-Gang Zhou; Jun-Ping Liu; Jing Li; Zai-Bo Sun; Lu Xiang; Yan-Yan Zhou; Hao-Shu Tang; Yan-Bin Zhang; Xi-Yan Zhu; Hai-Long He; Ming-Guo Zhai (Science Bulletin, 2025)

Selenium-calcium-magnesium co-application mitigates cadmium toxicity in rice: Mechanisms of cell wall detoxification and transporter gene regulation - Chukwuma Arinzechi; Peicheng Huang; Pengwei Zhao; Chongjian Tang; Mengying Si; Qi Liao; Qiming Wang; Yang Ping; Qingzhu Li; Zhihui Yang (Rhizosphere, 2025)

Characterization and functional analysis of the small heat shock protein HSP19.5 in Bombyx mori in response to Nosema bombycis infection - Zhenghao Han; Shidong Jiang; Jingxian Xie; Ibouanga Sama Lucreche Poupina; Xiaoli Mo; Li Sui; Ping Qian; Xudong Tang (Journal of Invertebrate Pathology, 2025)

Effects of pore water flow rate on microplastics transport in saturated porous media: Spatial distribution analysis - Henglei Xu; Ping Tang; Yongchao Zhou; Yiping Zhang; Tuqiao Zhang (Journal of Hazardous Materials, 2025)

Innovative catalytic approaches in fabricating bimetallic heterostructures for remediation of antibiotic-polluted water: Mechanistic insights and application prospects - Ping Yan; Honghong Lyu; Xinchen Gong; Zhiqiang Wang; Boxiong Shen; Jingchun Tang (Journal of Environmental Management, 2025)

Recognizing the state of aerobic granular sludge over its life-cycle in a continuous-flow membrane bioreactor with an artificial intelligence approach - Yu Zeng; Chenguang Zhao; Danling Ma; Liying Bin; Weirui Chen; Ping Li; Bing Tang (Journal of Environmental Management, 2025)

Promotional activity of an uncharacterized protein Bm0979 on Nosema bombycis in silkworm, bombyx mori - Yujia Fang; Qiong Yu; Wenzhe Chen; Zhenghao Han; Qingsheng Qu; Zhenwei Jia; Shidong Jiang; Jie Cheng; Xudong Tang; Ping Qian (Journal of Asia-Pacific Entomology, 2025)

Effects of different cooking times on the sensory evaluation and flavor characteristics of soy sauce - Xing Gao; Xiaomo Han; Mingguang Yu; Yuan Tang; Huanlu Song; Qi Meng; Rifeng Chen; Jiang Yu; Ping Yang; Zhili Yu (International Journal of Gastronomy and Food Science, 2025)

Terpene-conjugated curcumin analogs alleviated alcoholic liver injury in rats through mitigation of intestinal barrier abnormalities - Shuaihu Tao; Ruanping Song; Ziyu Wang; Wenjing Xie; Siyuan Xiao; Yangyang Liao; Xinjie Zhang; Qiongdan Hu; Xinxing Tang; Jingyuan Huang; Wan Liao; Hongtao Xiao; et al. (Food Bioscience, 2025)

Metabolomics-based discrimination of geographical variability in quality and antioxidant activity of golden mushroom (Floccularia luteovirens) from the Qinghai-Tibet Plateau - Yishui Cai; Ping Deng; Jiale Liu; Yang Luo; Tajie Sangzhu; Haozheng Li; Yunqi Zhao; Cailin Tang; Manjun Yang (Food Bioscience, 2025)

Transcriptome analysis reveals the mechanism of cortisol through GR regulating the expression of inflammatory cytokines in Siberian sturgeon (Acipenser baerii) after LPS treatment in vitro - Peng Tang; Yinqiu Chen; Defang Chen; Hao Zhu; Shaotong Dai; Jiawen Zhou; Xin Zhang; Xiaoli Huang; Ping Ouyang; Yi Geng; Zhiqiong Li (Fish & Shellfish Immunology, 2025)

The effect and mechanisms of nano cerium dioxide (Nano-CeO2) on cardiovascular development in zebrafish (Danio rerio) - Yiyun Liu; Yan-Ling Liao; Jin-Xia Wang; Bao-Fu Zhang; Qi-Ping Tang; Yuan Ding; Si-Jia Zuo; Qin-Hong Zhou; De-Sheng Pei (Environmental Pollution, 2025)

Discovery of potent MD2 inhibitors by hierarchical virtual screening strategy and bioactivity evaluation - Lili Yang; Jialu Liu; Lei Di; Siming Tang; Ping Hu; Fang Wang; Zeng Li (Chemico-Biological Interactions, 2025)

Evolving Therapeutic Landscape of Intracerebral Hemorrhage: Emerging Cutting-Edge Advancements in Surgical Robots, Regenerative Medicine, and Neurorehabilitation Techniques - Danyang Chen; Zhixian Zhao; Shenglun Zhang; Shiling Chen; Xuan Wu; Jian Shi; Na Liu; Chao Pan; Yingxin Tang; Cai Meng; Xingwei Zhao; Bo Tao; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the most serious form of stroke and has limited available therapeutic options. As knowledge on ICH rapidly develops, cutting-edge techniques in the fields of surgical robots, regenerative medicine, and neurorehabilitation may revolutionize ICH treatment. However, these new advances still must be translated into clinical practice. In this review, we examined several emerging therapeutic strategies and their major challenges in managing ICH, with a particular focus on innovative therapies involving robot-assisted minimally invasive surgery, stem cell transplantation, in situ neuronal reprogramming, and brain-computer interfaces. Despite the limited expansion of the drug armamentarium for ICH over the past few decades, the judicious selection of more efficacious therapeutic modalities and the exploration of multimodal combination therapies represent opportunities to improve patient prognoses after ICH.

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Roseateles cavernae sp. nov., a Bacterium Isolated from Freshwater of the Old Huanglong Cave in Yunnan Province, South-West China - Yu-Man Zhang; Qian Jiang; Mu-Yao Li; Qing-Yu Miao; Yi-Qing Li; Min Yin; Cui-Ping Miao; Shu-Kun Tang (Current Microbiology, 2025)

Construction and immunogenicity analysis of a recombinant baculovirus targeting the N protein of SARS-CoV-2 - Bohan Yu; Xiaoli Mo; Li Sui; Yujia Fang; Xudong Tang; Ping Qian (Biotechnology Letters, 2025)

Metabolism study of two phenethylamine − derived new psychoactive substances using in silico, in vivo, and in vitro approaches - Yiling Tang; Linhao Xu; Zhenshuo Guo; Junbo Zhao; Yue Xiao; Ping Xiang; Lili Xu; Hui Yan (Archives of Toxicology, 2025)

Transepithelial Transport of Hemp Protein-Derived Bioactive Peptide Trp–Tyr–Thr (WYT) in Human Caco-2 Cell Monolayers - Ping Wei; Dongning Ling; Yayuan Tang; Zhonglin Deng; Zhen Wei; Guoming Liu (International Journal of Peptide Research and Therapeutics, 2025)

One stone, three birds: Recovery of high-quality niobium and iron products from niobium-bearing tailings using low-temperature fluidized hydrogen reduction technology - Jiahao He; Zihang Wang; Ping Zhao; Shuai Yuan; Peng Gao; Zhidong Tang (Process Safety and Environmental Protection, 2025)

Five undescribed chromone-phenylpyridone hybrids from Cineraria repanda-derived Penicillium oxalicum with cytotoxic and antibacterial activity - Yu Wei Huang; Jing Guan; Yin Tang; Ren Xiang Tan; Li Ping Lin (Phytochemistry, 2025)

Conversion of earthen aquaculture ponds to integrated mangrove-aquaculture systems significantly reduced the emissions of CH4 and N2O - Zhinan Su; Guanglong Qiu; Ping Yang; Hong Yang; Wenjing Liu; Lishan Tan; Linhai Zhang; Dongyao Sun; Jiafang Huang; Kam W. Tang (Journal of Hydrology, 2025)

Elevated N2O emissions from coastal small water bodies: Implications for greenhouse gas inventories - Lele Tang; Wenjing Liu; Hong Yang; Ping Yang; Chuan Tong; Yongxin Lin; Dongyao Sun; Wenjing Tan; Wenbo Lin; Pingping Guo; Linhai Zhang; Kam W. Tang (Journal of Hydrology, 2025)

Fluvial downcutting and its influence on human settlement in the middle reaches of the Lancang River - Gang Hu; Changcheng Hu; Xiaowen Wu; Gaoyuan Pan; Daoba Zhuma; Qionghui He; Huiying Wang; Ping Wang; Liubing Xu; Jinming Xie; Jiafu Zhang; Xin Wang; et al. (Geomorphology, 2025)

Piezoelectric-enhanced rapid degradation of sulfamethoxazole using the Co3O4/Bi0.5Na0.5TiO3/Peroxymonosulfate process - Xiaomei Ma; Xunwu Yang; Kai Li; Ping Ning; Xin Sun; Yigui Tang; Shuangyou Bao; Chi Wang (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Dynamic analysis of fungal community and metabolome associated with postharvest diseases in banana peel under natural condition - Ping Yi; Ming Zhao; Fang Huang; Li Li; Jian Sun; Lihong Xie; Dongning Ling; Jiemin Li; Min Huang; Ting Gan; Yayuan Tang; Changbao Li; et al. (Postharvest Biology and Technology, 2025)

Plastic-lined ponds and eco-aquaculture systems had lower CO2 emissions than earthen aquaculture ponds - Min Lv; Zhinan Su; Guanglong Qiu; Kam W. Tang; Yan Hong; Yifei Zhang; Yingyi Chen; Jiafang Huang; Wanyi Zhu; Hong Yang; Ping Yang (Journal of Hydrology, 2025)

Cooperation of Lactoplantibacillus plantarum and polyethylene microplastics facilitated the disappearance of tetracycline during anaerobic fermentation of whole plant maize - Yubo Zhang; Pan Wang; Yu Tang; Chaosheng Liao; Xiaolong Tang; Pai Hou; Cheng Chen; Xiaokang Huang; Guangrou Lu; Lin Li; Mingjie Zhang; Fuxiang Li; et al. (Journal of Hazardous Materials, 2025)

Restoring turbid eutrophic shallow lakes to a clear-water state by combined biomanipulation and chemical treatment: A 4-hectare in-situ experiment in subtropical China - Bo Li; Deyuan Chen; Jichong Lu; Suxia Liu; Jiale Wu; Lei Gan; Xiaoqin Yang; Xiaolin He; Hu He; Jinlei Yu; Ping Zhong; Yali Tang; et al. (Journal of Environmental Management, 2025)

Boosting photocatalytic ozonation activity through F or I doping in g-C3N4: A trade-off between stability and performance - Weirui Chen; Weijie Chen; Yimin Luo; Yanqi Feng; Xukai Li; Jing Wang; Ping Li; Liying Bin; Bing Tang; Laisheng Li (Journal of Environmental Chemical Engineering, 2025)

Unveiling the secrets of the bistability of aerobic granular sludge in a continuous flow membrane bioreactor for treating real municipal wastewater - Biao Yang; Liying Bin; Weirui Chen; Xinyi Chen; Ping Li; Shanglong Wen; Shaosong Huang; Zhiqi Zhang; Bing Tang (Chemical Engineering Journal, 2025)

Advancing lactic acid Fermentation: Effects of micro aeration and herbal waste on red clover bioconversion - Chaosheng Liao; Mingjie Zhang; Pan Wang; Xiaolong Tang; Minghong You; Changbing Zhang; Guofu Jia; Wenlong Gou; Ning Mao; Yixiao Xie; Chao Chen; Shiqie Bai; et al. (Chemical Engineering Journal, 2025)

The Role of ICP Monitoring in Minimally Invasive Surgery for the Management of Intracerebral Hemorrhage - Ge Zhang; Yunjie Li; Danyang Chen; Zhuojin Wu; Chao Pan; Ping Zhang; Xingwei Zhao; Bo Tao; Han Ding; Cai Meng; Diansheng Chen; Wenjie Liu; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the second major stroke type, with high incidence, high disability rate, and high mortality. At present, there is no effective and reliable treatment for ICH. As a result, most patients have a poor prognosis. Minimally invasive surgery (MIS) is the fastest treatment method to remove hematoma, which is characterized by less trauma and easy operation. Some studies have confirmed the safety of MIS, but there are still no reports showing that it can significantly improve the functional outcome of ICH patients. Intracranial pressure (ICP) monitoring is considered to be an important part of successful treatment in traumatic brain diseases. By monitoring ICP in real time, keeping stable ICP could help patients with craniocerebral injury get a good prognosis. In the course of MIS treatment of ICH patients, keeping ICP stable may also promote patient recovery. In this review, we will take ICP monitoring as the starting point for an in-depth discussion.

Loading of redox-active metal Fe largely enhances the capacity of biochar to mitigate soil N2O emissions by promoting complete denitrification - Dan Yuan; Ping Wu; Jiao Yuan; Zhifen Jia; Chunsheng Hu; Tim J. Clough; Nicole Wrage-Mönnig; Jiafa Luo; Jiahuan Tang; Shuping Qin (Biology and Fertility of Soils, 2025)

Influences on the phytochemical characteristics and multiple bioactivities of Mesona chiensis Benth polysaccharides in response to different drying methods - Yayuan Tang; Zhen Wei; Ping Wei; Ping Yi; Guoming Liu; Changbao Li; Li Li; Jian Sun; Xuemei He (Food Research International, 2025)

The H2S-releasing multifunctional composite ionic liquid facilitates topical melittin delivery for psoriasis treatment through RONS scavenging and inflammation inhibition - Meng Zeng; Ping Deng; Qin Li; Qi Tang; Jixiang Li; Liangke Zhang (Chemical Engineering Journal, 2025)

Transforming behavior and removal mechanism of phosphorus from municipal wastewater in a continuous flow aerobic granular sludge-membrane bioreactor: Unveiling the functional genes associated with phosphorus metabolism - Bingduo Wang; Mengci Ni; Yu Zeng; Biao Yang; Lei Shang; Liying Bin; Weirui Chen; Ping Li; Xinyi Chen; Shanglong Wen; Shaosong Huang; Bing Tang (Chemical Engineering Journal, 2025)

Multi-omics analysis of the accumulation mechanism of flavonoids in rice caryopsis under blue light - Ping Zhang; Yongsheng Tang; Juxiang Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Guofei Jiang; Xuqin Wang; Lingyuan Zhang; Yutao Bai; Peng Qin (Plant Cell Reports, 2025)

Sex-biased juvenile hormone and gene expression underlie sex difference of stress resistance in the American cockroach - Fangfang Liu; Shudian Zhang; Ping Chen; Wei Tang; Xiaoyi Chen; Yingting Wu; Sishi Xia; Diqi Peng; Zhengyi Shao; Qin Li; Yuqing Liu; Xiaoshuai Zhang; et al. (Journal of Pest Science, 2025)

Effects of plant invasion and land use change on soil labile organic carbon in southern China’s coastal wetlands - Lihua Wang; Wenjing Liu; Xueya Zhou; Shenglei Fu; Ping Yang; Chuan Tong; Hong Yang; Dongyao Sun; Linhai Zhang; Wanyi Zhu; Kam W. Tang (Soil Ecology Letters, 2025)

Risk assessment of rip current in China: based on data from 33 beaches - Wenwen Tang; Qi Chen; Yibing Zong; Fan Zhang; Ya Ping Wang; Jianjun Jia (Geo-Marine Letters, 2025)

Composition of breeding bird communities under different intensities of human activity: A case study in Jiulingshan Nature Reserve in eastern China - Bo Zhou; Gang Yang; Mingxiao Di; Ping Lu; Xiaodong Weng; Jiuheng Xu; Yong Tang; Yong Peng; Xinyu Tao (Acta Oecologica, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

Estradiol Enhances Cerebellar Molecular Layer Interneuron-Purkinje Cell Synaptic Transmission and Improves Motor Learning Through ER-β in Vivo in Mice - Yong-Rui Piao; Mei-Rui Li; Ming-Ze Sun; Yang Liu; Chao-Yue Chen; Chun-Ping Chu; Yuki Todo; Zheng Tang; Chun-Yan Wang; Wen-Zhe Jin; De-Lai Qiu (The Cerebellum, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The catalytic mechanism of cobalt-based sites in the oxidation of MgSO3 - Zhaorui Li; Xin Tang; Fei Wang; Kai Li; Shi Lei; Ning Ping; XingYi Ma; Xin Sun (Process Safety and Environmental Protection, 2025)

Distinct mantle sources of two types of Neoproterozoic diabase in the North China Craton: Implications for mantle plume activity and ancient continent reconstruction - Qi Hou; Xiao-Ying Gao; Xiao-Yong Yang; Jun Tang; Shao-Bing Zhang; Zhang-Ping Liu; Cai-Yu Wan (Precambrian Research, 2025)

Mechanically and boiling water stable superhydrophobic coatings with special composite structures prepared by facile spraying method - Ping Zhu; Jiadong Geng; Lijing Zhu; Gang Wang; Lei Tang; Hongyi Hu; Zhixiang Zeng (Journal of Environmental Chemical Engineering, 2025)

Evaluation of the shear stability of aerobic granular sludge from a pilot-scale membrane bioreactor: Establishment of a quantitative method - Biao Yang; Bingduo Wang; Liying Bin; Weirui Chen; Xinyi Chen; Ping Li; Shanglong Wen; Shaosong Huang; Zhiqi Zhang; Bing Tang (Journal of Environmental Sciences, 2025)

Application of 3-D inversion of AMT data in exploration of concealed nonmetallic deposits: A Case Study on the Huashitou Mountain fluorite deposit in Beishan metallogenic belt, China - Jianhui Hu; Liuyang Xu; Yaotian Yin; Xu Jia; Ping Qi; Zhan Liang; Peng Su; Cheng Liu; Weidong Tang; Long Chen; Yanzhou Wang; Lin Liu (Journal of Applied Geophysics, 2025)

Magnetic evidence of redox transition event in the Okinawa Trough during the early-middle Holocene and its links to the Kuroshio Current evolution - Feng Wang; Tuqin Huang; Zhongbo Wang; Weiguo Zhang; Pengyu Qiao; Haiyan Tang; Xi Mei; Ping Yin; Zhongping Lai (Global and Planetary Change, 2025)

Aquaculture source of atmospheric N2O in China: Comparison of system types, management practices and measurement methods - Yifei Zhang; Guanghui Zhao; Ping Yang; Changchun Song; Yang Wang; Yiwen Zhang; Yuxing Zou; Zhuangpeng Zheng; Kam W. Tang; Siyue Li (Environmental Research, 2025)

Use of biochar derived from Spartina alterniflora to reduce sediment methane (CH4) production potential during non-farming period in earthen aquaculture ponds - Ping Yang; Dongyao Sun; Wenjing Liu; Kaiyuan Liu; Hong Yang; Chuan Tong; Linhai Zhang; Yongxin Lin; Derrick Y.F. Lai; Lishan Tan; Weifeng Chen; Kam W. Tang (Environmental Pollution, 2025)

Insights into the formation and development of membrane fouling in a continuous flow aerobic granular sludge membrane bioreactor - Mengci Ni; Juan Jiang; Biao Yang; Bingduo Wang; Liying Bin; Weirui Chen; Ping Li; Shaosong Huang; Bing Tang (Chemical Engineering Journal, 2025)

Efficient oxidative cyanation of fructose to nitriles over Acidic-MnO under ambient air pressure - Wenjie Shao; Junpeng Wang; Meiying Niu; Jun Tang; Qiuhong Pan; Ziguo He; Ping Cui; LiFeng Chen; Zhiyong Fang; Qingping Ke (Chemical Engineering Journal, 2025)

Astragalus polysaccharide/carboxymethyl chitosan/sodium alginate based electroconductive hydrogels for diabetic wound healing and muscle function assessment - Letian Tang; Shuyang Xie; Danyang Wang; Yiying Wei; Xiaopu Ji; Yicheng Wang; Nana Zhao; Zonglei Mou; Baoping Li; Wan Ru Sun; Ping Yu Wang; Nicola Paccione Basmadji; et al. (Carbohydrate Polymers, 2025)

Bacillus subtilis YN2014090 Water-Dispersible Granular Formulation for Controlling Powdery Mildew On Cucumber - Junjie Wu; Pengfei He; Pengbo He; Yixin Wu; Yingjie Jiang; Ping Tang; Guowen Tang; Shahzad Munir; Yueqiu He (Journal of Crop Health, 2025)

Application of sex-specific markers in identifying the sex of Pyropia haitanensis from different sources - Hong-Chang Ding; Hui-Ping Ma; Long-Chen Tang; Xing‑Hong Yan (Journal of Applied Phycology, 2025)

Plasma Ionomic Profile and Interaction Patterns in Coronary Artery Disease Patients - Qing-Qing Zhao; Xian-Long Shu; Zhen Yuan; Qian Gao; Ying Huang; Yuan-Qing Yang; Li-Ming Peng; Guo Wang; Xiao-Ping Chen; Bi-Lian Chen; Jie Tang (Biological Trace Element Research, 2025)

Influence of waste glass on concrete strength and permeability during dry-wet cycles - Xuebing Zhang; Yang Quan; Guohui Cao; Shenghua Tang; Wanji Ou; Jun Cao; Baikuang Chen; Luoqing Liu; Zhichao Wang; Ping Xiang (European Journal of Environmental and Civil Engineering, 2025)

Effect of cortisol through GR regulated inflammatory cytokine expression and apoptosis of Siberian sturgeon (Acipenser baerii) after LPS treatment - Peng Tang; Hao Zhu; Defang Chen; Yinqiu Chen; Shuhuang Chen; Youlian Liu; Xin Zhang; Xiaoli Huang; Zhiqiong Li; Ping Ouyang; Yi Geng (Aquaculture, 2025)

Formation and characterization of artificial gynogenetic northern snakehead (Channa argus) induced by inactivated sperm of mandarin fish (Siniperca chuatsi) - Anmin Liao; Shuxin Zhang; Qiuyan Yu; Yude Wang; Huifang Tan; Ping Wu; Yue Ding; Biao Hu; Wuxia Liu; Min Tao; Chun Zhang; Qinbo Qin; et al. (Aquaculture, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Penicipyrrolizidinones A−C, three pyrrolizidinone alkaloids with unprecedented skeletons from the mangrove-derived fungus Penicillium sp. DM27 - Zhenling Chen; Jing-Jing Zhang; Cheng-Yun Huang; Wei-Chen Chen; Li-Ming He; Qing-Qing Tang; Kong-Kai Zhu; Jing Li; Ping Gao; Meng-Ke Zhang; You-Sheng Cai (Phytochemistry, 2025)

Enhancing the affinity of Pb(II) to the metastable ferrihydrite with the presence of gallic acid and anoxia condition - Hao Luo; Yingjing Tian; Fenglian Fu; Liying Bin; Weirui Chen; Ping Li; Bing Tang (Journal of Environmental Management, 2025)

In situ reactivation of aerobic granular sludge in a membrane bioreactor after long-term storage: Revealing the variation in metabolic pathways under restored bioactivity - Yu Zeng; Bingduo Wang; Liying Bin; Weirui Chen; Ping Li; Xinyi Chen; Shanglong Wen; Shaosong Huang; Bing Tang (Chemical Engineering Journal, 2025)

Ultrahigh energy storage density and efficiency of antiferroelectric AgNbO3-based MLCCs via reducing the off-center cations displacement - Ting Tang; Dong Liu; Long Wang; Jiaze Li; Zheng Zhang; Lei Zhao; Bo-Ping Zhang; Li-Feng Zhu (Chemical Engineering Journal, 2025)

Intelligent online sensing of lubricating oil debris via dual-electrode oil-driven triboelectric nanogenerator - Long Wang; Jian Yu; Ping Wang; Lei Yang; Xijing Yu; Jianlong Qiu; Kunpeng Tan; Yuanbin Tang; Yanjie Guo (Chemical Engineering Journal, 2025)

A Machine Learning-Based Observational Constraint Correction Method for Seasonal Precipitation Prediction - Bofei Zhang; Haipeng Yu; Zeyong Hu; Ping Yue; Zunye Tang; Hongyu Luo; Guantian Wang; Shanling Cheng (Advances in Atmospheric Sciences, 2025)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

Comparative study of fenpropathrin and its main metabolite in soil-earthworm microcosms: Toxicity, degradation, transcriptome, and oxidative stress - Ping Zhang; LuLu Ran; Cancan Yang; Can Tang; Xiaojiang Ke; Zhifeng Xu (Science of The Total Environment, 2024)

Abscisic acid treatment positively regulates suberin polyaliphatics biosynthesis at wound sites in postharvest yam tubers - Xiaopeng Wei; Jing Xue; Ping Geng; Guo Liu; Ziyan Zhou; Chuanxue Yin; Yiwen Ji; Jiajun Dai; Guanhua Tang; Guangyuan Zhao; Wei Zong; Zhenzhen Ge; et al. (Postharvest Biology and Technology, 2024)

Bearing performance and failure mechanisms of HSCM piles in marine soft soil under lateral loads - Hang Cen; Jun-nan Zhao; Zhong-ling Zong; De-long Huang; Ding-wen Zhang; Hui-yue Wang; Ai-ping Tang (Ocean Engineering, 2024)

Petrogenesis of the Zenong Group volcanics in the central Lhasa subterrane, Tibet: Geodynamic implications of the scissor-like southward subduction of the Shiquanhe-Jiali Tethyan Ocean - Jia-jia Yu; Wei Chen; Ju-Xing Tang; Cheng-Yang Wang; Xu-Dong Ma; Qing-Ping Liu; Meng-Xiang Di; Chang Liu (Lithos, 2024)

Eco-friendly, stable, and high-performance biochar prepared by a twice-modification scheme: Saccharification of raw materials & thermal air oxidation of biochar - Yundong Liu; Bu Li; Wang Kai Tong; Han Tang; Zhaoli Ping; Wenjuan Wang; Min-tian Gao; Chaomeng Dai; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Management, 2024)

Effects of phosphate-solubilizing fungus Aspergillus flavus AF-LRH1 on promoting phosphorus solubilization, wheat growth and soil heavy metal remediation - Kaili Xu; Xiaoyong Lv; Feixue Yue; Lan Zhang; Ping Wang; Isaac Dennis Amoah; Kuok Ho Daniel Tang; Yiqing Yao; Ronghua Li (Journal of Environmental Chemical Engineering, 2024)

Linear π-conjugated organic cathodes with dispersed redox-active units for high performance aqueous zinc-ion batteries - Ting Xu; Lun Su; Caiyi Ku; Yihao Zhang; Lei Chen; Quan Gou; Siyu Fang; Ping Xue; Mi Tang; Chengliang Wang; Zhengbang Wang (Chemical Engineering Journal, 2024)

Co-insertion chemistry boosting site activity and structural stability of nickel hexacyanoferrate for superior aqueous ammonium ion storage - Ping Luo; Bojie Zhou; Zhen Huang; Wenwei Zhang; Yi Huang; Yixuan Jiang; Dongyao Zhu; Gongtao Yu; Feiyang Chao; Cheng Luo; Shijie Dong; Han Tang (Chemical Engineering Journal, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Neuroprotection by tetramethylpyrazine and its synthesized analogues for central nervous system diseases: a review - Fan Feng; Ding-Qiao Xu; Shi-Jun Yue; Yan-Yan Chen; Yu-Ping Tang (Molecular Biology Reports, 2024)

Multi-omics analysis unravels the underlying mechanisms of the escape response of the common strain black carp (Cyprinus carpio var. baisenensis) - Yuanfeng Xu; Ping Dong; Daniel Yohannes Sewo; Shengyan Su; Jianlin Li; Wenrong Feng; Yu Liao; Yongkai Tang (Aquaculture International, 2024)

Description and genomic characterization of Cohnella caldifontis sp. nov., isolated from hot springs in Yunnan province, south-west China - Ming-Xian Xiang; Cui-Ping Miao; Dian-Yan Zhang; Juan Wang; Yi-Qing Li; Min Yin; ShuKun Tang (Antonie van Leeuwenhoek, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

S-scheme 2D/2D B-doped N-deficient g-C3N4/ZnIn2S4 heterojunction for efficient H2 production intergrated with tertracycline degradation under visible-light illumination - Jiajia Liu; Yaodi Fu; Guoliang Chu; Ke Wen; Lingfang Qiu; Ping Li; Lihong Cheng; Banpeng Cao; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Shuwang Duo (Process Safety and Environmental Protection, 2024)

Comparative transcriptome analysis of Cyperus esculentus and C. rotundus with contrasting oil contents in tubers defines genes and regulatory networks involved in oil accumulation - Xue Bai; Mingyong Tang; Xiaodi Hu; Ping Huang; Yuan Wu; Tao Chen; Huiying He; Zeng-Fu Xu (Plant Science, 2024)

Vegetation restoration enhancing soil carbon sequestration in karst rocky desertification ecosystems: A meta-analysis - Wei Zheng; Xiaobin Guo; Ping Zhou; Li Tang; Jiaxin Lai; Yuting Dai; Wende Yan; Jinshui Wu (Journal of Environmental Management, 2024)

Study of Cerchar abrasive parameters of monomineralic rocks and its application for evaluating cutting efficiency - Xin-Fang Li; Xiao-Ping Zhang; Shao-Hui Tang; Wei-Qiang Xie; Xin-Mei Yang; Quan-Sheng Liu (International Journal of Rock Mechanics and Mining Sciences, 2024)

Spatiotemporal variability of leaf critical senescence age across northern lands and its key drivers - Xingli Xia; Cuihai You; Ruiling Lu; Ning Wei; Chenyu Bian; Ying Du; Erqian Cui; Songbo Tang; Zhiqin Tu; Jiaye Ping; Kun Huang; Jianyang Xia (Global and Planetary Change, 2024)

Texture characterization of 3D printed fibrous whey protein-starch composite emulsion gels as dysphagia food: A comparative study on starch type - Zhiming Wang; Funi Chen; Yuanyuan Deng; Xiaojun Tang; Ping Li; Zhihao Zhao; Mingwei Zhang; Guang Liu (Food Chemistry, 2024)

Acid-assisted pretreatment for sweet elephant grass in choline chloride/glycerol DES: Experimental and mechanism study - Yining Zhang; Weizhen Xie; Weidong Li; Yue Tang; Jiali Wu; Lihui Gan; Ling-Ping Xiao; Xu Zhang; Lu Lin; Xing Tang (Chemical Engineering Journal, 2024)

One-step synthesis of magnetic catalysts containing Mn3O4-Fe3O4 from manganese slag for degradation of enrofloxacin by activation of peroxymonosulfate - Yigui Tang; Zongsu Wei; Chi Wang; Ping Ning; Minghui He; Shuangyou Bao; Xin Sun; Kai Li (Chemical Engineering Journal, 2024)

Regulated charge transfer by cascade dual Z-scheme heterojunction of HCdS@ZnIn2S4-Cobalt porphyrin for efficient photocatalytic solar fuel production - Tengfei Bao; Chenxi Tang; Shuming Li; Ping She; Heng Rao; Jun-sheng Qin (Chemical Engineering Journal, 2024)

PbHfO3-based antiferroelectric materials: Fundamentals, properties, and advanced applications - Dong-Liang Li; Xin-Gui Tang; Shui-Feng Li; Xiao-Bin Guo; Dan Zhang; Qi-Jun Sun; Wen-Hua Li; Zhen-Hua Tang; Yan-Ping Jiang; Qiu-Xiang Liu (Chemical Engineering Journal, 2024)

Role of diffusible signal factor in regulating aerobic granular sludge formation under temperature shocks - Aiqi Tang; Shengqiang Fan; Ping Zhang; Ang Li (Bioresource Technology, 2024)

Optimal extraction of polysaccharides from Stevia rebaudiana roots for protection against hydrogen peroxide-induced oxidative damage in RAW264.7 cells - Zhiyan Tang; Mingrui Zhang; Lan Gao; Yulong Bao; Ping Li; Ming Wang; Taili Shao; Guodong Wang; Chunyan Liu (Natural Product Research, 2024)

Plastic liners as a simple and effective approach to reduce CH4 and N2O emissions from aquaculture ponds - Ping Yang; Zhinan Su; Kam W. Tang; Hong Yang; Lele Tang; Linhai Zhang; Juhua Luo; Jiafang Huang; Minjie Hu; Dongyao Sun; Guanglong Qiu (Agriculture, Ecosystems & Environment, 2024)

Preliminary study on the depositional model in the wave-dominated delta evolution during the Anthropocene: a case study of the Hanjiang River Delta in China - Hongyue Wang; Zhongbo Wang; Yang Wang; Haiyan Tang; Xiaodong Zhang; Xiaofeng Luo; Yongxin Mai; Xuhong Huang; Yilin Zheng; Ping Yin; Zhongping Lai (Acta Oceanologica Sinica, 2024)

Comparative transcriptome analysis reveals the immune defense mechanism of the red swamp crayfish (Procambarus clarkii) in response to Vibrio parahaemolyticus challenge - Xiang Lu; Sheng Tang; Xin Liu; Jun-Jie Jiang; Dan-Dan Bian; Dai-Zhen Zhang; Qiu-Ning Liu; Yong-Xu Cheng; Bo-Ping Tang; Li-Shang Dai (Aquaculture, 2024)

Effect of lead exposure on silkworm midgut: Insights into oxidative gene expression, digestive function, and microbial community structure - Yan-Xia Shi; Dan-Dan Bian; Fan-Xing Chen; Ye Jin; Qi Jiang; Qiu-Ning Liu; Bo-Ping Tang; Li-Shang Dai (Process Safety and Environmental Protection, 2024)

Investigating the thermal stability and calcium resistance of O/W emulsions prepared with glycosylated whey protein hydrolysates modified by different saccharides - Congzhen Shi; Yuanyuan Deng; Zhiming Wang; Yan Zhang; Xiaojun Tang; Zhihao Zhao; Ping Li; Pengfei Zhou; Guang Liu; Mingwei Zhang (Food Chemistry, 2024)

Enhancing the electromagnetic interference shielding performance of composite paper with corrugated paper-like structure - Jiasheng Wei; Ping He; Yantao Yang; Chunxia Tang; Zhu Long; Xiao Chen; Tingzhou Lei; Lei Dai (Chemical Engineering Journal, 2024)

Improved Streamflow Simulation by Assimilating In Situ Soil Moisture in Lumped and Distributed Approaches of a Hydrological Model in a Headwater Catchment - Hongxia Li; Yuanyuan Huang; Yongliang Qi; Yanjia Jiang; Xuan Tang; Elizabeth W. Boyer; Carlos R. Mello; Ping Lan; Li Guo (Water Resources Management, 2024)

Soil acidification enhanced soil carbon sequestration through increased mineral protection - Mengxiao Yu; Ying-Ping Wang; Qi Deng; Jun Jiang; Nannan Cao; Xuli Tang; Deqiang Zhang; Junhua Yan (Plant and Soil, 2024)

Microbial metabolism strengths carbon sequestration and crop yield in upland red soil after long-term ex situ incorporation of straw - Li Tang; Xiaobin Guo; Daoyou Huang; Xiaomeng Wei; Hao Sheng; Pei Luo; Ping Zhou; Wei Gao; Yan Li; Miaomiao Zhang; Wei Zheng; Jinshui Wu (Journal of Soils and Sediments, 2024)

Phylogenetic placements and phenotypic traits of soft rot bacteria isolated from potato (Solanum tuberosum) in Taiwan - Liang-Hsuan Wang; Wen-Chien Tang; Reun-Ping Goh; Jiun-Jie Chan; Yen-Hsin Chiu; Yea-Fang Wu; Shih-Min Su; Dao-Yuan Xue; Chia-Ching Chu (Journal of Plant Pathology, 2024)

Simultaneously inhibit cadmium and arsenic uptake in rice (Oryza sativa L.) by Selenium enhanced iron plaque: Performance and mechanism - Peicheng Huang; Dan Zou; Chunhua Dong; Chongjian Tang; Qingzhu Li; Pengwei Zhao; Ping Zhang; Qi Liao; Zhihui Yang (Chemosphere, 2024)

The analysis of growth performance and expression of growth-related genes in natural gynogenic blunt snout bream muscle derived from the blunt snout bream (Megalobrama amblycephala, ♀) × Chinese perch (Siniperca chuatsi, ♂) - Ping Wu; Wangwang Ji; Ya Zeng; Jie Tang; Chang Wu; Qinbo Qin; Ting Yi; Yi Zhou; Rurong Zhao; Min Tao; Chun Zhang; Chenchen Tang; et al. (Aquaculture, 2024)

MaHOS15 negatively regulates plant immune defense induced by banana fusarium wilt via salicylic acid pathway - Xingchen Jia; Kelin Chen; Yinglong Chen; Yi Tang; Hang Rong; Ping Lin; Yuhao Zhou; Chuqiao Wang; Mingyuan Wang; Jianfu Liu; Qizhi Wang; Hailing Yu (Physiological and Molecular Plant Pathology, 2024)

Linc20486 promotes BmCPV replication through inhibiting the transcription of AGO2 and Dicers - Mengdong Wang; Weiming Tang; Chengyue Wu; Yeping Chen; Hao Li; Ping Wu; Heying Qian; Xijie Guo; Zhendong Zhang (Journal of Invertebrate Pathology, 2024)

Numerical study on regenerative cooling technology with endothermic hydrocarbon fuel: A comprehensive review - Ke Tian; Ping Yang; Zicheng Tang; Zhilong Cheng; Jin Wang; Min Zeng; Qiuwang Wang; Ting Ma (Journal of Cleaner Production, 2024)

Difference between traditional brewing technology and mechanized production technology of jiangxiangxing baijiu: Micro ecology of zaopei, physicochemical factors and volatile composition - Lianqing Wang; Ping Tang; Qing Zhao; Qimuge Shan; Liqin Qin; Dongguang Xiao; Changwen Li; Jun Lu; Xuewu Guo (Food Research International, 2024)

Rapid evaluation of the quality of Smilax glabra Roxb. using QADS based on FT-NIR combined with multiple intelligent algorithms - Geng-zhi Zhan; Xin-yue Guo; Zi-chao Qiu; Lu-yao Cai; Qian Hu; Ye Gao; Shu-wan Tang; Cun-yu Li; Yun-feng Zheng; Guo-ping Peng (Food Chemistry, 2024)

Corrigendum to “Identification and molecular mechanisms of novel antioxidant peptides from fermented broad bean paste: A combined in silico and in vitro study” [Food Chemistry 450 (2024) 139297/ FOCH_FOODCHEM-D-23-08808] - Hongbin Lin; Jianhua Zhao; Yuqing Xie; Jie Tang; Qin Wang; Jie Zhao; Min Xu; Ping Liu (Food Chemistry, 2024)

Natural pyrethrins induce cytotoxicity in SH-SY5Y cells and neurotoxicity in zebrafish embryos (Danio rerio) - Wei-Guo Wang; Shou-Lin Li; Bin Liu; Ning Tang; Cheng Zhang; Xu-Feng Jiang; Li-Ming Tao; Wen-Ping Xu; Yang Zhang (Environmental Research, 2024)

Semi-wet synthesis of high-performance Li1.6Mn1.6O4 for selective lithium extraction from Salt Lakes Brine - Lu-Ri Bao; Wei-Ping Tang; Shu-Ying Sun (Desalination, 2024)

Alginate/multi-wall carbon nanotube fiber-based moist-electric generator with enhanced performance by constructing radial heterogenous structure - Rui Zhang; Xinye Li; Wenshuo Du; Taofu Zhao; Ping Tang; Xiaozhu Ju; Hai Wang; Yuezhen Bin (Chemical Engineering Journal, 2024)

Fe-reinforced silkworm silk with superstrong mechanical properties for mass production - Qingsong Liu; Xin Wang; Yifan Zhou; Yi Li; Zhangchuan Peng; Zhangchen Tang; Xiangyu Cai; Xinyu Fan; Xin Tang; Xiaoyin Tan; Xiaoqian Xie; Xinning Li; et al. (Chemical Engineering Journal, 2024)

Present and future climate of the Yangtze River Delta region: analysis of the CMIP6 HighResMIP simulations - Ping Yi; Guoxing Chen; Xu Tang (Theoretical and Applied Climatology, 2024)

In-situ observations of wave- and current-supported fluid mud dynamics on a hyperturbid macrotidal mudflat - Mingliang Li; Dezhi Chen; Hao Wu; Jieping Tang; Yiyi Zhang; Feng Luo; Fugang Gou; Xulong Gong; Ya Ping Wang (Frontiers in Marine Science, 2024)
Wave- and current-supported fluid mud on gently sloped continental shelves represents a type of sediment gravity flow capable of rapidly transporting substantial sediment over short periods, significantly contributing to coastal geomorphic evolution. To investigate the dynamics of intertidal fluid mud events, in-situ observations were conducted from May 9 to May 18, 2017, using a seabed tripod system at the lower intertidal flat of the central Jiangsu coast, China. Fluid mud was observed following a medium wind-wave event, with a maximum significant wave height of 0.42 m. The liquefied seabed, loosened by liquefaction, facilitated bed erosion and sediment resuspension. Fluid mud layers, with mean suspended sediment concentrations (SSCs) exceeding 10 g/L, periodically formed during high slack tide, early flood, and late ebb phases. These layers varied in thickness from 4 cm to 20 cm and exhibited strong stratification caused by suspended sediment. Fluid mud disappeared when the bottom turbulence kinetic energy exceeded a threshold of 0.00045 m²/s² due to an increase in current velocity. The downslope movement of intertidal fluid mud was estimated using a theoretical buoyancy-friction model and validated by observed offshore-directed velocity jets at 0.1 m above the seabed during high slack tide phases. Additionally, onshore winds favored fluid mud formation during early flood phases, while offshore winds favored it during late ebb phases. These observations suggest that fluid mud can form on intertidal flats under conditions where tidal flows and winds align, contributing to a deeper understanding of the formation mechanisms of shallow gravity flows and the improvement of sediment transport models.

Drivers of East Asian summer monsoon variability: Global oceans and the Tibetan Plateau - Anmin Duan; Guoxiong Wu; Bin Wang; Andrew G. Turner; Jun Hu; Wenting Hu; Ping Zhang; Die Hu; Yuheng Tang (Science Bulletin, 2024)

Evaluating the effects of laver cultivation on tidal flat erosion: Toward sustainable environmental practices - Dezhi Chen; Gaocong Li; Jieping Tang; Lintao Zhao; Ya Ping Wang; Chao Gao (Journal of Environmental Management, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Identification and molecular mechanisms of novel antioxidant peptides from fermented broad bean paste: A combined in silico and in vitro study - Hongbin Lin; Jianhua Zhao; Yuqing Xie; Jie Tang; Qin Wang; Jie Zhao; Min Xu; Ping Liu (Food Chemistry, 2024)

Integration of a biocompatible metal-phenolic network and fluorescence microspheres as labels for sensitive and stable detection of carbendazim with a lateral flow immunoassay - Zongyou Chen; Yanyan Tang; Ping Guo; Wei Zhang; Juan Peng; Yonghua Xiong; Bingfeng Ma; Weihua Lai (Food Chemistry, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Simplified Calculation of Earthquake Energy Transfer of Different Pipe Supports Inside Utility Tunnel at Horizontal Non-Homogeneous Field - De-long Huang; Hang Cen; Jin Wang; Hui-yue Wang; Qiang Liu; Zhong-ling Zong; Ai-ping Tang; Song-ling Xue (Geotechnical and Geological Engineering, 2024)

Transformation of As and Cd associated with Fe–Mn-modified biochar during simultaneous remediation on the contaminated soil - Gai Zeng; Yang Ping; Hao Xu; Zhihui Yang; Chongjian Tang; Weichun Yang; Mengying Si; Chukwuma Arinzechi; Lin Liu; Fangshu He; Xiaoming Zhang; Qi Liao (Environmental Science and Pollution Research, 2024)

Inhibition of flowering by gibberellins in the woody plant Jatropha curcas is restored by overexpression of JcFT - Ping Huang; Jie Yang; Jiapeng Ke; Li Cai; Yingxiong Hu; Jun Ni; Chaoqiong Li; Zeng-Fu Xu; Mingyong Tang (Plant Science, 2024)

Engineering of molecularly imprinted cavity within 3D covalent organic frameworks: An innovation for enhanced extraction and removal of microcystins - Yu-Hong Tang; Tian-Tian Ma; Xu-Qin Ran; Yukun Yang; Hai-Long Qian; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

PANI/GO and Sm co-modified Ti/PbO2 dimensionally stable anode for highly efficient amoxicillin degradation: Performance assessment, impact parameters and degradation mechanism - Zeyi Wang; Luyao Zhang; Rong Su; Lu Yang; Feng Xiao; Lichuan Chen; Ping He; Dingming Yang; Yali Zeng; Yun Zhou; Ying Wan; Bin Tang (Journal of Environmental Management, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Application of polyphenolic compound-based HPLC fingerprint in Chinese golden camellias (Camellia sect. Chrysantha) - Miaozi Gao; Junrong Tang; Jia Deng; Changwei Cao; Yingjun Zhang; Shengfeng Chai; Ping Zhao; Huan Kan; Yun Liu (Food Control, 2024)

Molecular characterization, expression analysis and function identification of Pf_IL-12p35, Pf_IL-23p19 and Pf_IL-12p40 genes in yellow catfish (Pelteobagrus fulvidraco) - Xin-Xin Jiang; Zi-Rui Tang; Zhang-Ping Li; Gui-Rong Zhang; Xu Zhou; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2024)

Study of the dynamic interactions between helix-stiffened cement mixing piles and soft soil under oblique incidence of SV waves in arbitrary space - Hang Cen; Zhong-ling Zong; De-long Huang; Hui-yue Wang; Xiao-xuan Zhuang; Zi-yuan Huang; Ai-ping Tang (Computers and Geotechnics, 2024)

Application of 210Pbex dating to establishing chronologies of modern terrestrial sedimentary deposits in estuarine deltas - Jinlin Li; Xinbao Zhang; Xiubin He; Jie Wei; Yong Yuan; Runchuan Zhang; Shengjun Wu; Yuhai Bao; Qiang Tang; Ping Huang (CATENA, 2024)

Variable responses of mineral-bound soil organic carbon to land cover change in southern China’s coastal wetlands - Ping Yang; Guanpeng Chen; Linhai Zhang; Chuan Tong; Hong Yang; Wanyi Zhu; Dongyao Sun; Lishan Tan; Yan Hong; Kam W. Tang (CATENA, 2024)

Unveiling the molecular mechanisms of size-dependent effect of polystyrene micro/nano-plastics on Chlamydomonas reinhardtii through proteomic profiling - Xiaoxue Li; Zheng Chu; Chenran Feng; Ping Song; Tong Yang; Lirun Zhou; Xin Zhao; Xin Chai; Jiale Xing; Sa Chen; Junzhe Zhang; Jigang Wang; et al. (Chemosphere, 2024)

Physicochemical characteristics of grease-trap wastewater with different potential mechanisms of FOG solid formation, separation, and accumulation inside grease traps - Ling Ying Tang; Ngie Hing Wong; Thion Am Chieng; Alex Kwong Jun Kiu; Chung Siung Choo; Yali Li; Chin Ping Tan; Abu Zahrim Yaser; Deni Shidqi Khaerudini; Gui Hua Chen; Jaka Sunarso (Water Research, 2024)

Residues of chlorpyrifos in the environment induce resistance in Aedes albopictus by affecting its olfactory system and neurotoxicity - Yanrong Chen; Chen Zhang; Wen Li; Ruoyun Lan; Rufei Chen; Jingchao Hu; Chenyu Yang; Ping Wang; Bin Tang; Shigui Wang (Science of The Total Environment, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

Fault detection of complicated processes based on an enhanced transformer network with graph attention mechanism - Yuping Cao; Xiaoguang Tang; Xiaogang Deng; Ping Wang (Process Safety and Environmental Protection, 2024)

Minor ergosteroids and a 19-nor labdane-type diterpenoid with anti-inflammatory effects from Ganoderma lucidum - Dan Cai; Yun-Yun Liu; Xin-Ping Tang; Mei Zhang; Yong-Xian Cheng (Phytochemistry, 2024)

Effect of the pore parameters of the perforated baffle on the control of liquid sloshing - Yuying Tang; Ya-dong Liu; Wei Zhang; Minmin Zheng; Yan-ping He (Ocean Engineering, 2024)

Soft sensor enabled real-time chemical dosing control systems for wastewater treatment: From hybrid model to full-scale application - Hualei Ding; Mingyue Tang; Qing Huang; Ping Yang; Zhen Liu; Xuejun Bi; Abhilash Nair; Xiaodong Wang (Journal of Water Process Engineering, 2024)

Spatiotemporal distributions of dissolved N2O concentration, diffusive N2O flux and relevant functional genes along a coastal creek in southeastern China - Ping Yang; Yongxin Lin; Hong Yang; Chuan Tong; Linhai Zhang; Derrick Y.F. Lai; Dongyao Sun; Lishan Tan; Lele Tang; Yan Hong; Kam W. Tang (Journal of Hydrology, 2024)

High-precision microcline 40Ar/39Ar dating by combined techniques - Xiu-Juan Bai; Yi-Long Li; Rong-Guo Hu; Xiao Liu; Bin Tang; Xiang-Ping Gu; Hua-Ning Qiu (Chemical Geology, 2024)

Recombinase-aided amplification coupled with lateral flow dipstick for efficient and accurate detection of Bombyx mori nucleopolyhedrovirus - Runpeng Wang; Sheng Xu; Erjun Wei; Ping He; Yiling Zhang; Qiang Wang; Xudong Tang; Zhongyuan Shen (Folia Microbiologica, 2024)

Design, optimization, and evaluation for a long-time-released transdermal microneedle delivery system containing estradiol - XiaoFei Tang; Huaiying Qin; XiaoYun Zhang; Haiyun Yang; Jianhua Yang; Ping Chen; Yinli Jin; Lu Yang (Drug Delivery and Translational Research, 2024)

Cell-Cycle-related Protein Centromere Protein F Deficiency Inhibits Cervical Cancer Cell Growth by Inducing Ferroptosis Via Nrf2 Inactivation - Xin hui Tang; Tian nan Zhao; Li Guo; Xin yue Liu; Wei na Zhang; Ping Zhang (Cell Biochemistry and Biophysics, 2024)
Cervical cancer (CC) is one of the severe cancers that pose a threat to women’s health and result in death. CENPF, the centromere protein F, plays a crucial role in mitosis by regulating numerous cellular processes, such as chromosome segregation during mitosis. According to bioinformatics research, CENPF serves as a master regulator that is upregulated and activated in cervical cancer. Nevertheless, the precise biological mechanism that CENPF operates in CC remains unclear. The aim of this study was to analyze the function of CENPF on cervical cancer and its mechanism. We conducted immunohistochemistry and western blot analysis to examine the expression levels of CENPF in both cervical cancer tissues and cells. To explore the hidden biological function of CENPF in cell lines derived from CC, we applied lentivirus transfection to reduce CENPF manifestation. CENPF’s main role is to regulate ferroptosis which was assessed by analyzing Reactive Oxygen Species (ROS), malonaldehyde (MDA), etc. The vitro findings were further validated through a subcutaneous tumorigenic nude mouse model. Our research finding indicates that there is an apparent upregulation of CENPF in not merely tumor tissues but also cell lines in the carcinomas of the cervix. In vitro and vivo experimental investigations have demonstrated that the suppression of CENPF can impede cellular multiplication, migration, and invasion while inducing ferroptosis. The ferroptosis induced by CENPF inhibition in cervical cancer cell lines is likely mediated through the Nrf2/HO-1 pathway. The data herein come up with the opinion that CENPF may have a crucial role in influencing anti-cervical cancer effects by inducing ferroptosis via the triggering of the Nrf2/HO-1 signaling pathway.

Streptomyces camelliae sp. nov., isolated from rhizosphere soil of Camellia oleifera Abel - Zheng Yaxi; Deng Aihua; Xu Xiaoxiao; Li Chenxi; Peng Yi; Tang Ting; Liu Jin; Ming Yiru; Mo Ping (Archives of Microbiology, 2024)

A rare case of near complete recovery in an apneic coma patient with brainstem encephalitis for 14 days and a 9-year follow-up - Weiyun Zhang; Ping Nie; Jing Zhou; Zhaohui Zhang; Jinrong Tang (Acta Neurologica Belgica, 2024)

Trace element compositions of pyrite and stibnite: implications for the genesis of antimony mineralization in the Yangla Cu skarn deposit, Northwestern Yunnan, China - Ping Pan; Xinfu Wang; Bo Li; Guo Tang; Zuopeng Xiang (Acta Geochimica, 2024)

Pyricularia pennisetigena as leaf blast disease-causing pathogen in king grass (Pennisetum sinese) and its assessment of the pathogenic risk - Yinglong Liu; Tengfei Gui; Ayesha Ahmed; Shahzad Munir; Pengfei He; Pengbo He; Yixin Wu; Ping Tang; Qiong Luo; Yueqiu He (Journal of Plant Pathology, 2024)

Energy harvesting from acid mine drainage using a highly proton/ion-selective thin polyamide film - Shenghua Zhou; Ying Mei; Wulin Yang; Chenxiao Jiang; Hao Guo; Shien-Ping Feng; Chuyang Y. Tang (Water Research, 2024)

Systemic evaluation of novel acaricide hexythiazox for bioactivity improvement and risk reduction at the enantiomer level - Ping Zhang; Furong Yang; Lulu Ran; Cancan Yang; Can Tang; Xiaojiang Ke; Juanni Chen; Wei Xiao; Lin He; Zhifeng Xu (Science of The Total Environment, 2024)

Artificial microbial consortia engineering: Intensify nitrogen removal from mature landfill leachate by simultaneous nitrification and denitrification - Xia Ke; Yi-Xin Li; Ting-Ting Guo; Zu-Lian Liao; Su-Qin Tang; Yi-Cheng Zhang; Shi-Peng Zhou; Ya-Ping Xue; Yu-Guo Zheng (Journal of Water Process Engineering, 2024)

Investigation into the potential mechanism of Bacillus amyloliquefaciens in the fermentation of broad bean paste by metabolomics and transcriptomics - Hongbin Lin; Shiqi Liao; Zesu Zhou; Ziting Yan; Jianhua Zhao; Yue Xiang; Min Xu; Jie Zhao; Ping Liu; Wengwu Ding; Yu Rao; Jie Tang (Food Research International, 2024)

LncRNA NR_030777 promotes mitophagy by targeting CDK1-related mitochondrial fission and ATG12 to attenuate paraquat-induced Parkinson's disease - Nengzhou Chen; Hong Hu; Jianping Tang; Fuli Zheng; Zhenkun Guo; Xinpei Lin; Michael Aschner; Wenya Shao; Guangxia Yu; Ping Cai; Wei-Chun Chou; Siying Wu; et al. (Environmental Pollution, 2024)

Biomimetically ordered ultralong hydroxyapatite nanowires-based hierarchical hydrogel scaffold with osteoimmunomodulatory and osteogenesis abilities for augmenting bone regeneration - Xiangwu Geng; Yifan Tang; Bo Yuan; Yuya Dai; Han-Ping Yu; Zhi-Chao Xiong; Ying-Jie Zhu; Xiongsheng Chen (Chemical Engineering Journal, 2024)

Valence state regulation of Terbium in all-inorganic amorphous solid for magnetic field sensing - Xudong Zhao; Jiadong Li; Weiwei Li; Ping Lu; Xianghua Zhang; Xiujian Zhao; Yinsheng Xu; Mengling Xia; Jiang Tang (Chemical Engineering Journal, 2024)

Innovative probiotic Escherichia coli nissle 1917-derived outer membrane vesicles coupled microspheres demonstrate anti-inflammatory and barrier-enhancing properties in colitis - Lu Han; Xu-Wei Liu; Wei-Xiong Li; Tao Zang; Zhi-Peng Li; Yao Deng; Lu-Lu Tan; Dun-Sheng Liang; Xiao-Jing Zhang; Xiao-Fan Shen; Sheng-Qiu Tang; Xiao-Ping Liao; et al. (Chemical Engineering Journal, 2024)

Interspecific occupancy-abundance relationship of benthic diatoms changes seasonally with attachment mode in a tropical river - Lin Tan; Yuting Liu; Muqi Shen; Guifeng Wei; Linglin Wan; Quehui Tang; Bo-Ping Han (Hydrobiologia, 2024)

Experimental study on the influence mechanism of soil additives on scraper wear during EPB-TBM tunnelling in abrasive sandy ground - Shao-Hui Tang; Xiao-Ping Zhang; Quan-Sheng Liu; Wei-Qiang Xie; Jian Wu; Hao-Jie Wang; Xin-Fang Li (Bulletin of Engineering Geology and the Environment, 2024)

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

Ginsenoside Rg1 Alleviates Sepsis-Induced Acute Lung Injury by Reducing FBXO3 Stability in an m6A-Dependent Manner to Activate PGC-1α/Nrf2 Signaling Pathway - Rong Liu; Qiang Wang; Yao Li; Ruixue Wan; Ping Yang; Dexing Yang; Jiefu Tang; Jiafei Lu (The AAPS Journal, 2024)

Unraveling the aroma profiling of Baijiu: Sensory characteristics of aroma compounds, analytical approaches, key odor-active compounds in different Baijiu, and their synthesis mechanisms - Lianqing Wang; Ping Tang; Pengjie Zhang; Jun Lu; Yefu Chen; Dongguang Xiao; Xuewu Guo (Trends in Food Science & Technology, 2024)

The influence of soil factors on protist community dynamics during plant succession in subalpine natural and planted forests - Kai Fang; Na Tang; Jia Liu; Xiao-Ying Zhang; He-Liang He; Wen-Qiang Zhao; Yong-Ping Kou; Qing Liu (Soil Biology and Biochemistry, 2024)

Associations between community green view index and fine particulate matter from Airboxes - Jia-Hong Tang; Ying-Jhen Huang; Ping-Hsien Lee; Yu-Ting Lee; Yu-Chun Wang; Ta-Chien Chan (Science of The Total Environment, 2024)

Occurrence, distribution, and risk assessment of antibiotics in a typical aquaculture area around the Dongzhai Harbor mangrove forest on Hainan Island - Tuan-Tuan Wang; Shuai Shao; Shi-Di Fan; Wang-Qing Tang; Jiang-Wei Miao; Sai Wang; Xiao-Cong Cao; Chuan Liu; Guang-Guo Ying; Zhong-Bing Chen; Hai-Long Zhou; Xiao-Ping Diao; et al. (Science of The Total Environment, 2024)

Amorphous FeOOH shell decorated Bi2O4 for the boosted photocatalytic degradation of tetracycline under visible irradiation - Yuming Sun; Yubin Tang; Fangyan Chen; Ping Huang; Wenqian Sun; Yanhua Song (Journal of Environmental Chemical Engineering, 2024)

Emission and spatial variation characteristics of odorous pollutants in the aerobic tank of an underground wastewater treatment plant (UWWTP) in southern China - Xiang Xiao; Ke Kuang; Zijun Tang; Xia Yang; Haiwen Wu; Yunqing Wang; Ping Fang (Environmental Pollution, 2024)

Visual measurement of lateral relative displacement of wheel-rail of high-speed train under earthquake - Shujun Fang; Linjie Yang; Jianyuan Tang; Wei Guo; Chen Zeng; Ping Shao (Engineering Structures, 2024)

A novel Zr-P-modified nanomagnetic herbal biochar immobilized Cd and Pb in water and soil and enhanced the relative abundance of metal-resistant bacteria: Biogeochemical and spectroscopic investigations to identify the governing factors and potential mechanisms - Yueru Fang; Ping Wang; Lan Zhang; Han Zhang; Ran Xiao; Yuan Luo; Kuok Ho Daniel Tang; Ronghua Li; Hamada Abdelrahman; Zengqiang Zhang; Jörg Rinklebe; Sang Soo Lee; et al. (Chemical Engineering Journal, 2024)

Experimental and computational investigation of chaotic advection mixing in laminar rectangular stirred tanks - Anqi Li; Yuan Yao; Xiaoyu Tang; Peiqiao Liu; Qian Zhang; Qian Li; Ping Li; Feng Zhang; Yundong Wang; Changyuan Tao; Zuohua Liu (Chemical Engineering Journal, 2024)

Host-guest synergistic hydrogen bond triggered signal amplification for visualizing the plant hormone salicylic acid - A-Ling Tang; Li-Long Zhang; Shuai Tan; Ping Yang; Wei Niu; Mei-Hong Ge; Lin-Lin Yang; Pei-Yi Wang; Li-Wei Liu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2024)

Intensifying the simultaneous removal of nitrogen and phosphorus of an integrated aerobic granular sludge-membrane bioreactor by Acinetobacter junii - Weifeng Liang; Biao Yang; Liying Bin; Yadong Hu; Depeng Fan; Weirui Chen; Ping Li; Bing Tang (Bioresource Technology, 2024)

Inter-model spread in East Asian Summer Monsoon onset timing linked to the tropical Pacific and Indian oceans' mean state in CMIP6 models - Die Hu; Anmin Duan; Yuheng Tang; Bin Tang; Ping Zhang (Atmospheric Research, 2024)

A mapping method for emission inventory and its application in air quality modeling - Jin Fan; Mengying Shen; Tingyu Yan; Kaicheng Zhang; Tongge Zhang; Chen Gong; Xinyun Tian; Yanan Shang; Xianyu Yang; Ping Shao; Wei Tang; Maoshan Li; et al. (Atmospheric Pollution Research, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Latitudinal responses of wetland soil nitrogen pools to plant invasion and subsequent aquaculture reclamation along the southeastern coast of China - Lishan Tan; Ping Yang; Xiao Lin; Yongxin Lin; Linhai Zhang; Chuan Tong; Yan Hong; Derrick Y.F. Lai; Kam W. Tang (Agriculture, Ecosystems & Environment, 2024)

Unveiling grain production patterns in China (2005–2020) towards targeted sustainable intensification - Bingwen Qiu; Zeyu Jian; Peng Yang; Zhenghong Tang; Xiaolin Zhu; Mingjie Duan; Qiangyi Yu; Xuehong Chen; Miao Zhang; Ping Tu; Weiming Xu; Zhiyuan Zhao (Agricultural Systems, 2024)

A novel safer CD19CAR with shRNA interference of IFN-γ can reduce multiple cytokine levels without significantly compromising its killing efficacy - Ping Zhang; Peiting Ying; Hongzhe Li; Ning Zhao; Rongrong Liu; Sisi Li; Weiqun Xu; Yang Tang; Yongmin Tang (Apoptosis, 2024)

Evaluating the stabilities of common power-law models for describing particle size distributions across the continental shelf of the northern South China Sea - Wendi Zheng; Shilin Tang; Ping Shi; Wenxi Cao; Wen Zhou (Marine Geology, 2024)

Quantitative characterization of resident’ exposure to typical semi-volatile organic compounds (SVOCs) around a non-ferrous metal smelting plant - Mengmeng Wang; Yiyi Li; Yinyi Lv; Jian Tang; Pengkun Wei; Ping Lu; Leicheng Zhao; Guiying Li; Zhiguo Cao; Taicheng An (Journal of Hazardous Materials, 2024)

Potential of perennial sorghum for biogas production: Pretreatment with yeast-contained inoculants during anaerobic storage - Xiaolong Tang; Chaosheng Liao; Shufeng Zhou; Cheng Chen; Lin Li; Guangrou Lu; Xiaokang Huang; Mingjie Zhang; Chao Chen; Ping Li (Fuel, 2024)

Fibrous whey protein mediated homogeneous and soft-textured emulsion gels for elderly: Enhancement of bioaccessibility for curcumin - Zhiming Wang; Yuanyuan Deng; Yan Zhang; Xiaojun Tang; Pengfei Zhou; Ping Li; Zhihao Zhao; Zhangying Wang; Guang Liu; Mingwei Zhang (Food Chemistry, 2024)

A review on the antibiotic florfenicol: Occurrence, environmental fate, effects, and health risks - Xingying Guo; Haibo Chen; Yongqi Tong; Xintong Wu; Can Tang; Xian Qin; Jiahua Guo; Ping Li; Zhen Wang; Wenhua Liu; Jiezhang Mo (Environmental Research, 2024)

Low-cost and completely non-fused small-molecule acceptors based on tetrathiophene featuring 3,5-dialkylthiophene side chain enable efficient organic solar cells - Minghui Cao; Xiaoying Zhang; Xuejiao Tang; Shixin Meng; Jing Cao; Zhi-Guo Zhang; Chao Weng; Ping Shen (Chemical Engineering Journal, 2024)

Experimental study on strength characteristics and constitutive behavior of frozen chloride silty clay - Yu Tang; Ping Yang; Lin Li; Zhiliang Zhou (Cold Regions Science and Technology, 2024)

Shear Modulus of Weathered Red Sandstone Coarse-Grained Soil under Drying–Wetting Cycles - Xiang Tang; Chang-ping Wen (Geotechnical and Geological Engineering, 2024)

Significant inter-annual fluctuation in CO2 and CH4 diffusive fluxes from subtropical aquaculture ponds: Implications for climate change and carbon emission evaluations - Ping Yang; Linhai Zhang; Yongxin Lin; Hong Yang; Derrick Y.F. Lai; Chuan Tong; Yifei Zhang; Lishan Tan; Guanghui Zhao; Kam W. Tang (Water Research, 2024)

Comparison of four pre-oxidants coupled powdered activated carbon adsorption for odor compounds and algae removal: Kinetics, process optimization, and formation of disinfection byproducts - Heng-Xuan Zhao; Shuang Zhang; Tian-Yang Zhang; Yi-Ping Zhu; Ren-Jie Pan; Meng-Yuan Xu; Zheng-Xiong Zheng; Chen-Yan Hu; Yu-Lin Tang; Bin Xu (Science of The Total Environment, 2024)

Iridoid and lignan glycosides from Lancea tibetica - Yi Zhu; Junlin Wang; Lu Tang; Yuxin Shang; Weiyi Zhao; Wei Zhang; Ping Hai; Yongbiao Zheng; Wenbo Li; Yanfang Su (Phytochemistry Letters, 2024)

Revealing the formation mechanisms of key flavors in fermented broad bean paste - Yue Xiang; Binbin Zhou; Chunyan Jiang; Zhirui Tang; Ping Liu; Wenwu Ding; Hongbin Lin; Jie Tang (Food Research International, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

Deciphering the role of hydraulic retention time (HRT) in integrated fixed-film activated sludge (IFAS) system under aniline stress: Effects on microbial succession and communication - Nan-ping Wu; Bin Tan; Meng Li; Naif Abdullah Al-Dhabi; Bing Lin; Qi He; Hao-nan Shen; Jia-jing Cheng; Wangwang Tang; Qian Zhang (Chemical Engineering Journal, 2024)

Fluorogenic RNA aptamer output sensors via transcription activated by recombinase polymerase amplification for nucleic acid testing - Jiajie Liang; Xin Liu; Wei Xiao; Peijun Teng; Ping Guan; Wanli Liang; Liangshan Hu; Guanbo He; Haorong He; Gan Li; Siyi Zou; Cheng Lu; et al. (Chemical Engineering Journal, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

Water storage changes (2003–2020) in the Ordos Basin, China, explained by GRACE data and interpretable deep learning - Ziming Hu; Shinan Tang; Shaoxing Mo; Xiaoqing Shi; Xin Yin; Yuanyuan Sun; Xiaomin Liu; Limin Duan; Ping Miao; Tingxi Liu; Jichun Wu (Hydrogeology Journal, 2024)

Identification and Analysis of DNA Methylation Inflammation-Related Key Genes in Intracerebral Hemorrhage - Sanpeng Xu; Qiong Wu; Zhe Tang; Ping Li (Biochemical Genetics, 2024)

Removal and recovery of phosphate by modified oyster shell and its fertilizer application - Ping Li; Jianxu Li; Weirui Chen; Xiujuan Guan; Bing Tang; Liying Bin; Shaosong Huang (Science of The Total Environment, 2024)

Mass-immigration shapes the antibiotic resistome of wastewater treatment plants - Lanping Zhang; Bob Adyari; Liyuan Hou; Xiaoyong Yang; Mahmoud Gad; Yuwen Wang; Cong Ma; Qian Sun; Qiang Tang; Yifeng Zhang; Chang-Ping Yu; Anyi Hu (Science of The Total Environment, 2024)

Reciprocal transplant experiment reveals multiple factors influencing changes in coral microbial communities across climate zones - Ya-Fan Chan; Yu-Hsiang Chen; Sheng-Ping Yu; Hsing-Ju Chen; Yoko Nozawa; Sen-Lin Tang (Science of The Total Environment, 2024)

FAM21 interacts with Ku to promote the localization of WASH to DNA double strand break sites - Tao Wang; Ai-Xue Zheng; Ping Li; Tuo Tang; Lu-Ping Zhang; Yu Hong; Xian Hong; Zhi-Hui Deng (DNA Repair, 2024)

C vacancy and F decorated g-C3N4 for boosting photocatalytic ozonation of sodium p-perfluorinated nonoxybenzenesulfonate - Weirui Chen; Siyou Fu; Xukai Li; Jing Wang; Xunan Ning; Liying Bin; Ping Li; Bing Tang; Laisheng Li (Chemical Engineering Journal, 2024)

Achieving ultrahigh energy storage density and efficiency above 90% via reducing defect concentrations for AgNbO3-based multilayer capacitors - Dekai Shi; Dong Liu; Lei Zhao; Qi Wang; Ting Tang; Xinyue Long; Liqin Yan; Bo-Ping Zhang; He Qi; Li-Feng Zhu (Chemical Engineering Journal, 2024)

Effects of land-use patterns on seasonal water quality at multiple spatial scales in the Jialing River, Chongqing, China - Yuan-Bo Wang; Muhammad Junaid; Jiao-Yun Deng; Qi-Ping Tang; Lin Luo; Zhuo-Yuan Xie; De-Sheng Pei (CATENA, 2024)

Adipose Tissue Exosome circ_sxc Mediates the Modulatory of Adiposomes on Brain Aging by Inhibiting Brain dme-miR-87-3p - Qiufang Li; Lingxiao Wang; Chao Tang; Xiaoya Wang; Zhengwen Yu; Xu Ping; Meng Ding; Lan Zheng (Molecular Neurobiology, 2024)

Fluid mud induced by periodic tidal advection and fine-grained sediment settling in the Yangtze estuary - Hao Wu; Jieping Tang; Weihua Li; Fei Xing; Haifei Yang; Fan Zhang; Ya Ping Wang (Frontiers in Marine Science, 2023)
This study presents in-situ observations of fluid mud in the Yangtze Estuary via a bottom tripod. Six occurrences of periodic fluid muds (F1-F6) were observed at high slack water, with suspended sediment concentration (SSC) exceeding 10 kg/m 3 . The thickness of the fluid mud varied across the six occurrences, reaching a maximum of 0.32m. Notably, temperature and salinity anomalies were observed within the fluid mud. The formation of fluid mud was found to be influenced by turbulence, with turbulence kinetic energy (TKE) below 5×10 -4 m 2 /s 2 favoring settling as the primary cause of formation. The critical shear stress ( τ cw ) for fluid mud formation was estimated to be approximately 0.09 Pa. The formation of fluid muds during early tidal cycles was attributed to liquefaction and bed erosion resulting from strong waves. However, in most cases, the wave energy was insufficient for erosion, suggesting that advection played a role in sediment supply during the subsequent tide cycles. The increased cross-channel current velocity during flood facilitated the lateral transport of a significant amount of eroded sediment from shallow water into the channel. Due to its short duration, the fluid mud layer was entrained by the current before consolidation. Enhanced turbulence led to the breakdown of fluid mud at the early ebb. The critical τ cw for fluid mud breakdown depended on the density and duration of the fluid mud, with a maximum value of up to 0.70 Pa. The absence of the fluid mud layer during low slack water and neap tide was associated with a reduction in advection and tidal pumping, disrupting the original sediment balance between supply and demand. These data provide valuable insights into the formation and breakdown of fluid mud, contributing to estuarine hydrodynamic modeling studies and enhancing the understanding of estuary dynamics.

Community pattern of potential phenanthrene (PHE) degrading bacteria in PHE contaminated soil revealed by 13C-DNA stable isotope probing - Xiufeng Tang; Ye Li; Ruihe Jin; Guoyu Yin; Lijun Hou; Min Liu; Feng Ju; Ping Han (Chemosphere, 2023)

B4C/Ce co-modified Ti/PbO2 dimensionally stable anode: Facile one-step electrodeposition preparation and highly efficient electrocatalytic degradation of tetracycline - Zeyi Wang; Rong Su; Maojie Zhao; Luyao Zhang; Lu Yang; Feng Xiao; Weishan Tang; Lichuan Chen; Ping He; Dingming Yang (Chemosphere, 2023)

Formation and identification of artificial gynogenetic mandarin fish (Siniperca chuatsi) induced by inactivated sperm of largemouth bass (Micropterus salmoides) - Ping Wu; Ya Zeng; Qinbo Qin; Wangwang Ji; Chang Wu; Yi Zhou; Rurong Zhao; Min Tao; Chun Zhang; Chenchen Tang; Shaojun Liu (Aquaculture, 2023)

Abundance, diversity and physiological preferences of comammox Nitrospira in urban groundwater - Xiufeng Tang; Ye Li; Min Liu; Lijun Hou; Ping Han (Science of The Total Environment, 2023)

Identification and characterization of a novel Iflavirus in a stored-product psocid, Liposcelis bostrychophila (Psocodea: Liposcelididae) - Peng-Yu Guo; Dan-Dan Wei; Hua-Yue Feng; Xin-Ping Tang; Yu-Ang Chen; Yi Li; Jin-Jun Wang (Journal of Stored Products Research, 2023)

The significantly boosted photodegradation of tetracycline over a novel hierarchical 0D/3D S-scheme heterojunction ZnSnO3/CdIn2S4 - Wenqian Sun; Fangyan Chen; Ping Huang; Yuming Sun; Yanhua Song; Yubin Tang (Journal of Environmental Chemical Engineering, 2023)

An acidic heteropolysaccharide rich in galactose and arabinose derived from ginger: Structure and dynamics - Xiao-tong Lin; Bo-xian Xiao; Jun-ping Liu; Ming-yuan Cao; Zhi-ping Yang; Li-yan Zhao; Gui-tang Chen (Food Bioscience, 2023)

Hydrodynamic response to bathymetric changes in Tampa Bay, Florida - Jing Chen; Yonggang Liu; Robert H. Weisberg; Steven A. Murawski; Sherryl Gilbert; David F. Naar; Lianyuan Zheng; Matthew Hommeyer; Catherine Dietrick; Mark E. Luther; Cheryl Hapke; Edward Myers; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

A Case of Kerion Complicating with Acute Generalized Exanthematous Pustular Dermatophytid (AGEPD) - Li Tang; Hongjian Shi; Ping Zhan; Zhihua Li; Qing Jiang; Xiaobing Wang; Weijun Liu (Mycopathologia, 2023)

The analyses of the complete mitochondrial genomes of three crabs revealed novel gene rearrangements and phylogenetic relationships of Brachyura - Zhao-Zhe Xin; Sheng Tang; Xiang Lu; Hua-Bin Zhang; Dai-Zhen Zhang; Gang Wang; Bo-Ping Tang; Qiu-Ning Liu (Molecular Biology Reports, 2023)

Do submerged macrophytes facilitate the development of large crustacean zooplankton in tropical shallow lakes? - Xing Rao; Jichong Lu; Ping Zhong; Xiufeng Zhang; Yali Tang; Jinlei Yu; Hu He; Erik Jeppesen; Zhengwen Liu (Hydrobiologia, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Exploratory study on the efficacy of bortezomib combining mitoxantrone or CD22-CAR T therapy targeting CD19-negative relapse after CD19-CAR T cell therapy with a simpler cell-line-based model - Diandian Ba; Hongzhe Li; Rongrong Liu; Ping Zhang; Yongmin Tang (Apoptosis, 2023)

Effects of Seasonal Photoperiod on Growth, Lipid Metabolism, and Antioxidant Response in the Huanghe Carp (Cyprinus carpio haematopterus) - Wenqian Wang; Shengyan Su; Ping Dong; Wenrong Feng; Jianlin Li; Chengfeng Zhang; Yongkai Tang (Fishes, 2023)
Photoperiod is one of the most important environmental cues for organisms, and it plays a crucial role in regulating feeding, behavior, growth, and metabolism. However, seasonal photoperiods are often overlooked in carp culture or experiments, with a poorly understood effect on lipid metabolism and oxidative stress in fish. To explore the effects of seasonal photoperiods, we exposed Huanghe carp (Cyprinus carpio haematopterus) to summer photoperiod (14 h light:10 h dark) and winter photoperiod (10 h light:14 h dark) daylight conditions in an eight-week experiment. Our results suggested that the winter photoperiod significantly increased the liver TG level as well as the transcript levels of genes related to lipid synthesis, indicating that the lipid metabolism in Huanghe carp liver was enhanced compared to summer photoperiod conditions, and that lipid deposition may be responsible for the increase in body weight level and hepatosomatic index. Additionally, MDA, GSH, GSH-PX, and T-AOC levels were significantly elevated in the liver of fish under the winter photoperiod, suggesting that Huanghe carp responded to winter photoperiod exposure-induced oxidative stress in the liver by enhancing the antioxidant response. Based on transcriptome analysis, the winter photoperiod activated hepatic autophagy response and the FOXO signaling pathway in Huanghe carp. Combined with the correlation analysis, the Huanghe carp maintains the physiological health of the liver by activating the FOXO signaling pathway-mediated cell cycle regulation and autophagy response in response to oxidative stress during winter photoperiod exposure. Our study provides the first evidence for the physiological regulation of the liver in Huanghe carp under seasonal photoperiod stimulation.

New benzofuran neolignans with neuroprotective activity from Phyllanthodendron breynioides - Tong Su; Mei-Cen Pu; Di-Kai Tang; Jin-Chen Long; Fang-Yu Yuan; Ai-Ping Yin; Shu-Qi Wu; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2023)

An investigation of Nitrospira bacteria in coastal wetlands of China: distribution pattern and related environmental driving factors - Qiang Zhao; Dongyao Sun; Xiufeng Tang; Lijun Hou; Min Liu; Ping Han (Frontiers in Marine Science, 2023)
Nitrate is mainly converted via aerobic nitrite oxidation during the second step of nitrification, which is catalyzed by nitrite-oxidizing bacteria (NOB) and the recently discovery complete ammonia oxidizers (comammox). Members of the genus Nitrospira are the most diverse and widespread known NOB and comammox. However, the community assembly of Nitrospira in estuary and coastal wetland and the major environmental shaping factors remain understudied. Here in this study, we investigated the geographical distribution pattern of Nitrospira along the large-scale coastal wetlands of China. The results showed that the abundance of Nitrospira ranged from 4.96×10 6 - 3.88×10 7 copies/g dry sediment, significantly (more than one order of magnitude) higher than amoA gene of ammonia-oxidizers. The identified Nitrospira belong to Nitrospira lineage IV (50%), lineage I and II. The adaptability of the three lineages to environmental factors (such as temperature, pH, salinity and particle size) are different, which leads to the diversity of its distribution composition in different estuaries. Network analysis showed that the cooperation takes greater portion than competition in the relationship of Nitrospira population. This study revealed the abundance and community composition of Nitrospira bacteria, as well as the major environmental driving factors in coastal wetland ecosystems, which deepens our understanding of the niche separation of Nitrospira with the nitrogen cycling.

Fast perception of rock mass strength and integrity in TBM tunnelling using in-situ penetration test - Wei-Qiang Xie; Xiao-Ping Zhang; Shao-Hui Tang; Xiao-Li Liu; Xin-Fang Li; Qi Zhang; Fa-Yuan Yan; Chen Xu; Quan-Sheng Liu (Tunnelling and Underground Space Technology, 2023)

Heavy metal stress in plants: Ways to alleviate with exogenous substances - Di Feng; Rongxue Wang; Xiaoan Sun; Li'nan Liu; Ping Liu; Jingchun Tang; Chenxi Zhang; Hao Liu (Science of The Total Environment, 2023)

Environmental cadmium exposure facilitates mammary tumorigenesis via reprogramming gut microbiota-mediated glutamine metabolism in MMTV-Erbb2 mice - Yang Yue; Huadong Zhang; Ping Deng; Miduo Tan; Chengzhi Chen; Bo Tang; Jingdian Li; Fengqiong Chen; Qi Zhao; Ling Li; Rongrong Hao; Hui Wang; et al. (Science of The Total Environment, 2023)

Contribution of the bacterial community of poorly fermented oat silage to biogas emissions on the Qinghai Tibetan Plateau - Chaosheng Liao; Binbin Na; Xiaolong Tang; Man Zhao; Changbing Zhang; Shiyong Chen; Minghong You; Binqiang Bai; Lizhuang Hao; Dorjeeh Tondrob; Guangpeng Qu; Shuqing Yang; et al. (Science of The Total Environment, 2023)

Electrical stimulation induces anti-tumor immunomodulation via a flexible microneedle-array-integrated interdigital electrode - Yixuan Pan; Yangxi Zhang; Xueying Shi; Dongdong Li; Xiaodan Xu; Bing Xiao; Ying Piao; Jiajia Xiang; Shiqun Shao; Frederic Chun-Yip Ho; Youqing Shen; A. Ping Zhang; et al. (Science Bulletin, 2023)

Lindenane sesquiterpenoid dimers from Chloranthus holostegius with anti-neuroinflammatory activities in BV-2 microglia - Zhao-Chun Zhan; Yi-Ping Xia; Qing Tang; Hui-Hui Zhu; Jing-Yi Du; Jun-Xing Cai; Yan-Jun Chen; Zhong-Nan Wu; Yao-Lan Li; Neng-Hua Chen; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2023)

Seasonal variations in source-sink balance of CO2 in subtropical earthen aquaculture ponds: Implications for carbon emission management - Lele Tang; Linhai Zhang; Ping Yang; Chuan Tong; Hong Yang; Lishan Tan; Yongxin Lin; Derrick Y.F. Lai; Kam W. Tang (Journal of Hydrology, 2023)

Enhancing catalytic hydrolysis activity of ZnNiAl hydrotalcite-like compounds-derived oxides using rare earth metals - Kunlin Li; Yu Tian; Xie Tang; Peng Gao; Xiao Peng; Ping Ning; Chi Wang; Fei Wang; Xin Sun; Kai Li (Journal of Cleaner Production, 2023)

Bisphenol analogues inhibit human and rat 17β-hydroxysteroid dehydrogenase 1: 3D-quantitative structure-activity relationship (3D-QSAR) and in silico docking analysis - Sailing Chen; Shaowei Wang; Jingyi Zheng; Han Lu; Huiqian Chen; Yunbing Tang; Nan Wang; Yang Zhu; Yiyan Wang; Ping Duan; Ren-shan Ge (Food and Chemical Toxicology, 2023)

Seismic design and experimental testing of precast tolerance concrete shear wall subject to cyclic load - Peng Mi; Ping Tan; Yiming Li; Zhibin Liu; Mengxiong Tang; Fulin Zhou (Engineering Structures, 2023)

Uniform lithium deposition regulated by lithiophilic Mo3N2/MoN heterojunction nanobelts interlayer for stable lithium metal batteries - Xiaojuan Zhang; Liang Zhou; Kunpeng Hu; Dandan Gao; Shuo Tang; Li He; Yuanfu Chen; Ping Zhang; Zhigang Zhang (Chemical Engineering Journal, 2023)

Soil organic nitrogen content and composition in different wetland habitat types along the south-east coast of China - Xiao Lin; Yanli Yang; Ping Yang; Yan Hong; Linhai Zhang; Chuan Tong; Derrick Y.F. Lai; Yongxin Lin; Lishan Tan; Yalan Tian; Kam W. Tang (CATENA, 2023)

Repair of dysfunctional bone marrow endothelial cells alleviates aplastic anemia - Shu-Qian Tang; Tong Xing; Zhong-Shi Lyu; Li-Ping Guo; Mi Liang; Chen-Yuan Li; Yuan-Yuan Zhang; Yu Wang; Lan-Ping Xu; Xiao-Hui Zhang; Xiao-Jun Huang; Yuan Kong (Science China Life Sciences, 2023)

Correction to: Effects of Dl-3‑n‑butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Effects of Dl-3-n-butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Vascular cognitive impairment (VCI) has been one of the major types of cognitive impairment. Blood–brain barrier damage plays an essential part in the pathogenesis of VCI. At present, the treatment of VCI is mainly focused on prevention, with no drug clinically approved for the treatment of VCI. This study aimed to investigate the effects of DL-3-n-butylphthalide (NBP) on VCI rats. A modified bilateral common carotid artery occlusion (mBCCAO) model was applied to mimic VCI. The feasibility of the mBCCAO model was verified by laser Doppler, 13 N-Ammonia-Positron Emission Computed Tomography (PET), and Morris Water Maze. Subsequently, the Morris water maze experiment, Evans blue staining, and western blot of tight junction protein were performed to evaluate the effect of different doses of NBP (40 mg/kg, 80 mg/kg) on the improvement of cognitive impairment and BBB disruption induced by mBCCAO. Immunofluorescence was employed to examine the changes in pericyte coverage in the mBCCAO model and the effect of NBP on pericyte coverage was preliminarily explored. mBCCAO surgery led to obvious cognitive impairment and the decrease of whole cerebral blood flow, among which the blood flow in the cortex, hippocampus and thalamus brain regions decreased more significantly. High-dose NBP (80 mg/kg) improved long-term cognitive function in mBCCAO rats, alleviated Evans blue leakage and reduced the loss of tight junction proteins (ZO-1, Claudin-5) in the early course of the disease, thereby exerting a protective effect on the blood–brain barrier. No significant changes in pericyte coverage were observed after mBCCAO. High-dose NBP improved cognitive function in mBCCAO rats. High-dose NBP protected the integrity of BBB by upregulating TJ protein expression, rather than regulating pericyte coverage ratio. NBP could be a potential drug for the treatment of VCI.

Simultaneous electrochemical detection of dimethyl bisphenol A and bisphenol A using a novel Pt@SWCNTs-MXene-rGO modified screen-printed sensor - Guangfei Qu; Yun Zhang; Junhong Zhou; Huimin Tang; Wei Ji; Zhoupeng Yan; Keheng Pan; Ping Ning (Chemosphere, 2023)

The influence of environmental humidity change on the stability of rock caves in Longyou Grottoes - Huihui Zhang; Tianjiao Li; Shibin Tang; Ping Li; Yanwu Wang; Chun'an Tang (Tunnelling and Underground Space Technology, 2023)

Cyclic utilization of waste aluminum polishing solution by an efficient co-extraction system: Influence factors and extraction mechanism - Hui Chen; Shixin Li; Yingna Li; Ziqian Du; Liying Bin; Weidong Li; Fenglian Fu; Ping Li; Bing Tang (Process Safety and Environmental Protection, 2023)

Free roll decay simulation of a polar research vessel with an anti-roll tank based on CFD - Chao Chen; Ya-dong Liu; Wei Zhang; Yan-ping He; Yu-ying Tang (Ocean Engineering, 2023)

Photo-assisted “co-movement catalysis”: CoFe2O4/CNS heterojunction based portable electrochemical sensor for simultaneous detection of Pb2+ and Cd2+ in natural water - Fengqian Xie; Feng Tang; Xinli Li; Xiaoran Wu; Shujun Wang; Hongqiang Xie; Ping Wang; Yueyun Li; Qing Liu (Journal of Hazardous Materials, 2023)

Characterization on nicotine degradation and research on heavy metal resistance of a strain Pseudomonas sp. NBB - Zhaoyong Xu; Tingting Zhang; Haiyang Hu; Wenzhao Liu; Ping Xu; Hongzhi Tang (Journal of Hazardous Materials, 2023)

Facet engineering of BiVO4 photocatalyst for the synergetic adsorption and activation of persulfate for organic pollutants degradation - Ling-Ling Zheng; Lei Tian; Dengke Wang; Ying Chen; Qian-Qian Tang; Qiu-Ju Xing; Xiao-Zhen Liu; Dai-She Wu; Jian-Ping Zou (Chemical Engineering Journal, 2023)

Sodium alginate based energy harvesting fibers: Multiscale structure and moist-electrical properties - Rui Zhang; Hai Wang; Meijie Qu; Shuhui Li; Yue Ma; Xinye Li; Ping Tang; Yuezhen Bin (Chemical Engineering Journal, 2023)

The culprit for the declining performance of anaerobic reactors caused by calcification: Bioavailability deterioration - Wenda Chen; Huiming Tang; Dongdong Xu; Wenji Li; Chao Pan; Leiyan Guo; Da Kang; Ping Zheng; Meng Zhang (Bioresource Technology, 2023)

Ecological distribution of anaerobic granular sludge towards efficient anaerobic reactor - Wenda Chen; Huiming Tang; Dongdong Xu; Wenji Li; Chao Pan; Leiyan Guo; Da Kang; Baolan Hu; Ping Zheng; Meng Zhang (Bioresource Technology, 2023)

Hyperthermophilic pretreatment significantly accelerates thermophilic composting humification through improving bacterial communities and promoting microbial cooperation - Shi-Peng Zhou; Su-Qin Tang; Xia Ke; Hai-Yan Zhou; Shu-Ping Zou; Ya-Ping Xue; Yu-Guo Zheng (Bioresource Technology, 2023)

The Epidemiology of Tinea Capitis in Guangxi Province, China - Dongyan Zheng; Tianwei Liang; Weixuan Wu; Najwa Al-Odaini; Kaisu Pan; Lan Huang; Guomei Huang; Lulu Tang; Xinlei Li; Shao He; Huahui Jian; Nibo Wei; et al. (Mycopathologia, 2023)

Insights into the life-cycle of aerobic granular sludge in a continuous flow membrane bioreactor by tracing its heterogeneous properties at different stages - Biao Yang; Weifeng Liang; Liying Bin; Weirui Chen; Xinyi Chen; Ping Li; Shanglong Wen; Shaosong Huang; Bing Tang (Water Research, 2023)

Twelve natural estrogens and ten bisphenol analogues in eight drinking water treatment plants: Analytical method, their occurrence and risk evaluation - Zhao Tang; Ze-hua Liu; Hao Wang; Yi-ping Wan; Zhi Dang; Peng-ran Guo; Yu-mei Song; Sa Chen (Water Research, 2023)

Afidopyropen suppresses silkworm growth and vitality by affecting carbohydrate metabolism and immune function - Erjun Wei; Ping He; Runpeng Wang; Sheng Xu; Yiling Zhang; Qiang Wang; Xudong Tang; Zhongyuan Shen (Pesticide Biochemistry and Physiology, 2023)

In situ deposition of double Fe-based Fenton catalysts on the porous membrane for the development of multi-defense against various foulants toward highly efficient water purification - Yu-Ling Yang; Gang Wang; Ping Zhu; Lei Tang; Zhi-Xiang Zeng; Li-Jing Zhu (Chemical Engineering Journal, 2023)

Spatiotemporal patterns and propagation mechanism of meteorological droughts over Yangtze River Basin and Pearl River Basin based on complex network theory - Chao Gao; Lei Liu; Silong Zhang; Yue-Ping Xu; Xiaoyan Wang; Xiongpeng Tang (Atmospheric Research, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Comparison and Selection of Index for Macro-indentation Test of Brittle Rock - Xiao-Ping Zhang; Xin-Mei Yang; Wei-Qiang Xie; Quan-Sheng Liu; Shao-hui Tang (Rock Mechanics and Rock Engineering, 2023)

Metabolic characteristics of self-pollinated wheat seed under red and blue light during early development - Ping Zhang; Yongsheng Tang; Yongjiang Liu; Junna Liu; Qianchao Wang; Hongxin Wang; Hanxue Li; Li Li; Peng Qin (Planta, 2023)

Enhancing catalytic performance of Fe and Mo co-doped dual single-atom catalysts with dual-enzyme activities for sensitive detection of hydrogen peroxide and uric acid - Jin Chen; Jiali Zhong; Juanhua Lai; Zoujun Peng; Tao Lian; Xiaomin Tang; Pengjun Li; Ping Qiu (Analytica Chimica Acta, 2023)

CMOS-based observation of Resident Space Objects using short-exposure stacking mode - Zheng-Hai Zhu; Jing-Hui Zheng; Hao Luo; Guo-Ping Chen; Wei Wang; Yin-Dun Mao; Wen-Tang Wu; Kun-Peng Wang (Advances in Space Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

UGT2B13 and UGT2C1 are involved in lambda-cyhalothrin resistance in Rhopalosiphum padi - Suji Wang; Xi Liu; Hongcheng Tang; Mengtian Li; Ping Gao; Xiong Peng; Maohua Chen (Pesticide Biochemistry and Physiology, 2023)

Investigation of the redox behavior of biochar-based bipolar electrochemistry in porous media - Hongwei Zhang; Haiyin Xu; Hui Zi; Yuwei Tang; Xijie Zheng; Ping Wang; Jing Huang; Honghui Wu; Peipei Song; linxin Wu; Zechen Liu; Wenshao Mao; et al. (Chemical Engineering Journal, 2023)

Application of 210Pbex in elucidating contemporary sedimentary dynamics in the water-level fluctuation zone of the Three Gorges Reservoir, China - Jinlin Li; Yuhai Bao; Jie Wei; Xiubin He; Qiang Tang; Xinbao Zhang; Shengjun Wu; Ping Huang; Hong Li (CATENA, 2023)

One-pot preparation of layered double oxides-engineered biochar for the sustained removal of tetracycline in water - Jiayi Tang; Yongfei Ma; Zhikang Deng; Ping Li; Xuebin Qi; Zulin Zhang (Bioresource Technology, 2023)

Compound-specific radiocarbon analysis of benzene polycarboxylic acids for source apportionment of polyaromatic organic matter in ambient aerosols - Xin Yi; Xiaofei Geng; Yangzhi Mo; Guangcai Zhong; Jiao Tang; Sanyuan Zhu; Zhineng Cheng; Shizhen Zhao; Jun Li; Örjan Gustafsson; Ping'an Peng; Gan Zhang (Atmospheric Environment, 2023)

Recent advances in micro (nano) plastics in the environment: Distribution, health risks, challenges and future prospects - Yan-Bo Ma; Zhuo-Yuan Xie; Naima Hamid; Qi-Ping Tang; Jiao-Yun Deng; Lin Luo; De-Sheng Pei (Aquatic Toxicology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

The first homosporous lycophyte genome revealed the association between the recent dynamic accumulation of LTR-RTs and genome size variation - Ji-Gao Yu; Jun-Yong Tang; Ran Wei; Mei-Fang Lan; Rui-Chen Xiang; Xian-Chun Zhang; Qiao-Ping Xiang (Plant Molecular Biology, 2023)

Estimating wheat grain yield by assimilating phenology and LAI with the WheatGrow model based on theoretical uncertainty of remotely sensed observation - Yining Tang; Ruiheng Zhou; Ping He; Minglei Yu; Hengbiao Zheng; Xia Yao; Tao Cheng; Yan Zhu; Weixing Cao; Yongchao Tian (Agricultural and Forest Meteorology, 2023)

Development of an LC-MS/MS method for the determination of multiple mycotoxins in human urine - Mobing Chen; Wei Liu; Ping Xiang; Linhao Xu; Yiling Tang; Ran Kong; Shuo Yang; Hui Yan; Bin Di (Food Additives & Contaminants: Part A, 2023)

Four cases of reported adverse effects from black boletoi, Anthracoporus nigropurpureus (Boletaceae) mushroom ingestion - Jing Ma; Jing Xia; Hai-Jiao Li; Lin-Jie Su; Rou Xue; Shuai Jiang; Tai-Jie Yu; Yi Liu; Li-Ping Tang (Toxicon, 2023)

Heavy metal(loid)s in agriculture soils, rice, and wheat across China: Status assessment and spatiotemporal analysis - Cheng-Chen Wang; Qiao-Chu Zhang; Chang-An Yan; Guo-Yong Tang; Meng-Yan Zhang; Lena Q. Ma; Rong-Hui Gu; Ping Xiang (Science of The Total Environment, 2023)

Effects of conversion of coastal marshes to aquaculture ponds on sediment anaerobic CO2 production and emission in a subtropical estuary of China - Lishan Tan; Linhai Zhang; Ping Yang; Chuan Tong; Derrick Y.F. Lai; Hong Yang; Yan Hong; Yalan Tian; Chen Tang; Manjing Ruan; Kam W. Tang (Journal of Environmental Management, 2023)

Hexachloroplatinic(IV)-GO colloids as ideal electrodes modification materials for electrochemical sensing, HER and OER - Guangfei Qu; Junhong Zhou; Wei Ji; Huimin Tang; Kunling Wei; Yun Zhang; Keheng Pan; Ping Ning (Chemical Engineering Journal, 2023)

Degradation of PCB77 in spiked soils by ferrous sulfide-activated persulfate combined with potassium permanganate - Yue Bu; Nannan Wu; Yumeng Qi; Junyan Wei; Xiaosheng Tang; Ahmed A Allam; Ping Sun; Zunyao Wang; Ruijuan Qu (Chemical Engineering Journal, 2023)

Effects of fungal agents and biochar on odor emissions and microbial community dynamics during in-situ treatment of food waste - Shu-Ping Zou; Ru-Sheng Liu; Yu Luo; Chun-Tao Bo; Su-Qin Tang; Ya-Ping Xue; Yu-Guo Zheng (Bioresource Technology, 2023)

Applying expanded metal mesh for outdoor shades in outdoor thermal environments - Shing-Ru Yang; Shih-Tang Lan; Yi-Ting Wu; Tsuyoshi Honjo; Tzu-Ping Lin (International Journal of Biometeorology, 2023)

lA multiple PAHs-degrading Shinella sp. strain and its potential bioremediation in wastewater - Zan Wang; Haiyang Hu; Zhan Zhang; Yongming Xu; Ping Xu; Hongzhi Tang (Science of The Total Environment, 2023)

Formation and transport of fluid mud triggered by typhoon events in front of the subaqueous Changjiang Delta - Jieping Tang; Hao Wu; Fei Xing; Fan Zhang; Bixuan Tang; Gaocong Li; Ya Ping Wang (Marine Geology, 2023)

Magma system and equilibrium depth of the Cenozoic basalts in the central North China craton - Xiangdong Su; Jianhua Ping; Wei Leng; Jichang Zhao; Yanjie Tang; Jiaqi Liu (Lithos, 2023)

Environmentally relevant level of perfluorooctanoic acid affect the formation of aerobic granular sludge - Zhouyun Xie; Ni Zhang; Guojing Yang; Qiuxiang Xu; Dongbo Wang; Li Tang; Jingfen Xia; Ping Li; Xiaoming Li (Journal of Environmental Management, 2023)

Efficient removal of refractory dyestuffs from textile wastewater by composite hydrated alumina derived from waste aluminum polishing solution - Shixin Li; Hui Chen; Yingna Li; Ziqian Du; Liying Bin; Weidong Li; Fenglian Fu; Ping Li; Bing Tang (Journal of Environmental Chemical Engineering, 2023)

Highly sensitive detection of thiram residues on fruit peel surfaces using a filter paper-based SERS sensor with AgNWs@ZIF-8 - Nuan Xu; Zhenhua Tang; Yan-Ping Jiang; Junlin Fang; Li Zhang; Xiaofang Lai; Qi-Jun Sun; Jing-Min Fan; Xin-Gui Tang; Qiu-Xiang Liu; Ji-Kang Jian (Journal of Environmental Chemical Engineering, 2023)

Effects of landscape modification on coastal sediment nitrogen availability, microbial functional gene abundances and N2O production potential across the tropical-subtropical gradient - Ping Yang; Kam W. Tang; Linhai Zhang; Xiao Lin; Hong Yang; Chuan Tong; Yan Hong; Lishan Tan; Derrick Y.F. Lai; Yalan Tian; Wanyi Zhu; Manjing Ruan; et al. (Environmental Research, 2023)

PSS modified by 3-aminopropyltrimethoxysilane linking large-area GNPs/PSS to silicone rubber with stable interface combination for high sensitivity flexible resistive sensor - Han Feng; Ping Liu; Xu Guo; Junliang Li; Yifan Sun; Shunge Wu; Ruohai Hu; Zhi Liu; Helei Tian; Yuanming Ma; Caixia Liu; Houzhu Huang; et al. (Chemical Engineering Journal, 2023)

Rapid granulation of aerobic granular sludge in an integrated moving bed biofilm reactor-membrane bioreactor: Effects and mechanism of Streptomyces cellulosus microspheres - Huanlong Zhang; Yue Xu; Liying Bin; Ping Li; Fenglian Fu; Shaosong Huang; Bing Tang (Bioresource Technology Reports, 2023)

Effect of co-inoculation of Lactobacillus plantarum and Lentilactobacillus buchneri on aerobic stability and microbial community composition of perennial sorghum silage - Maoya Li; Shufeng Zhou; Xiaolong Tang; Chaosheng Liao; Ping Li; Yixiao Xie; Qiming Cheng; Chao Chen (Biomass and Bioenergy, 2023)

The Relationship Between Phytoplankton Diversity and Ecosystem Functioning Changes with Disturbance Regimes in Tropical Reservoirs - Yuping Xu; Lu Wang; Quehui Tang; Luigi Naselli-Flores; Erik Jeppesen; Bo-Ping Han (Ecosystems, 2023)

Experimental study on flow and heat transfer of supercritical carbon dioxide in zigzag channels with bending angle 30° for advanced nuclear systems - Sheng-hui Liu; Rui-long Liu; Yan-ping Huang; Xiao-liang Zhu; Liu Yang; Jia Tang; Bin Han; Tian-yang Xing; Xue-bin Zhao (Annals of Nuclear Energy, 2023)

Late cretaceous magmatism in the Northern Lhasa subterrane, central Tibet: geodynamic implications - Miao Sun; Wei Chen; Reiner Klemd; Ju-Xing Tang; Xu-Dong Ma; Qing-Ping Liu (International Geology Review, 2023)

Erosion and accretion of salt marsh in extremely shallow water stages - Dezhi Chen; Jieping Tang; Fei Xing; Jun Cheng; Mingliang Li; Yiyi Zhang; Benwei Shi; Lianqiang Shi; Ya Ping Wang (Frontiers in Marine Science, 2023)
Salt marshes, which commonly exist on the upper tidal flat, provide a natural barrier against sea level rise and coastal storm. The extremely shallow water stages (water depth< 0.2 m), including the initial stage of flood tides and the last stage of ebb tides, can induce a significant impact on sediment dynamics of saltmarshes and associated tidal flats, despite lasting for only a short time (around 10 min), which has been less studied. In this study, two parallel field sites were established to quantify erosion-accretion processes and morphological changes during extremely shallow water stages in salt marshes within Doulonggang tidal flat along the Jiangsu coast. Our results revealed that obvious accretion occurred during extremely shallow water stages, with a total deposition amount of +33.8 mm in vegetated areas and +20.8 mm in unvegetated areas. In contrast, erosion dominated during deep water stages, with a total erosion amount of -22.3 mm at the vegetated site and -32.7 mm at the unvegetated site. The magnitude of bed-level change during extremely shallow water stages was 7~8 times greater than that during deep water stages, even though the duration of extremely shallow water stages was only about 14~15% of the entire tidal cycle. Furthermore, strong winds significantly impacted deposition during extremely shallow water stages compared to calm weather. During the strong wind period, the average bed level change rate reached +0.15 mm/min and +0.12 mm/min in the vegetated and unvegetated areas, respectively. This is significantly higher than the +0.05 mm/min and +0.01 mm/min during the calm weather period. These results reveal that extremely shallow water stages have substantial impacts on sedimentary processes, which are vital for the maintenance of tidal flat systems.

Effects of chitosan coating combined with thermal treatment on physicochemical properties, bacterial diversity and volatile flavor of braised duck meat during refrigerated storage - Huanhuan Li; Sijia Qu; Ping Ma; Jin Zhang; Ke Zhao; Lihong Chen; Qicheng Huang; Gaohang Zou; Honggang Tang (Food Research International, 2023)

Flexible phase change films with enhanced thermal conductivity and low electrical conductivity for thermal management - Yuang Zhang; Ping Wu; Yao Meng; Rongwen Lu; Shufen Zhang; Bingtao Tang (Chemical Engineering Journal, 2023)

Responses of coastal sediment organic and inorganic carbon to habitat modification across a wide latitudinal range in southeastern China - Yan Hong; Linhai Zhang; Ping Yang; Chuan Tong; Yongxin Lin; Derrick Y. F. Lai; Hong Yang; Yalian Tian; Wanyi Zhu; Kam W. Tang (CATENA, 2023)

Mathematical Model of Two-Phase Spontaneous Imbibition with Dynamic Contact Angle - Lei Zhang; Jingjing Ping; Bo Tang; Lixin Kang; Gloire Imani; Yongfei Yang; Hai Sun; Junjie Zhong; Jun Yao; Dongyan Fan (Transport in Porous Media, 2023)

Comprehensive study on the hydrochar for adsorption of Cd(II): preparation, characterization, and mechanisms - Xu Han; Zirui Wang; Nan Lu; Jiaqing Tang; Ping Lu; Ke Zhu; Jiunian Guan; Til Feike (Environmental Science and Pollution Research, 2023)

Transcriptomic profiling and differential analysis reveal the renal toxicity mechanisms of mice under cantharidin exposure - Xin Liu; Linghan Zhang; Wenchao Tang; Tingting Zhang; Ping Xiang; Qin Shen; Taotao Ye; Yuanyuan Xiao (Toxicology and Applied Pharmacology, 2023)

Lignin-based covalent organic polymers with improved crystallinity for non-targeted analysis of chemical hazards in food samples - Zhan-Chao Li; Wei Li; Rui Wang; Dong-Xia Wang; An-Na Tang; Xiao-Peng Wang; Xiao-Ping Gao; Gai-Ming Zhao; De-Ming Kong (Journal of Hazardous Materials, 2023)

Anaerobic biodegradation of polycyclic aromatic hydrocarbons - Chao Chen; Zhan Zhang; Ping Xu; Haiyang Hu; Hongzhi Tang (Environmental Research, 2023)

Low-temperature efficient removal of PH3 over novel Cu-based adsorbent in an anaerobic environment - Yuan Tang; Jiayu Feng; Ping Ning; Fei Wang; Xin Sun; Kai Li (Chemical Engineering Journal, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Correction to: Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

Transition of source/sink processes and fate of ammonium in groundwater along with redox gradients - Li-Li Han; Helin Wang; Lianghao Ge; Min Nina Xu; Jin-Ming Tang; Li Luo; Ping Li; Shuh-Ji Kao (Water Research, 2023)

Seismic behavior of unbonded post-tension wall with replaceable energy dissipator - Peng Mi; Ping Tan; Yiming Li; Xiaofeng Zhao; Mengxiong Tang (Soil Dynamics and Earthquake Engineering, 2023)

Benzimidazole fungicide biotransformation by comammox Nitrospira bacteria: Transformation pathways and associated proteomic responses - Ping Han; Ana B. Rios-Miguel; Xiufeng Tang; Yaochun Yu; Li-Jun Zhou; Lijun Hou; Min Liu; Dongyao Sun; Mike S.M. Jetten; Cornelia U. Welte; Yujie Men; Sebastian Lücker (Journal of Hazardous Materials, 2023)

Ammonia-oxidizing archaea and comammox Nitrospira clade B as freeze–thaw resistant nitrifiers in wetland soils - Xiufeng Tang; Jun Li; Dongyao Sun; Linfa Fang; Lijun Hou; Min Liu; Ping Han (International Biodeterioration & Biodegradation, 2023)

Genome-wide transcriptome analysis uncovers gene networks regulating fruit quality and volatile compounds in mango cultivar 'Tainong' during postharvest - Li Li; Ping Yi; Jian Sun; Jie Tang; Guoming Liu; Jinfeng Bi; Jianwen Teng; Meijiao Hu; Fang Yuan; Xuemei He; Jinfeng Sheng; Ming Xin; et al. (Food Research International, 2023)

Effects of different extraction methods on the structural, antioxidant and hypoglycemic properties of red pitaya stem polysaccharide - Yayuan Tang; Xuemei He; Guoming Liu; Zhen Wei; Jinfeng Sheng; Jian Sun; Changbao Li; Ming Xin; Li Li; Ping Yi (Food Chemistry, 2023)

Liquid water determination by airborne millimeter cloud radar and in-situ size distribution measurements - Dongfei Zuo; Dantong Liu; Delong Zhao; Ling Yang; Yichen Chen; Wei Zhou; Mengyu Huang; Hui He; Ping Tian; Yuanmou Du; Wei Xiao; Ruijie Li; et al. (Atmospheric Research, 2023)

Comparison between the stem and leaf photosynthetic productivity in Eucalyptus urophylla plantations with different age - Xia Chen; Mingyu Luo; Yulin Kang; Ping Zhao; Zhiyao Tang; Yuanyuan Meng; Li Huang; Yanpei Guo; Xiancheng Lu; Lei Ouyang; Markku Larjavaara (Planta, 2023)

Correction to: Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2023)

Anti-Vascular Endothelial Growth Factor Therapy Abolishes Glioma-Associated Endothelial Cell-Induced Tumor Invasion - Feng Tang; Feng-Ping Li; Xue-Tao Huang; Guo-Hua Wang; Ze-Fen Wang; Zhi-Qiang Li (Journal of Molecular Neuroscience, 2023)

Two new tetrahydroisoquinoline alkaloids from Portulaca oleracea - Kai-Jun Tang; Yu Chen; Jing Li; Xu Tao; Lu-Ping Yang; Tian-Yun Jin; Jia-Shun Zhu; Yu Zhao; Tao Shen; Xiao-Ning Wang; Dong-Mei Ren; Lan Xiang (Phytochemistry Letters, 2023)

Mitogenome-based phylogenomics provides insights into the positions of the enigmatic sinensis group and the sanguinolenta group in Selaginellaceae (Lycophyte) - Jun-Yong Tang; Ran Wei; Xian-Chun Zhang; Qiao-Ping Xiang (Molecular Phylogenetics and Evolution, 2023)

Contrasting effects of aeration on methane (CH4) and nitrous oxide (N2O) emissions from subtropical aquaculture ponds and implications for global warming mitigation - Ping Yang; Kam W. Tang; Hong Yang; Chuan Tong; Linhai Zhang; Derrick Y.F. Lai; Yan Hong; Lishan Tan; Wanyi Zhu; Chen Tang (Journal of Hydrology, 2023)

Spectral change of dissolved organic matter after extracted by solid-phase extraction and its feasibility in predicting the acute toxicity of polar organic pollutants in textile wastewater - Lingfang Fu; Liying Bin; Zhaobo Luo; Zehong Huang; Ping Li; Shaosong Huang; Dieudonne Nyobe; Fenglian Fu; Bing Tang (Journal of Hazardous Materials, 2023)

Experimental and kinetic study on JP-10/air autoignition and the effect of NO2 at high temperatures - Lei Shi; Ping Xu; Rui Wang; Weixin Tang; Tao Ding; Rongpei Jiang; Changhua Zhang (Fuel, 2023)

Phospholipase A2 induces acute kidney injury by complement mediated mitochondrial apoptosis via TNF-α/NF-κB signaling pathway - Xin Tang; Tiantian Wei; Mingjing Guan; Peiyun Li; Yajun Pu; Lixin Cheng; Zhifeng Zhou; Ping Fu; Ling Zhang (Food and Chemical Toxicology, 2023)

Fluid transport in porous media based on differences in filter media morphology and biofilm growth in bioreactors - Ping Tang; Henglei Xu; Wenming Zhang; Yixuan Zhu; Jin Yang; Yongchao Zhou (Environmental Research, 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Coexistence of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and IgA nephropathy - Qi Xiong; Wei Lin; Chanjuan Shen; Ting Meng; Rong Tang; Joshua D. Ooi; Peter J. Eggenhuizen; Jinbiao Chen; Wannian Nie; Xia Li; Qiaoling Zhou; Ping Xiao; et al. (Immunologic Research, 2023)

Biofertilizer made from a mixed microbial community can enhance the suppression of fusarium wilt of banana when combined with acid soil ameliorant - Jianfeng Huang; Yuwan Pang; Gen Cheng; Tengfei Wu; Qiaoyi Huang; Xu Huang; Qiong Yi; Mu Zhang; Shuanhu Tang; Hongting Fu; Ping Li (European Journal of Plant Pathology, 2023)

Quantifying the relative contribution of driving factors to the transformation of bauxite residue into a plant growth substrate - Shiming Tang; Xi Zhang; Xueqian Ren; Ping Du; Jie Ren (Soil and Tillage Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Sedimentary dinoflagellate cyst records of human-induced environmental changes in Daya Bay, the northern South China Sea - Ping-Ping Shen; Ying Li; Ya-Nan Tang; Qing-Shang Song; Yue Xue (Journal of Marine Systems, 2023)

Enhanced elemental mercury removal in coal-fired flue gas by modified algal waste-derived biochar: Performance and mechanism - Qihao Cao; Chang Wang; Daoyuan Tang; Xuedong Zhang; Ping Wu; Yan Zhang; He Liu; Zhiyong Zheng (Journal of Environmental Management, 2023)

Experimental study on flexural behavior of UHPC wet joint in prefabricated multi-girder bridge - En-Feng Deng; Zhe Zhang; Chen-Xi Zhang; Yi Tang; Wei Wang; Zhan-Jun Du; Ji-Ping Gao (Engineering Structures, 2023)

Synthesis and adsorption properties of metal oxide-coated lithium ion-sieve from salt lake brine - Lu-Ri Bao; Jing-Ze Zhang; Wei-Ping Tang; Shu-Ying Sun (Desalination, 2023)

Valence engineering at the interface of MoS2/Mo2C heterostructure for bionic nitrogen reduction - Tong Ye; Kun Ba; Xiaoyong Yang; Taishi Xiao; Yangye Sun; Hanqi Liu; Can Tang; Binghui Ge; Ping Zhang; Tao Duan; Zhengzong Sun (Chemical Engineering Journal, 2023)

Hydroxychloroquine repairs burn damage through the Wnt/β-catenin pathway - Sheau-Chung Tang; Chun-Te Lu; Jiunn-Liang Ko; Cheng-Hui Lin; Yu-Ping Hsiao (Chemico-Biological Interactions, 2023)

Genetic lineage tracing identifies cardiac mesenchymal-to-adipose transition in an arrhythmogenic cardiomyopathy model - Xinyan Huang; Lei Yan; Jufeng Meng; Nanbo Liu; Shuoji Zhu; Zhen Jiang; Shan Kou; Teng Feng; Chao-Po Lin; Bin Zhou; Juan Tang; Ping Zhu; et al. (Science China Life Sciences, 2023)

Transcriptome analyses reveal the effects of mixed saline–alkali stress on indoleacetic acid and cytokinins in Malus hupehensis Rehd. leaves - Xin-Liang Wang; Ling Peng; Jian Wang; Jing-Lei Liu; Jing-Jing Jia; Li-Ping Tang (Physiology and Molecular Biology of Plants, 2023)

Key technology for the construction and inspection of long-distance underwater tunnel for 1000 kV gas-insulated transmission line - Xiao-Ping Zhang; Shao-Hui Tang; Quan-Sheng Liu; Hao-Jie Wang; Xin-Fang Li; Peng Chen; Hao Liu (Bulletin of Engineering Geology and the Environment, 2023)

Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

Diffusive nitrous oxide (N2O) fluxes across the sediment-water-atmosphere interfaces in aquaculture shrimp ponds in a subtropical estuary: Implications for climate warming - Yalan Tian; Ping Yang; Hong Yang; Huimin Wang; Linhai Zhang; Chuan Tong; Derrick Y.F. Lai; Yongxin Lin; Lishan Tan; Yan Hong; Chen Tang; Kam W. Tang (Agriculture, Ecosystems & Environment, 2023)

Insights into the health status of the general population living near an electroplating industry zone: metal elevations and renal impairment - Peiwei Xu; Shiming Lai; Lizhi Wu; Weizhong Chen; Yuan Chen; Dandan Xu; Jie Xiang; Ping Cheng; Zhijian Chen; Xiaofeng Wang; Xiaoming Lou; Jun Tang (Environmental Science and Pollution Research, 2022)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Ten years of warming increased plant-derived carbon accumulation in an East Asian monsoon forest - Jing Zhang; Luhui Kuang; Zhijian Mou; Toshiaki Kondo; Jun Koarashi; Mariko Atarashi-Andoh; Yue Li; Xuli Tang; Ying-Ping Wang; Josep Peñuelas; Jordi Sardans; Dafeng Hui; et al. (Plant and Soil, 2022)

Combined analysis of mRNA and miRNA reveals the banana potassium absorption regulatory network and validation of miRNA160a - Wenliang Chen; Tao Dong; Yinglong Chen; Ping Lin; Chuqiao Wang; Kelin Chen; Yi Tang; Mingyuan Wang; Jianfu Liu; Hailing Yu (Plant Molecular Biology, 2022)

Three-Dimensional Ultrasound Localization Microscopy with Bipartite Graph-Based Microbubble Pairing and Kalman-Filtering-Based Tracking on a 256-Channel Verasonics Ultrasound System with a 32 × 32 Matrix Array - U-Wai Lok; Chengwu Huang; Joshua D. Trzasko; Yohan Kim; Fabrice Lucien; Shanshan Tang; Ping Gong; Pengfei Song; Shigao Chen (Journal of Medical and Biological Engineering, 2022)
Purpose Three-dimensional (3D) ultrasound localization microscopy (ULM) using a 2-D matrix probe and microbubbles (MBs) has recently been proposed to visualize microvasculature in three spatial dimensions beyond the ultrasound diffraction limit. However, 3D ULM has several limitations, including: (1) high system complexity, (2) complex MB flow dynamics in 3D, and (3) extremely long acquisition time that had to be addressed. Method To reduce the system complexity while maintaining high image quality, we used a sub-aperture process to reduce received channel counts. To address the second issue, a 3D bipartite graph-based method with Kalman filtering-based tracking was used in this study for MB tracking. An MB separation approach was incorporated to separate high concentration MB data into multiple, sparser MB datasets, allowing better MB localization and tracking for a limited acquisition time. Results The proposed method was first validated in a flow channel phantom, showing improved spatial resolutions compared with the contrasted enhanced power Doppler image. Then the proposed method was evaluated with an in vivo chicken embryo brain dataset. Results showed that the reconstructed 3D super-resolution image achieved a spatial resolution of around 52 μm (smaller than the wavelength of around 200 μm). Conclusion A lower system complexity of 3D ULM has been proposed. In addition, our proposed 3D ULM provided the capability of 3D motion compensation and MB tracking. Microvessels that cannot be resolved clearly using localization only, can be well identified with the proposed method.

Isolation and identification of two Beauveria bassiana strains from silkworm, Bombyx mori - Yiling Zhang; Xu Yang; Jiao Zhang; Mingzhen Ma; Ping He; Yu Li; Qiang Wang; Xudong Tang; Zhongyuan Shen (Folia Microbiologica, 2022)

Characterization of a novel victorivirus from Nigrospora chinensis, a fungus isolated from tobacco - Jie Zhong; Wen Wen Sui; Ping Li; Qian Jun Tang; Tian Bo Liu; Yan Song Xiao (Archives of Virology, 2022)

p21-activated kinase 1 (PAK1) as a therapeutic target for cardiotoxicity - Ping Guo; Yufeng Liu; Jingrong Feng; Shihang Tang; Fanyan Wei; Jian Feng (Archives of Toxicology, 2022)

Application of regional citrate anticoagulation in patients at high risk of bleeding during intermittent hemodialysis: a prospective multicenter randomized controlled trial - Xiaoyan Tang; Dezheng Chen; Ling Zhang; Ping Fu; Yanxia Chen; Zhou Xiao; Xiangcheng Xiao; Weisheng Peng; Li Cheng; Yanmin Zhang; Hongbo Li; Kehui Li; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Paenibacillus hamazuiensis sp. nov., a bacterium isolated from Hamazui hot spring in Yunnan province, south-west China - Juan Wang; Ming Deng; En-Min Zhou; Lei Ran; Cui-Ping Miao; Yi-Qing Li; Jun-Mei Ding; Shu-Kun Tang (Archives of Microbiology, 2022)

Bioclogging alleviation for constructed wetland based on the interaction among biofilm growth and hydrodynamics - Ping Tang; Li Chen; Wenming Zhang; Yongchao Zhou (Environmental Science and Pollution Research, 2022)

Characterization of infected process and primary mechanism in rice Acuce defense against rice blast fungus, Magnaporthe oryzae - Xiaoqing Ma; Guihua Duan; Hongfeng Chen; Ping Tang; Shunyu Su; Zhaoxia Wei; Jing Yang (Plant Molecular Biology, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Phylogeny and species diversity in Hygrophorus section Aurei in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Gabriel Moreno; Yun-Ju Pu; Yu-Guang Fan; Shu-Da Yang; Tie-Zhi Liu; Li-Ping Tang (Mycological Progress, 2022)

Comprehensive Transcriptome Analysis of Tea Crabapple (Malus hupehensis Rehd.) Roots Subjected to Mixed Saline–Alkali Stress - Xin-Liang Wang; Ling Peng; Jian Wang; Jing-Jing Jia; Li-Ping Tang (Plant Molecular Biology Reporter, 2022)

Degradation mechanism of HCN by electrochemically coupled copper-loaded magnetic nanoparticles in a liquid phase pseudo-homogeneous system - Guangfei Qu; Wei Ji; Junyan Li; Shuaiyu Liang; Zhishuncheng Li; Huimin Tang; Junhong Zhou; Ping Ning (Environmental Science and Pollution Research, 2022)

Mapping the spatial distribution of fossil geothermal manifestations and assessment of geothermal potential of the Tangyin rift, Southeast of Taihang Mountain in China - Joshua Mahwa; Da-jiang Li; Jian-hua Ping; Wei Leng; Jia-bo Tang; Dong-yun Shao (Journal of Mountain Science, 2022)
The spatial prediction of geothermal sites along the southeast side of Taihang Mountain in the Tangyin rift is a critical goal in the development of renewable energy resources in cities such as Hebi in Henan province, which has significant potential for geothermal energy production due to the existence of deep faults and Cenozoic volcano. The study aimed to delineate areas with high geothermal manifestations for detailed geothermal exploration and well-test drilling. To define favorable zones for geothermal potentiality, multi-source datasets were chosen to generate evidence thematic layers that demonstrate the distribution of geothermal anomalies such as geologic maps, structural maps, Land Surface Temperature maps (LST), and hydrothermal mineral alterations maps. The remote sensing and Geographical Information System (GIS) approaches were integrated to map fossil geothermal manifestations and appraise the promising geothermal zones from Landsat 8 OLI/TIRS and Advanced Spaceborne Thermal Emission and Reflection Radiometer-Digital Elevation Model (ASTER-DEM) dataset using the Analytic Hierarchy Process (AHP), which is one of the Mult-criteria Decision Making methods. Results show LST values ranging from 22.6°C to 45.4°C, with the highest values found along the faults and volcanic areas. The hydrothermal alteration minerals discriminated from band ratios of 4/2, 6/5, and 6/7 for iron oxide, ferrous minerals, and clays reveal the presence of high amount of montmorillonite and illite minerals along the faults and volcanoes which are related to hot fluid circulation from subsurface. Structural analysis shows that the major structural trend follows the NNE Tangdong and Tangxi faults, with high density on the west side of the Tangxi fault where there is good exposure of outcrop but less fault density on the east side due to sedimentation in a low land which may conceal geological structures. Lastly, all the thematic layers of geothermal factors were reclassified, ranked, and integrated by the weight overlay logic model based on the influence of geothermal suitability to map potential areas for geothermal resources whereby 5 zones were obtained ranging from very poor to very good. The promising potential sites are mostly found along the highly deep structures of the major Tangxi fault crosscutting the permeable lithology of carbonate rocks and around the Hebi volcanoes. The distribution of hot springs and geothermal wells of the Hebi field were correlated and verified against the potential geothermal anomalies map. The overall integrated method proposes an advanced technique for designing the Tangyin rift’s exploration plan and development actions for geothermal resources utilization, which can be used for exploration of any unveiling geothermal potential sites.

ML323, a USP1 inhibitor triggers cell cycle arrest, apoptosis and autophagy in esophageal squamous cell carcinoma cells - Yaxin Sun; Beibei Sha; Wenjing Huang; Miaomiao Li; Shan Zhao; Yuan Zhang; Jie Yan; Zheng Li; Jingwen Tang; Peiyan Duan; Jianxiang Shi; Pei Li; et al. (Apoptosis, 2022)

Cadinane-type sesquiterpenes with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Mappianthus iodoides - Yan-Ping Liu; Xiao-Mei Yu; Ze-Hua Qiao; Bo Jiang; Lan Xie; Hao-Xuan Tang; Xiao Liang; Yan-Hui Fu (Natural Product Research, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Discovery of potential anti-SARS-CoV-2 drugs based on large-scale screening in vitro and effect evaluation in vivo - Haoran Peng; Cuiling Ding; Liangliang Jiang; Wanda Tang; Yan Liu; Lanjuan Zhao; Zhigang Yi; Hao Ren; Chong Li; Yanhua He; Xu Zheng; Hailin Tang; et al. (Science China Life Sciences, 2022)

Use of DNA nanosensors based on upconverting nanoparticles for detection of Nosema bombycis by fluorescence resonance energy transfer - Ping He; Hongli Chen; Jiancheng Sun; Qiang Wang; Xudong Tang; Yiling Zhang; Feng Zhu; Zhongyuan Shen (Folia Microbiologica, 2022)

A critical review on EDTA washing in soil remediation for potentially toxic elements (PTEs) pollutants - Yaoning Chen; Hongjuan Jiang; Yuanping Li; Yihuan Liu; Yanrong Chen; Li Chen; Xinli Luo; Ping Tang; Haoqin Yan; Mengyang Zhao; Yu Yuan; Suzhen Hou (Reviews in Environmental Science and Bio/Technology, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Potential Application of Biosurfactant-Producing Bacteria for Bioremediation of Oil Polluted Marine Intertidal Sediments - Ping Guo; Wei-Wei Xu; Dan-Na Wei; Man-Xia Zhang; Jin Zhang; Shi Tang; Bin-Xia Cao; Jian-Guo Lin; Wei Li (Journal of Marine Science and Engineering, 2022)
The removal of oil contaminants in marine intertidal sediments under cold climate is an urgent issue. Although the bioavailability of petroleum hydrocarbons decreases at low temperatures, biosurfactants can promote oil biodegradation. In this study, characteristics of biosurfactants produced by cold-adapted oil-degrading bacteria Planococcus sp. XW-1 were studied. Adding the XW-1 biosurfactant could effectively facilitate the solubility of phenanthrene, pyrene, diesel oil, and crude oil. The solubilization was limited by the number of rings and the molecular weight (WSRphenanthrene = 0.0234; WSRpyrene = 0.0165; WSRdiesel oil = 0.0027; WSRcrude oil = 0.0015). Additional biosurfactants significantly washed out crude oil adsorbed to the sand (reduction from 17.1%, 22.7% to 87.9% and 94.28% in 24 h). With the increase in particle size, the removal efficiency increased from 87.9% to 94.28%. After the addition of biosurfactant, the effect of degradation increased by 20% in 20 days. The results suggest that the biosurfactant-producing bacteria Planococcus sp. XW-1 is a promising candidate used in the in situ bioremediation of petroleum-contaminated intertidal sediment.

Prenylated coumarins from the fruits of Artocarpus heterophyllus with their potential anti-inflammatory and anti-HIV activities - Lei Tao; Ya-Ting Zhuo; Ze-Hua Qiao; Juan Li; Hao-Xuan Tang; Qiao-Mei Yu; Yun-Yao Liu; Yan-Ping Liu (Natural Product Research, 2022)

Medium chain triglyceride and medium-and long chain triglyceride: metabolism, production, health impacts and its applications – a review - Yee-Ying Lee; Teck-Kim Tang; Eng-Seng Chan; Eng-Tong Phuah; Oi-Ming Lai; Chin-Ping Tan; Yong Wang; Nur Azwani Ab Karim; Noorlida Habi Mat Dian; Joo Shun Tan (Critical Reviews in Food Science and Nutrition, 2022)

Revising the species diversity of Hygrophorus section Olivaceoumbrini s.l. (Hygrophoraceae, Agaricales) in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Shuai Jiang; Yan-Jia Hao; Man Mu; Li-Ping Tang (Mycological Progress, 2022)

Spatial and temporal characteristics, influencing factors and prediction models of water quality and algae in early stage of Middle Route of South-North Water Diversion Project - Zheng Jing; Hao Chen; Huiqun Cao; Xianqiang Tang; Yuming Shang; Yuhan Liang; Ping’an Luo; Huiping Luo (Environmental Science and Pollution Research, 2022)

Potent immunosuppressive and anti-inflammatory bisindole alkaloids from Melodinus fusiformis - Lu Liu; Ming-Jun Xie; Wen-Bing Zhou; Jin-Tang Wang; Jia-Yi Wang; Afsar Khan; Ya-Ping Liu; Jian-Xin Cao; Gui-Guang Cheng; Wen-Yuan Mao (Natural Product Research, 2022)

Activating PIK3CA postzygotic mutations in segmental overgrowth of muscles with bone involvement in the body extremities - Wen Tian; Liying Sun; Qi Zhang; Junhui Zhao; Yang Guo; Wenyao Zhong; Liu Liu; Katia Meirelles; Sha Tang; Jing Zhang; Yingzhao Huang; Yuehan Yin; et al. (Molecular Genetics and Genomics, 2022)

Detection of functional and structural brain alterations in female schizophrenia using elastic net logistic regression - Ying Wu; Ping Ren; Rong Chen; Hong Xu; Jianxing Xu; Lin Zeng; Donghui Wu; Wentao Jiang; NianSheng Tang; Xia Liu (Brain Imaging and Behavior, 2022)
Neuroimaging technique is a powerful tool to characterize the abnormality of brain networks in schizophrenia. However, the neurophysiological substrate of schizophrenia is still unclear. Here we investigated the patterns of brain functional and structural changes in female patients with schizophrenia using elastic net logistic regression analysis of resting-state functional magnetic resonance imaging data. Data from 52 participants (25 female schizophrenia patients and 27 healthy controls) were obtained. Using an elastic net penalty, the brain regions most relevant to schizophrenia pathology were defined in the models using the amplitude of low-frequency fluctuations (ALFF) and gray matter, respectively. The receiver operating characteristic analysis showed reliable classification accuracy with 85.7% in ALFF analysis, and 77.1% in gray matter analysis. Notably, our results showed eight common regions between the ALFF and gray matter analyses, including the Frontal-Inf-Orb-R, Rolandic-Oper-R, Olfactory-R, Angular-L, Precuneus-L, Precuenus-R, Heschl-L, and Temporal-Pole-Mid-R. In addition, the severity of symptoms was found positively associated with the ALFF within the Rolandic-Oper-R and Frontal-Inf-Orb-R. Our findings indicated that elastic net logistic regression could be a useful tool to identify the characteristics of schizophrenia -related brain deterioration, which provides novel insights into schizophrenia diagnosis and prediction.

Tropical tall forests are more sensitive and vulnerable to drought than short forests - Liyang Liu; Xiuzhi Chen; Philippe Ciais; Wenping Yuan; Fabienne Maignan; Jin Wu; Shilong Piao; Ying‐Ping Wang; Jean‐Pierre Wigneron; Lei Fan; Pierre Gentine; Xueqin Yang; et al. (Global Change Biology, 2022)
Our limited understanding of the impacts of drought on tropical forests significantly impedes our ability in accurately predicting the impacts of climate change on this biome. Here, we investigated the impact of drought on the dynamics of forest canopies with different heights using time‐series records of remotely sensed Ku‐band vegetation optical depth (Ku‐VOD), a proxy of top‐canopy foliar mass and water content, and separated the signal of Ku‐VOD changes into drought‐induced reductions and subsequent non‐drought gains. Both drought‐induced reductions and non‐drought increases in Ku‐VOD varied significantly with canopy height. Taller tropical forests experienced greater relative Ku‐VOD reductions during drought and larger non‐drought increases than shorter forests, but the net effect of drought was more negative in the taller forests. Meta‐analysis of in situ hydraulic traits supports the hypothesis that taller tropical forests are more vulnerable to drought stress due to smaller xylem‐transport safety margins. Additionally, Ku‐VOD of taller forests showed larger reductions due to increased atmospheric dryness, as assessed by vapor pressure deficit, and showed larger gains in response to enhanced water supply than shorter forests. Including the height‐dependent variation of hydraulic transport in ecosystem models will improve the simulated response of tropical forests to drought.

Constitutive expression of tyrosine phenol-lyase from Erwinia herbicola in Escherichia coli for l-DOPA production - Mengqing Tang; Yajun Bai; Tai-Ping Fan; Xiaohui Zheng; Yujie Cai (Systems Microbiology and Biomanufacturing, 2022)

A contribution to knowledge of Gyroporus (Gyroporaceae, Boletales) in China: three new taxa, two previous species, and one ambiguous taxon - Hui-Jing Xie; Li-Ping Tang; Man Mu; Yu-Guang Fan; Shuai Jiang; Ming-Sheng Su; Zhi-Qun Liang; Nian-Kai Zeng (Mycological Progress, 2022)

The combined toxicity and mechanism of multi-walled carbon nanotubes and nano zinc oxide toward the cabbage - Mo Hong; Ji-Lai Gong; Wei-Cheng Cao; Rong Fang; Zhe Cai; Jun Ye; Zeng-Ping Chen; Wang-Wang Tang (Environmental Science and Pollution Research, 2022)

A thermophile Hydrogenibacillus sp. strain efficiently degrades environmental pollutants polycyclic aromatic hydrocarbons - Xiaoyu Qiu; Weiwei Wang; Lige Zhang; Lihua Guo; Ping Xu; Hongzhi Tang (Environmental Microbiology, 2022)
Summary Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous pollutants threatening ecosystems and human health. Here, we isolated and characterized a new strain, Hydrogenibacillus sp. N12, which is a thermophilic PAH‐degrader. Strain N12 utilizes naphthalene as a sole carbon and energy source above 60°C and co‐metabolizes many other PAHs as well. The metabolites were identified in the catabolism of naphthalene by gas chromatography–mass spectrometry (GC–MS) and stable isotopic analysis. Based on the identified metabolites, we proposed two possible metabolic pathways, one via salicylic acid and the other via phthalic acid. Whole‐genome sequencing reveals that strain N12 possesses a small chromosome of 2.6 Mb. Combining genetic and transcriptional information, we reveal a new gene cluster for the naphthalene degradation. The genes, designated as nar AaAb that are predicted to encode the alpha and beta subunits of naphthalene dioxygenase, were subsequently subcloned into Escherichia coli and the enzyme activity was detected by whole‐cell transformation. Capacity to degrade several other tricyclic‐PAHs was also characterized, suggesting co‐existence of other constitutively expressed enzyme systems in strain N12 in addition to the naphthalene degradation gene cluster. Our study provides insights into the potential of the thermophilic PAH‐degrader in biotechnology and environmental management applications.

Isoquercitrin Upregulates Aldolase C Through Nrf2 to Ameliorate OGD/R-Induced Damage in SH-SY5Y Cells - Shi-Chang Cai; Chuan-An Yi; Xiang-Shang Hu; Gen-Yun Tang; Li-Ming Yi; Xiu-Ping Li (Neurotoxicity Research, 2021)

Stress response mechanisms and description of three novel species Shewanella avicenniae sp. nov., Shewanella sedimentimangrovi sp. nov. and Shewanella yunxiaonensis sp. nov., isolated from mangrove ecosystem - Guo-Hong Liu; Qi Zhang; Manik Prabhu Narsing Rao; Shang Yang; Rong Tang; Huai Shi; Jie-Ping Wang; Guan-Min Huang; Bo Liu; Shun-Gui Zhou; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

Cytotoxic triterpenoid glycosides from leaves of Cyclocarya paliurus - Hui-Hui Sun; Wen-Yan Lv; Jie Tan; Yu-Cheng Tang; Hui Zhu; Jian-Bo Qu; Jing Li; Jian-Ping Wu; Xi-Wen Chang; Zhi-Chun Yang; Wen-Xuan Wang; Zu-Hui Chen; et al. (Natural Product Research, 2021)

Heat stress inhibits TLR4-NF-κB and TLR4-TBK1 signaling pathways in broilers infected with Salmonella Typhimurium - Wei-Hao Li; Yi-Lei Liu; Jian-Chi Lun; Yong-Ming He; Lu-Ping Tang (International Journal of Biometeorology, 2021)
With the global warming, the harm of heat stress (HS) to the breeding industry has become more common, which causes the decline of animal production performance and low immunity. This study aimed to analyze the effect of HS on the intestinal immune function of Salmonella- infected chickens. Fourteen-day-old broilers were divided into the following four groups of eight replicates: control (Control), heat stress (HS), Salmonella Typhimurium (ST), and heat stress + Salmonella Typhimurium (HS+ST). The broilers were subjected to a heat stress of 35 °C from 15 to 28 days of age. Salmonella Typhimurium (ST, 14028, 10 9 cfu/mL) was inoculated, via oral administration at 29 days of age, into ST and HS+ST group birds. On the 4th day after Salmonella Typhimurium administration, an increase in jejunum IgA levels was observed in chickens infected with Salmonella Typhimurium. Mechanistic regulation of TLR4-NFκB-NLRP3 and TLR4-TBK1 signaling by heat stress was evaluated in Salmonella Typhimurium–infected broilers. Heat stress markedly inhibited the expression of cytokines including TNF-α, IL-6, IL-1β, NLRP3, caspase-1, NF-κB-p65, and p-NF-κB-p65, and the TLR4-TBK1 cytokines IFN-α, IFN-γ, p-IRF3, and p-TBK1 in jejunum of broilers infected with Salmonella Typhimurium. Collectively, our results demonstrate that heat stress can inhibit intestinal immune response by downregulating the expression of TLR4-NFκB-NLRP3 and TLR4-TBK1 signaling pathways in broilers infected with Salmonella Typhimurium.

Association between ambient air pollution and multiple sclerosis: a systemic review and meta-analysis - Chao Tang; Qing-Ru Li; Yan-Mei Mao; Yuan-Rui Xia; Heng-Sheng Guo; Jun-Ping Wang; Zong-Wen Shuai; Dong-Qing Ye (Environmental Science and Pollution Research, 2021)

Qaidamihabitans albus gen. nov., sp. nov., a new member of the family Pseudonocardiaceae, and transfer of Prauserella shujinwangii to Qaidamihabitans gen. nov. as Qaidamihabitans shujinwangii comb. nov. - Li-Sha Tian; Gang-Qiang Jiang; Rui Li; Ping Ni; Chuan-En Li; Hong-Yan Zhang; Juan Wang; Xiao-Ping Zhang; Yun Wang; Shu-Kun Tang (Archives of Microbiology, 2021)

Dynamic evolution of eukaryotic mitochondrial and nuclear genomes: a case study in the gourmet pine mushroom Tricholoma matsutake - Shu Zhang; Xue Bai; Li‐Yuan Ren; Hui‐Hui Sun; Hui‐Ping Tang; Lu‐Min Vaario; Jianping Xu; Yong‐Jie Zhang (Environmental Microbiology, 2021)
Summary Fungi, as eukaryotic organisms, contain two genomes, the mitochondrial genome and the nuclear genome, in their cells. How the two genomes evolve and correlate to each other is debated. Herein, taking the gourmet pine mushroom Tricholoma matsutake as an example, we performed comparative mitogenomic analysis using samples collected from diverse locations and compared the evolution of the two genomes. The T. matsutake mitogenome encodes 49 genes and is rich of repetitive and non‐coding DNAs. Six genes were invaded by up to 11 group I introns, with one cox1 intron cox1P372 showing presence/absence dynamics among different samples. Bioinformatic analyses suggested limited or no evidence of mitochondrial heteroplasmy. Interestingly, hundreds of mitochondrial DNA fragments were found in the nuclear genome, with several larger than 500 nt confirmed by PCR assays and read count comparisons, indicating clear evidence of transfer of mitochondrial DNA into the nuclear genome. Nuclear DNA of T. matsutake showed a higher mutation rate than mitochondrial DNA. Furthermore, we found evidence of incongruence between phylogenetic trees derived from mitogenome and nuclear DNA sequences. Together, our results reveal the dynamic genome evolution of the gourmet pine mushroom.

The transferability of random forest and support vector machine for estimating daily global solar radiation using sunshine duration over different climate zones - Wei Wu; Mao-Fen Li; Xia Xu; Xiao-Ping Tang; Chao Yang; Hong-Bin Liu (Theoretical and Applied Climatology, 2021)

Community structure and abundance of comammox Nitrospira in Chongming eastern intertidal sediments - Dongyao Sun; Min Liu; Lijun Hou; Mengyue Zhao; Xiufeng Tang; Qiang Zhao; Jun Li; Ping Han (Journal of Soils and Sediments, 2021)

Carbon transfer from the submerged macrophyte Hydrilla verticillata to zooplankton: a 13C-labeled mesocosm study - Ling Su; Zongan Jin; Lichao Xie; Yali Tang; Zhengwen Liu; Ping Zhong; Yaling Su; Qiuqi Lin (Hydrobiologia, 2021)

A comprehensive analysis of gorilla-specific LINE-1 retrotransposons - Soyeon Jeon; Songmi Kim; Man Hwan Oh; Ping Liang; Wanxiangfu Tang; Kyudong Han (Genes & Genomics, 2021)

Geochemical characteristics of the lower Cambrian Qiongzhusi Formation in Huize area, east Yunnan: implications for paleo-ocean environment and the origin of black rock series - Yong Cheng; Weiqing Liu; Wei Wu; Yu Zhang; Guo Tang; Cong Liu; Qi Nie; Yiming Wen; Ping Lu; Chuanyu Zhang (Arabian Journal of Geosciences, 2021)

Anti-inflammatory steroids from the fruits of Artocarpus heterophyllus - Yun-Yao Liu; Ting Wang; Rong-Xiang Yang; Hao-Xuan Tang; Lei Qiang; Yan-Ping Liu (Natural Product Research, 2021)

Hygrophorus russula complex (Hygrophoraceae, Agaricales) in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Moreno Gabriel; Tie-Zhi Liu; Li-Ping Tang (Mycological Progress, 2021)

Insights from comparative proteomic analysis into degradation of phenanthrene and salt tolerance by the halophilic Martelella strain AD-3 - Xin Chen; Weiwei Wang; Haiyang Hu; Hongzhi Tang; Yongdi Liu; Ping Xu; Kuangfei Lin; Changzheng Cui (Ecotoxicology, 2021)

An experimental study on cutting tool hardness optimization for shield TBMs during dense fine silty sand ground tunneling - Xiao-Ping Zhang; Shao-Hui Tang; Quan-Sheng Liu; Xin-Bin Tu; Peng Chen; Fang-Yi Li (Bulletin of Engineering Geology and the Environment, 2021)

Association of gut microbiomes with lung and esophageal cancer: a pilot study - Weitao Shen; Derong Tang; Yali Deng; Huilin Li; Tian Wang; Ping Wan; Ran Liu (World Journal of Microbiology and Biotechnology, 2021)

Correction to: TIP60 recruits SUV39H1 to chromatin to maintain heterochromatin genome stability and resist hydrogen peroxide-induced cytotoxicity - Bo Tu; Yantao Bao; Ming Tang; Qian Zhu; Xiaopeng Lu; Hui Wang; Tianyun Hou; Ying Zhao; Ping Zhang; Wei-Guo Zhu (Genome Instability & Disease, 2021)

Simulation study on sectional ventilation of long-distance high-temperature roadway in mine - Ping Huang; Wei Huang; Yongliang Zhang; Shibin Tang (Arabian Journal of Geosciences, 2021)

The sub-inhibitory concentration of cinnamaldehyde resists Aeromonas hydrophila pathogenicity via inhibition of W-pili production - Ping Ouyang; Jiehao Chen; Lizi Yin; Yi Geng; Defang Chen; Kaiyu Wang; Weiming Lai; Hongrui Guo; Jing Fang; Zhengli Chen; Li Tang; Chao Huang; et al. (Aquaculture International, 2021)

Genetic mapping of highly versatile and solvent‐tolerant Pseudomonas putida B6 ‐2 ( ATCC BAA ‐2545) as a ‘superstar’ for mineralization of PAHs and dioxin‐like compounds - Weiwei Wang; Qinggang Li; Lige Zhang; Jie Cui; Hao Yu; Xiaoyu Wang; Xingyu Ouyang; Fei Tao; Ping Xu; Hongzhi Tang (Environmental Microbiology, 2021)
Summary Polycyclic aromatic hydrocarbons (PAHs) and dioxin‐like compounds, including sulfur, nitrogen and oxygen heterocycles, are widespread and toxic environmental pollutants. A wide variety of microorganisms capable of growing with aromatic polycyclic compounds are essential for bioremediation of the contaminated sites and the Earth's carbon cycle. Here, cells of Pseudomonas putida B6‐2 (ATCC BAA‐2545) grown in the presence of biphenyl (BP) are able to simultaneously degrade PAHs and their derivatives, even when they are present as mixtures, and tolerate high concentrations of extremely toxic solvents. Genetic analysis of the 6.37 Mb genome of strain B6‐2 reveals coexistence of gene clusters responsible for central catabolic systems of aromatic compounds and for solvent tolerance. We used functional transcriptomics and proteomics to identify the candidate genes associated with catabolism of BP and a mixture of BP, dibenzofuran, dibenzothiophene and carbazole. Moreover, we observed dynamic changes in transcriptional levels with BP, including in metabolic pathways of aromatic compounds, chemotaxis, efflux pumps and transporters potentially involved in adaptation to PAHs. This study on the highly versatile activities of strain B6‐2 suggests it to be a potentially useful model for bioremediation of polluted sites and for investigation of biochemical, genetic and evolutionary aspects of Pseudomonas .

Terpenoids from the South China Sea soft coral Sinularia multiflora - Zheng Wang; Ping-Lin Li; Xiang-Chao Luo; Qi Wang; Leen van Ofwegen; Xu-Li Tang; Guo-Qiang Li (Natural Product Research, 2021)

Comparative analysis of sRNAs, degradome and transcriptomics in sweet sorghum reveals the regulatory roles of miRNAs in Cd accumulation and tolerance - Weitao Jia; Kangqi Lin; Tengxue Lou; Juanjuan Feng; Sulian Lv; Ping Jiang; Ze Yi; Xuan Zhang; Duoliya Wang; Zijing Guo; Yetao Tang; Rongliang Qiu; et al. (Planta, 2021)

Evaluation of the differences between biofilm and planktonic Brucella abortus via metabolomics and proteomics - Taishan Tang; Ye Xu; Jianfeng Wang; Xiao Tan; Xiaona Zhao; Ping Zhou; Fande Kong; Changqing Zhu; Chengping Lu; Huixing Lin (Functional & Integrative Genomics, 2021)

Interactive effect of water level and flushing rate on population dynamics of a harmful cyanobacterial species: Raphidiopsis raciborskii - Quehui Tang; Lamei Lei; Li Zhao; Jiguang Gu; Lijuan Xiao; Bo-Ping Han (Ecotoxicology, 2021)

Application of an enhanced BP neural network model with water cycle algorithm on landslide prediction - Yong-gang Zhang; Jun Tang; Rao-ping Liao; Ming-fei Zhang; Yan Zhang; Xiao-ming Wang; Zheng-yang Su (Stochastic Environmental Research and Risk Assessment, 2021)

Ziziphus jujuba Mill., a plant used as medicinal food: a review of its phytochemistry, pharmacology, quality control and future research - Shi-Jun Liu; Yan-Ping Lv; Zhi-Shu Tang; Yu Zhang; Hong-Bo Xu; Dong-Bo Zhang; Chun-Li Cui; Hong-Bo Liu; Huan-Huan Sun; Zhong-Xing Song; Si-Min Wei (Phytochemistry Reviews, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Nutrigenomics reveals potential genetic underpinning of diverse taste preference of Chinese men - Zhouhai Zhu; Junpu Mei; Silong Sun; Sheming Lu; Meng Li; Ying Guan; Ying Chen; Yuqiong Xu; Tao Zhang; Fengxue Shi; Xuemei Li; Mingming Miao; et al. (Genes & Genomics, 2021)

Fast and accurate land-cover classification on medium-resolution remote-sensing images using segmentation models - Wei Zhang; Ping Tang; Lijun Zhao (International Journal of Remote Sensing, 2021)

Functional Differences Between Two Kv1.1 RNA Editing Isoforms: a Comparative Study on Neuronal Overexpression in Mouse Prefrontal Cortex - Liting Zhang; Zetong Peng; Wenjun Bian; Pingping Zhu; Bin Tang; Wei-Ping Liao; Tao Su (Molecular Neurobiology, 2021)

IMPERFECTIVE EXINE FORMATION (IEF) is required for exine formation and male fertility in Arabidopsis - Kaiqi Wang; Xin Zhao; Chaoting Pang; Sida Zhou; Xuexue Qian; Nan Tang; Naiying Yang; Ping Xu; Xiaofeng Xu; Jufang Gao (Plant Molecular Biology, 2021)

Spillover effect between carbon spot and futures market: evidence from EU ETS - Jian Liu; Shuai Tang; Chun-Ping Chang (Environmental Science and Pollution Research, 2021)

Lentibacillus saliphilus. sp. nov., a moderately halophilic bacterium isolated from a saltern in Korea - Yun Wang; Gang-Qiang Jiang; Hong-Ping Lin; Peng Sun; Hong-Yan Zhang; Dong-Mei Lu; Li-Yun Wang; Chang-Jin Kim; Shu-Kun Tang (Archives of Microbiology, 2021)

Identifying Accurate Crack Initiation and Propagation Thresholds in Siliceous Siltstone and Limestone - Xiao-Ping Zhang; Gen-Gen Lv; Quan-Sheng Liu; Shun-Chuan Wu; Qi Zhang; Pei-Qi Ji; Xu-Hai Tang (Rock Mechanics and Rock Engineering, 2021)

Differential response of microbial diversity and abundance to hydrological residual time and age in cascade reservoirs - Yihong Yue; Fushun Wang; Zhiwei Fu; Yi Tang; Jing Ma; Yong Qin; Meng Li; Ming Yang; Xue-Ping Chen (Journal of Soils and Sediments, 2021)

Correction to: Non-Invasive Multimodality Imaging Directly Shows TRPM4 Inhibition Ameliorates Stroke Reperfusion Injury - Bo Chen; Gandi Ng; Yahui Gao; See Wee Low; Edwin Sandanaraj; Boominathan Ramasamy; Sakthivel Sekar; Kishore Bhakoo; Tuck Wah Soong; Bernd Nilius; Carol Tang; Edward G. Robins; et al. (Translational Stroke Research, 2020)

N2O Emissions Mitigation in Acidic Soil Following Biochar Application Under Different Moisture Regimes - Muhammad Aamer; Muhammad Shaaban; Muhammad Umair Hassan; Liu Ying; Tang Haiying; Ma Qiaoying; Hassan Munir; Adnan Rasheed; Li Xinmei; Li Ping; Huang Guoqin (Journal of Soil Science and Plant Nutrition, 2020)

What Factors Control the Variations in Abundance, Biomass, and Size of Mesozooplankton in a Subtropical Eutrophic Bay? - Ping Du; Zhi B. Jiang; Yuan L. Zhu; Yan B. Tang; Yi B. Liao; Quan Z. Chen; Jiang N. Zeng; Lu Shou (Estuaries and Coasts, 2020)

Groundwater resources survey of tongchuan city using the audio magnetotelluric method - Zhi-min Xu; Jing-tian Tang; Guang Li; Hui-Cui Xin; Zhang-jian Xu; Xin-ping Tan; Jin Li (Applied Geophysics, 2020)

Population pharmacokinetics and dose optimization of ceftriaxone for children with community-acquired pneumonia - Muhammad Wasim Khan; Ya-Kun Wang; Yue-E Wu; Bo-Hao Tang; Min Kan; Hai-Yan Shi; Yi Zheng; Bao-Ping Xu; A-Dong Shen; Evelyne Jacqz-Aigrain; Li-Yuan Tian; Wei Zhao (European Journal of Clinical Pharmacology, 2020)

TIP60 recruits SUV39H1 to chromatin to maintain heterochromatin genome stability and resist hydrogen peroxide-induced cytotoxicity - Bo Tu; Yantao Bao; Ming Tang; Qian Zhu; Xiaopeng Lu; Hui Wang; Tianyun Hou; Ying Zhao; Ping Zhang; Wei-Guo Zhu (Genome Instability & Disease, 2020)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

Correction to: Evolutionary and recombination analysis of porcine reproductive and respiratory syndrome isolates in China - Zhendong Zhang; Xiangyang Qu; Hongliang Zhang; Xudong Tang; Ting Bian; Yingjun Sun; Mingming Zhou; Fubo Ren; Ping Wu (Virus Genes, 2020)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

Growth factor receptor bound protein-7 regulates proliferation, cell cycle, and mitochondrial apoptosis of thyroid cancer cells via MAPK/ERK signaling - Haili Tang; Ping Yang; Xiaojun Yang; Shujia Peng; Xi’e Hu; Guoqiang Bao (Molecular and Cellular Biochemistry, 2020)

Sandstorm weather is a risk factor for mortality in ischemic heart disease patients in the Hexi Corridor, northwestern China - Xinghui Li; Hui Cai; Xiaolan Ren; Jin He; Jia Tang; Ping Xie; Nan Wang; Fangfei Nie; Linfeng Lei; Chenchen Wang; Wenli Li; Jing Ma (Environmental Science and Pollution Research, 2020)

Production, safety, health effects and applications of diacylglycerol functional oil in food systems: a review - Yee-Ying Lee; Teck-Kim Tang; Eng-Tong Phuah; Chin-Ping Tan; Yong Wang; Ying Li; Ling-Zhi Cheong; Oi-Ming Lai (Critical Reviews in Food Science and Nutrition, 2020)

The dynamic process of dietary soybean β-conglycinin in digestion, absorption, and metabolism among different intestinal segments in grass carp (Ctenopharyngodon idella) - Xu-Dong Duan; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Jun Jiang; Bei-Ping Tan; Qi-Hui Yang; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

Brief report of the first cured 2019-nCoV pneumonia patient in West China Hospital - En-Qiang Chen; Li-Chun Wang; Guang-Min Tang; Yao Yang; Min-Jin Wang; Rong Deng; Fang Chen; Meng-Lan Wang; Ya-Chao Tao; Ping Feng; Hong Tang (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Species diversity and seasonal dynamics of filamentous cyanobacteria in urban reservoirs for drinking water supply in tropical China - Yang Yang; Xunhao Zheng; Quehui Tang; Jiguang Gu; Lamei Lei; Bo-Ping Han (Ecotoxicology, 2020)

Microseismic Monitoring to Characterize Structure-Type Rockbursts: A Case Study of a TBM-Excavated Tunnel - Quan-Sheng Liu; Jian Wu; Xiao-Ping Zhang; Lie-Xian Tang; Chen Bi; Wei-Wei Li; Jin-Lin Xu (Rock Mechanics and Rock Engineering, 2020)

Evolutionary and recombination analysis of porcine reproductive and respiratory syndrome isolates in China - Zhendong Zhang; Xiangyang Qu; Hongliang Zhang; Xudong Tang; Ting Bian; Yingjun Sun; Mingming Zhou; Fubo Ren; Ping Wu (Virus Genes, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

The BIG gene controls size of shoot apical meristems in Arabidopsis thaliana - Wen Jie Zhang; Li Ming Zhai; Hai Xia Yu; Jing Peng; Shan Shan Wang; Xian Sheng Zhang; Ying Hua Su; Li Ping Tang (Plant Cell Reports, 2020)

Tenuazonic acid-induced change in volatile emission from rose plants and its chemometrical analysis - Fa-zhong Yang; Yun-xian Li; Min Tang; Guo-lei Zhu; Shi-ping Zhou; Bin Yang (Journal of Plant Diseases and Protection, 2020)

The enhancement of NH3-SCR performance for CeO2 catalyst by CO pretreatment - Ping Zhang; Rui-tang Guo; Li-jun Wu; Wei-guo Pan (Environmental Science and Pollution Research, 2020)

Biodegradation of microcystin-RR and nutrient pollutants using Sphingopyxis sp. YF1 immobilized activated carbon fibers-sodium alginate - Guofeng Ren; Xinghou He; Pian Wu; Yayuan He; Yong Zhang; Shibiao Tang; Xinli Song; Yafei He; Yuandan Wei; Ping Ding; Fei Yang (Environmental Science and Pollution Research, 2020)

Effects of Organic Copper on Growth Performance and Oxidative Stress in Mice - Mingyu Zhi; Ping Tang; Ying Liu; Da He; Suxia Zheng (Biological Trace Element Research, 2020)

Outbreak of carp edema virus disease in cultured ornamental koi in a lower temperature in China - Ping Ouyang; Yaojia Zhou; Ruixue Yang; Zhuangzhi Yang; Kaiyu Wang; Yi Geng; Weiming Lai; Xiaoli Huang; Defang Chen; Jing Fang; Zhengli Chen; Li Tang; et al. (Aquaculture International, 2020)

Animal models of transient ischemic attack: a review - Jiahui Wang; Ping Zhang; Zhouping Tang (Acta Neurologica Belgica, 2020)
Transient ischemic attack (TIA) is defined as a brief episode of neurological dysfunction caused by focal cerebral ischemia. TIA is a critical early warning signal of stroke. Patients with TIA may have long-term cognitive decline. The pathogenesis and pathological changes of TIA have not been fully elucidated. Animal models can simulate the process of human diseases and are essential tools to investigate injury mechanisms and therapeutic approaches of TIA. Most TIA animal models are based on ischemic stroke models and the definition of TIA. Each model has unique strengths and weaknesses. The establishment of a successful and reliable TIA model should follow three criteria: (1) objective evidence of cerebral arteries occlusion and reperfusion, (2) no permanent neurological deficit, and (3) no acute cerebral infarction. However, experimental animal models are impossible to be completely consistent with human TIA, because TIA itself is a heterogeneous disease. In the present review, the selection of animals, methodological development, and evaluation of cerebral blood flow of animal models of TIA are comprehensively evaluated.

Microbial dynamics and soil physicochemical properties explain large‐scale variations in soil organic carbon - Haicheng Zhang; Daniel S. Goll; Ying‐Ping Wang; Philippe Ciais; William R. Wieder; Rose Abramoff; Yuanyuan Huang; Bertrand Guenet; Anne‐Katrin Prescher; Raphael A. Viscarra Rossel; Pierre Barré; Claire Chenu; et al. (Global Change Biology, 2020)
First‐order organic matter decomposition models are used within most Earth System Models (ESMs) to project future global carbon cycling; these models have been criticized for not accurately representing mechanisms of soil organic carbon (SOC) stabilization and SOC response to climate change. New soil biogeochemical models have been developed, but their evaluation is limited to observations from laboratory incubations or few field experiments. Given the global scope of ESMs, a comprehensive evaluation of such models is essential using in situ observations of a wide range of SOC stocks over large spatial scales before their introduction to ESMs. In this study, we collected a set of in situ observations of SOC, litterfall and soil properties from 206 sites covering different forest and soil types in Europe and China. These data were used to calibrate the model MIMICS (The MIcrobial‐MIneral Carbon Stabilization model), which we compared to the widely used first‐order model CENTURY. We show that, compared to CENTURY, MIMICS more accurately estimates forest SOC concentrations and the sensitivities of SOC to variation in soil temperature, clay content and litter input. The ratios of microbial biomass to total SOC predicted by MIMICS agree well with independent observations from globally distributed forest sites. By testing different hypotheses regarding (using alternative process representations) the physicochemical constraints on SOC deprotection and microbial turnover in MIMICS, the errors of simulated SOC concentrations across sites were further decreased. We show that MIMICS can resolve the dominant mechanisms of SOC decomposition and stabilization and that it can be a reliable tool for predictions of terrestrial SOC dynamics under future climate change. It also allows us to evaluate at large scale the rapidly evolving understanding of SOC formation and stabilization based on laboratory and limited filed observation.

Cytotoxic components from the Xisha sponge Fascaplysinopsis reticulata - Guo-Fei Qin; Xu-Li Tang; Nicole J. de Voogd; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2020)

Marchenko imaging based on self-adaptive traveltime updating - Xiao-Chun Chen; Ye-Zheng Hu; Xu-Ri Huang; Hou-Zhu Zhang; Wei-Ping Cao; Yun-Gui Xu; Jing Tang (Applied Geophysics, 2020)

Molecular characterization of the Krüppel-homolog 1 and its role in ovarian development in Sogatella furcifera (Hemiptera: Delphacidae) - Kui Hu; Ping Tian; Lu Yang; Yan Tang; Lin Qiu; Hualiang He; Wenbing Ding; Youzhi Li (Molecular Biology Reports, 2020)

In vitro antifungal activity of dimethyl trisulfide against Colletotrichum gloeosporioides from mango - Lihua Tang; Jianyou Mo; Tangxun Guo; Suiping Huang; Qili Li; Ping Ning; Tom Hsiang (World Journal of Microbiology and Biotechnology, 2020)

Research on Application of Transient Electromagnetic Method in Hydraulic Fracturing - Dong-ming Zhang; Han Yang; Zi Rao; Zhong-yu Ou; Ping Tang (Geotechnical and Geological Engineering, 2020)

Risk profiling using metabolomic characteristics for susceptible individuals of drug-induced liver injury caused by Polygonum multiflorum - Le Zhang; Ming Niu; Ai-wu Wei; Jin-fa Tang; Can Tu; Zhao-fang Bai; Zheng-sheng Zou; Xiao-he Xiao; You-ping Liu; Jia-bo Wang (Archives of Toxicology, 2020)

Synthesis and biological evaluation of C-13, C-14 modified taxane analogues from 1-deoxybaccatin VI - Ping Tang; Hai-Xia Lin; Tian-Hai Yuan; Yong-Mei Cui (Natural Product Research, 2019)

Carbazole alkaloids from Clausena emarginata with their potential antiproliferative activities - Yan-Hui Fu; Yan-Lei Ma; Gui Yan; Qing Wen; Shi Hu; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Ping Liu (Natural Product Research, 2019)

Inositol as a new enhancer for improving lipid production and accumulation in Schizochytrium sp. SR21 - Zhao-Xin Liu; Shuai You; Bin-Ping Tang; Bo Wang; Sheng Sheng; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2019)

On the rapid intensification for Typhoon Meranti (2016): convection, warm core, and heating budget - Xiba Tang; Fan Ping; Shuai Yang; Mengxia Li; Jing Peng (Frontiers of Earth Science, 2019)

HprK Xcc is a serine kinase that regulates virulence in the Gram‐negative phytopathogen Xanthomonas campestris - Rui‐Fang Li; Ping Cui; Ping‐Zhen Wei; Xing‐Yan Liu; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2019)
Summary The HprK serine kinase is a component of the phosphoenolpyruvate phosphotransferase system (PTS) of bacteria that generally regulates catabolite repression through phosphorylation/dephosphorylation of the PTS protein PtsH at a conserved serine residue. However, many bacteria do not encode a complete PTS or even have an HprK homologue. Xanthomonas campestris pv. campestris ( Xcc ) is a pathogen that cause black rot disease in crucifer plants and one of the few Gram‐negative bacteria that encodes a homologue of HprK protein (herein HprK Xcc ). To gain insight into the role of HprK Xcc and other PTS‐related components in Xcc we individually mutated and phenotypically assessed the resulting strains. Deletion of hprK Xcc demonstrated its requirement for virulence and other diverse cellular processes associated including extracellular enzyme activity, extracellular‐polysaccharide production and cell motility. Global transcriptome analyses revealed the HprK Xcc had a broad regulatory role in Xcc . Additionally, through overexpression, double gene deletion and transcriptome analysis we demonstrated that hprK Xcc shares an epistatic relationship with ptsH . Furthermore, we demonstrate that HprK Xcc is a functional serine kinase, which has the ability to phosphorylate PtsH. Taken together, the data illustrates the previously unappreciated global regulatory role of HprK Xcc and previously uncharacterized PTS components that control virulence in this pathogen.

First report of sheath rot caused by Fusarium proliferatum on Pisang Awak Banana (Musa ABB) in China - Sui-Ping Huang; Ji-Guang Wei; Tang-Xun Guo; Qi-Li Li; Li-Hua Tang; Jian-You Mo; Ji-Feng Wei; Xiao-Bing Yang (Journal of Plant Pathology, 2019)

Two new 5,6-epoxysterols from calcareous marine sponge Leucetta chagosensis - Wei-Zhuo Tang; Zhong-Zhen Yang; Fan Sun; Shu-Ping Wang; Fan Yang; Wei-Hua Jiao; Hou-Wen Lin (Natural Product Research, 2019)

Synthesis and antitumor evaluation of novel fused heterocyclic 1,2,4-triazolo[3,4-b]-1,3,4-thiadiazole derivatives - Xiao-Jia Liu; Hai-Ying Liu; Hai-Xin Wang; Yan-Ping Shi; Rui Tang; Shuai Zhang; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

Furanocoumarins with potential antiproliferative activities from Clausena lenis - Yan-Ping Liu; Qing Wen; Shi Hu; Yan-Lei Ma; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Hui Fu; Shen-Xiang Qiu (Natural Product Research, 2019)

Expression, Purification and Characterization of a Novel Antimicrobial Peptide: Gloverin A2 from Bombyx mori - Guoqi Su; Feng Tang; Daiwen Chen; Bing Yu; Zhiqing Huang; Yuheng Luo; Xiangbing Mao; Ping Zheng; Jie Yu; Junqiu Luo; Jun He (International Journal of Peptide Research and Therapeutics, 2019)

Anti-secretogranin III therapy of oxygen-induced retinopathy with optimal safety - Fen Tang; Michelle E. LeBlanc; Weiwen Wang; Dan Liang; Ping Chen; Tsung-Han Chou; Hong Tian; Wei Li (Angiogenesis, 2019)

Expression and characterization of two chitinases with synergistic effect and antifungal activity from Xenorhabdus nematophila - Jia Liu; Ziyan NanGong; Jie Zhang; Ping Song; Yin Tang; Yue Gao; Qinying Wang (World Journal of Microbiology and Biotechnology, 2019)

Suppression of Fusarium wilt of banana by combining acid soil ameliorant with biofertilizer made from Bacillus velezensis H-6 - Jianfeng Huang; Yuwan Pang; Fabao Zhang; Qiaoyi Huang; Mu Zhang; Shuanhu Tang; Hongting Fu; Ping Li (European Journal of Plant Pathology, 2019)

A comprehensive analysis of the Baboon-specific full-length LINE-1 retrotransposons - Wooseok Lee; Minhoon Choi; Songmi Kim; Wanxiangfu Tang; Dong Hee Kim; Heui-Soo Kim; Ping Liang; Kyudong Han (Genes & Genomics, 2019)

Land-cover classification from multiple classifiers using decision fusion based on the probabilistic graphical model - Zhao Bian; Ping Tang; Jun Yan (International Journal of Remote Sensing, 2019)

New isolates from leaves of Nicotiana tabacum and their biological activities - Shanzhai Shang; Jianlian Shi; Jianguo Tang; Juxing Jiang; Wei Zhao; Xudong Zheng; Ping Lei; Jingmei Han; Chengya Wang; Dalin Yuan; Guangyu Yang; Yongkuan Chen; et al. (Natural Product Research, 2019)

Hydrogen Sulfide Inhibits Formaldehyde-Induced Senescence in HT-22 Cells via Upregulation of Leptin Signaling - Wei-Wen Zhu; Min Ning; Yi-Zhu Peng; Yi-Yun Tang; Xuan Kang; Ke-Bin Zhan; Wei Zou; Ping Zhang; Xiao-Qing Tang (NeuroMolecular Medicine, 2019)

Photosynthetic activity of Prorocentrum donghaiense Lu acclimated to phosphorus limitation and its photosynthetic responses to nutrient depletion - Kai-Ming Sun; Ming Xin; Ping Sun; Yan Li; Ruixiang Li; Xuexi Tang; Zongling Wang (Journal of Applied Phycology, 2019)

Potential effects of exploiting the Yunfu pyrite mine (southern China) on soil: evidence from analyzing trace elements in surface soil - Zhi-hua Tang; Ting-ping Ouyang; Ming-kun Li; Ning-sheng Huang; Yao-qiu Kuang; Qiao Hu; Zhao-yu Zhu (Environmental Monitoring and Assessment, 2019)

The Tibetan Plateau Surface-Atmosphere Coupling System and Its Weather and Climate Effects: The Third Tibetan Plateau Atmospheric Science Experiment - Ping Zhao; Yueqing Li; Xueliang Guo; Xiangde Xu; Yimin Liu; Shihao Tang; Wenming Xiao; Chunxiang Shi; Yaoming Ma; Xing Yu; Huizhi Liu; La Jia; et al. (Journal of Meteorological Research, 2019)

Epidemiological trends and virological traits of hepatitis B virus infection in pregnant women and neonates - Ting-Ting Peng; Qiu-E Cai; Min Yang; Shao-Ping Chen; Feng Chen; Miao Wang; Ling Peng; Gary Wong; Chen-Guang Shen; Wen-Bing Cheng; Sai-Yun Liu; Ya-Bai Peng; et al. (Archives of Virology, 2019)

Structurally diverse diterpenoids from Trigonostemon howii - Yan-Ping Liu; Qing Wen; Shi Hu; Yan-Lei Ma; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Hui Fu (Natural Product Research, 2019)

Experimental and Numerical Study on the Damage Evolution of Random Rock Joint Surface During Direct Shear Under CNL Condition - Wenchen Fan; Ping Cao; Guodong Tang (Geotechnical and Geological Engineering, 2019)

Toxicological effects benzotriazole to the marine scallop Chlamys nobilis: a 2-month exposure study - Tang-tian He; Tao Zhang; Shi-bo Liu; Jing-chun Shi; Yi-sheng Huang; Huai-ping Zheng; Wen-hua Liu (Environmental Science and Pollution Research, 2019)

Enhanced water solubility, antioxidant activity, and oral absorption of hesperetin by D-α-tocopheryl polyethylene glycol 1000 succinate and phosphatidylcholine - Su-Fang Gu; Li-Ying Wang; Ying-Jie Tian; Zhu-Xian Zhou; Jian-Bin Tang; Xiang-Rui Liu; Hai-Ping Jiang; You-Qing Shen (Journal of Zhejiang University-SCIENCE B, 2019)

Non-Invasive Multimodality Imaging Directly Shows TRPM4 Inhibition Ameliorates Stroke Reperfusion Injury - Bo Chen; Gandi Ng; Yahui Gao; See Wee Low; Edwin Sandanaraj; Boominathan Ramasamy; Sakthivel Sekar; Kishore Bhakoo; Tuck Wah Soong; Bernd Nilius; Carol Tang; Edward G. Robins; et al. (Translational Stroke Research, 2019)
The transient receptor potential melastatin 4 (TRPM4) channel has been suggested to play a key role in the treatment of ischemic stroke. However, in vivo evaluation of TRPM4 channel, in particular by direct channel suppression, is lacking. In this study, we used multimodal imaging to assess edema formation and quantify the amount of metabolically functional brain salvaged after a rat model of stroke reperfusion. TRPM4 upregulation in endothelium emerges as early as 2 h post-stroke induction. Expression of TRPM4 channel was suppressed directly in vivo by treatment with siRNA; scrambled siRNA was used as a control. T2-weighted MRI suggests that TRPM4 inhibition successfully reduces edema by 30% and concomitantly salvages functionally active brain, measured by 18 F-FDG-PET. These in vivo imaging results correlate well with post-mortem 2,3,5-triphenyltetrazolium chloride (TTC) staining which exhibits a 34.9% reduction in infarct volume after siRNA treatment. Furthermore, in a permanent stroke model, large areas of brain tissue displayed both edema and significant reductions in metabolic activity which was not shown in transient models with or without TRPM4 inhibition, indicating that tissue salvaged by TRPM4 inhibition during stroke reperfusion may survive. Evans Blue extravasation and hemoglobin quantification in the ipsilateral hemisphere were greatly reduced, suggesting that TRPM4 inhibition can improve BBB integrity after ischemic stroke reperfusion. Our results support the use of TRPM4 blocker for early stroke reperfusion.

Coexpression of FOXK1 and vimentin promotes EMT, migration, and invasion in gastric cancer cells - Hui Zhang; Xiaosheng Wu; Yizhi Xiao; Liqing Wu; Ying Peng; Weimei Tang; Guangnan Liu; Yong Sun; Jing Wang; Huiqiong Zhu; Mengwei Liu; Wenjing Zhang; et al. (Journal of Molecular Medicine, 2019)

The effects of ethoxyquin and Angelica sinensis extracts on lipid oxidation in fish feeds and growth, digestive and absorptive capacities and antioxidant status in juvenile red carp (Cyprinus carpio var. xingguonensis): a comparative study - HuaTao Li; SiYi Tang; WenHao Du; Jun Jiang; PeiYuan Peng; Ping Yuan; YiHong Liao; Jiao Long; SiShun Zhou (Fish Physiology and Biochemistry, 2019)

EGb761 improves the cognitive function of elderly db/db−/− diabetic mice by regulating the beclin-1 and NF-κB signaling pathways - Zhu-Fei Guan; Xiao-Ming Zhang; Ying-Hong Tao; Yu Zhang; Yan-Yan Huang; Gang Chen; Wei-Jun Tang; Gang Ji; Qi-Lin Guo; Ming Liu; Qian Zhang; Na-Na Wang; et al. (Metabolic Brain Disease, 2018)

The impact of GJA8 SNPs on susceptibility to age-related cataract - Xiaoning Yu; Xiyuan Ping; Xin Zhang; Yilei Cui; Hao Yang; Xiajing Tang; Yelei Tang; Xingchao Shentu (Human Genetics, 2018)

Photosynthetic response of Scirpus validus and Typha orientalis to elevated temperatures in Dianchi Lake, Southwestern China - Jun-ping Xu; Mei Sun; Hang Wang; Yun Zhang; Xiao-tang Zhang; Kun Tian (Journal of Mountain Science, 2018)

Auditory sensitivity exhibits sexual dimorphism and seasonal plasticity in music frogs - Ping Yang; Fei Xue; Jianguo Cui; Steven E. Brauth; Yezhong Tang; Guangzhan Fang (Journal of Comparative Physiology A, 2018)

Anaerobic oxidation of methane coupled to denitrification: fundamentals, challenges, and potential - Hyung-Sool Lee; Youneng Tang; Bruce E. Rittmann; He-Ping Zhao (Critical Reviews in Environmental Science and Technology, 2018)

DEM generation using Ziyuan-3 mapping satellite imagery without ground control points - Ping Zhou; Xinming Tang; Li Guo; Xia Wang; Wenfeng Fan (International Journal of Remote Sensing, 2018)

Preparation and application of magnetic nitrogen-doped rGO for persulfate activation - Ya Pang; Kun Luo; Lin Tang; Xue Li; Yong Song; Cheng-yong Li; Li-ping Wang (Environmental Science and Pollution Research, 2018)

A new polyoxygenated cyclohexene derivative from Artabotrys hainanensis - Jin-Ying Tang; Yan-Ping Liu; Peng-Kun Ju; Xiu-Lan Luo; Zhi-Jie Zhang; Peng Ren; Liang Lai; Guang-Ying Chen; Yan-Hui Fu (Natural Product Research, 2018)

Variability of aerosol optical thickness in the tropical Indian Ocean and South China Sea during spring intermonsoon season - Qingyang Sun; DanLing Tang; Gad Levy; Ping Shi (International Journal of Remote Sensing, 2018)

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Transcriptome analysis of wheat seedling and spike tissues in the hybrid Jingmai 8 uncovered genes involved in heterosis - Yong-jie Liu; Shi-qing Gao; Yi-miao Tang; Jie Gong; Xiao Zhang; Yong-bo Wang; Li-ping Zhang; Ren-wei Sun; Quan Zhang; Zhao-bo Chen; Xiang Wang; Cai-juan Guo; et al. (Planta, 2018)

BDNF/TrkB Pathway Mediates the Antidepressant-Like Role of H2S in CUMS-Exposed Rats by Inhibition of Hippocampal ER Stress - Le Wei; Li-Yuan Kan; Hai-Ying Zeng; Yi-Yun Tang; Hong-Lin Huang; Ming Xie; Wei Zou; Chun-Yan Wang; Ping Zhang; Xiao-Qing Tang (NeuroMolecular Medicine, 2018)

MicroRNA Profiling in Aging Brain of PSEN1/PSEN2 Double Knockout Mice - Suji Ham; Tae Kyoo Kim; Sangjoon Lee; Ya-Ping Tang; Heh-In Im (Molecular Neurobiology, 2018)

Protein-bounded uremic toxin p-cresylsulfate induces vascular permeability alternations - Wei-Hua Tang; Chao-Ping Wang; Teng-Hung Yu; Pei-Yang Tai; Shih-Shin Liang; Wei-Chin Hung; Cheng-Ching Wu; Sung-Hao Huang; Yau-Jiunn Lee; Shih-Chieh Chen (Histochemistry and Cell Biology, 2018)

Lower Es3 in Zhanhua Sag, Jiyang Depression: a case study for lithofacies classification in lacustrine mud shale - Jian-Ping Yan; Xu He; Qin-Hong Hu; Qiang Liang; Hong-Ming Tang; Chun-Zhen Feng; Bin Geng (Applied Geophysics, 2018)

Recent advances in the development of polycyclic skeletons via Ugi reaction cascades - Jie Lei; Jiang-Ping Meng; Dian-Yong Tang; Brendan Frett; Zhong-Zhu Chen; Zhi-Gang Xu (Molecular Diversity, 2018)

Evolutionary relationships of two balitorids (Cypriniformes, Balitoridae) revealed by comparative mitogenomics - Li‐Xia Shi; Chen Zhang; Yin‐Ping Wang; Qiong‐Ying Tang; Patrick D. Danley; Huan‐Zhang Liu (Zoologica Scripta, 2018)
Balitoridae, a family within the Cypriniformes, inhabit torrential mountain streams in Asia. Although they have long fascinated ichthyologists for their numerous adaptations to this tumultuous environment, the evolutionary history of this group remains poorly understood. In this study, we investigate the evolutionary relationships of the balitorids with particular attention to the phylogenetic placement of two balitorid species, Yaoshania pachychulis and Erromyzon kalotaenia . Both species have extremely limited distributions, they are limited to Mt. Dayaoshan of the Pearl River in China and require dedicated conservation plans. However, little is known about their evolutionary relationships to other balitorids. Here, we examined the evolutionary relationships of Y. pachychulis and E. kalotaenia to each other and other balitorids through sequencing the complete mitochondrial genomes of nine balitorid individuals. For the newly sequenced balitorids, the length of the whole mitogenome, gene arrangement and their base composition are similar to those of other bony fishes. Analyses based on these newly sequenced mitogenomes and an additional 50 previously published mitogenomes show that Y. pachychulis and E. kalotaenia cluster as different clade within the subfamily Gastromyzontinae. The genetic distance between these two species ranges from 0.127 ± 0.003 to 0.132 ± 0.004 which is slightly higher than that between some genera (e.g. the distance between Vanmanenia and Metahomaloptera is 0.127 ± 0.004). Therefore, it is reasonable to assign Y. pachychulis and E. kalotaenia to different genera. Phylogenetic signal assessment suggested that ND 1 , ND 4 and ND 5 genes as well as their concatenated subsets perform relatively well in reconstructing the Cobitoidea phylogeny. The divergence time estimation indicated that the balitorids distributed in Mt. Dayaoshan might have originated and evolved following the flattening and uplifting of the Yunnan–Guizhou Plateau during the late Miocene to late Pliocene.

Geochemistry of uranium in Chinese coals and the emission inventory of coal-fired power plants in China - Jian Chen; Ping Chen; Duoxi Yao; Wenhui Huang; Shuheng Tang; Kejian Wang; Wenzhong Liu; Youbiao Hu; Qingguang Li; Ruwei Wang (International Geology Review, 2018)

HpaP, a novel regulatory protein with ATPase and phosphatase activity, contributes to full virulence in Xanthomonas campestris pv. campestris - Ping Cui; Rui‐Fang Li; Da‐Pei Zhang; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2018)
Summary The ability of the bacterial phytopathogen Xanthomonas campestris pv. campestris ( Xcc ) to cause disease is dependent on the type III secretion system (T3SS). Proteins of the Xcc T3SS are encoded by hrp (hypersensitive response and pathogenicity) genes and whose expression is mainly controlled by the regulators HrpG and HrpX. Here, we describe the identification and characterization of a previously unknown regulatory protein ( named HpaP), which plays important role in hrp gene expression and virulence in Xcc . Clean deletion of hpaP demonstrated reduced virulence and HR (hypersensitive response) induction of Xcc and alterations in cell motility and stress tolerance. Global transcriptome analyses revealed that most hrp genes were down regulated in the hpaP mutant, suggesting HpaP positively regulates hrp genes. GUS activity assays implied that HpaP regulates the expression of hrp genes via controlling the expression of hrpX . Biochemical analyses revealed that HpaP protein had both ATPase and phosphatase activity. While further site‐directed mutagenesis of conserved residues in the PTP loop (a protein tyrosine phosphatase signature) of HpaP resulted in the loss of both phosphatase activity and regulatory activity in virulence and HR. Taken together, the findings identify a new regulatory protein that controls hrp gene expression and virulence in Xcc .

The effect of electron competition on chromate reduction using methane as electron donor - Pan-Long Lv; Liang Zhong; Qiu-Yi Dong; Shi-Lei Yang; Wei-Wei Shen; Quan-Song Zhu; Chun-Yu Lai; An-Cheng Luo; Youneng Tang; He-Ping Zhao (Environmental Science and Pollution Research, 2018)

EGb761 Ameliorates Neuronal Apoptosis and Promotes Angiogenesis in Experimental Intracerebral Hemorrhage via RSK1/GSK3β Pathway - Chao Pan; Na Liu; Ping Zhang; Qian Wu; Hong Deng; Feng Xu; Lifei Lian; Qiming Liang; Yang Hu; Suiqiang Zhu; Zhouping Tang (Molecular Neurobiology, 2018)

Synthesis and biological evaluation of novel A-seco-taxoids derived from 1-deoxybaccatin VI - Wei-Qing Qiu; Yong-Mei Cui; Ping Tang; Yuan-You Qiu; Hai-Xia Lin (Natural Product Research, 2018)

Impact of urban water system treatment on the surrounding residential land price - Ji-wei Zhu; Bo Chen; Ping Lu; Jian-lin Liu; Gang Tang (Arabian Journal of Geosciences, 2018)

The Effects of Soil Drying on the Growth of a Dominant Peatland Species, Carex lasiocarpa - Jihong Yuan; Ping Wang; Jacob Weiner; Hongfeng Bian; Zhanhui Tang; Lianxi Sheng (Wetlands, 2017)

Metal-based proteasomal deubiquitinase inhibitors as potential anticancer agents - Xin Chen; Qianqian Yang; Lu Xiao; Daolin Tang; Q. Ping Dou; Jinbao Liu (Cancer and Metastasis Reviews, 2017)

Effects of virus infection on plant growth, root development and phytohormone levels in in vitro-cultured pear plants - Jie Chen; Hui-Hui Tang; Liu Li; Shi-Jiao Qin; Guo-Ping Wang; Ni Hong (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Generation and Screening of T-DNA Insertion Mutants Mediated by Agrobacterium tumefaciens in the Garden Asparagus Stem Blight Pathogen Phomopsis asparagi - Yueping Zhang; Huaxiang Qu; Ping Zhao; Yongping Tang; Jingsong Zhou; Shaochun Luo; Yuling Yin; Guangyu Chen (Current Microbiology, 2017)

Gracilibacillus aidingensis sp. nov., a novel moderately halophilic bacterium isolated from Aiding salt lake - Tong-Wei Guan; Lei Tian; En-Yuan Li; Shu-Kun Tang; Xiao-Ping Zhang (Archives of Microbiology, 2017)

Olivibacter flavus sp. nov., a novel endophytic bacterium isolated from the root of Camellia sinensis - Lei Tian; Tong-Wei Guan; Ling-Ling Yang; Kai-Yang Lu; Bing-Bing Liu; Wei-Xun ChunYu; Min Yin; En-Yuan Li; Yang Ji; Xiao-Ping Zhang; Shu-Kun Tang (Archives of Microbiology, 2017)

Glycomyces xinjiangensis sp. nov., a novel actinomycete isolated from a hypersaline habitat - Tong-Wei Guan; Hui-Ping Xiang; Peng-Hao Wang; Lei Tian; Shu-Kun Tang; Shun-Xian Zhao; Xi-Chao Zhang (Archives of Microbiology, 2017)

Two new phenolic glycosides from the stem of Zanthoxylum armatum DC - Tao Guo; Li-Ping Dai; Xiao-Feng Tang; Tong-Tong Song; Ya Wang; Ai-Hong Zhao; Ying-Ying Cao; Jun Chang (Natural Product Research, 2017)

Mapping stripe rust resistance gene YrZH22 in Chinese wheat cultivar Zhoumai 22 by bulked segregant RNA-Seq (BSR-Seq) and comparative genomics analyses - Yong Wang; Jingzhong Xie; Huaizhi Zhang; Bingmin Guo; Shunzong Ning; Yongxing Chen; Ping Lu; Qiuhong Wu; Miaomiao Li; Deyun Zhang; Guanghao Guo; Yan Zhang; et al. (Theoretical and Applied Genetics, 2017)

A low-complexity algorithm for fast acquisition of weak DSSS signal in high dynamic environment - Ping Tang; Shuai Wang; Xiangming Li; Zhike Jiang (GPS Solutions, 2017)

A new indole alkaloid with anti-inflammatory activity from Nauclea officinalis - Qing-Long Liu; A-Hong Chen; Jin-Ying Tang; Yan-Lei Ma; Zhi-Hua Jiang; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu; Wei Xu (Natural Product Research, 2017)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Behavioral responses of the egg parasitoid Trissolcus japonicus to volatiles from adults of its stink bug host, Halyomorpha halys - Yong-Zhi Zhong; Jin-Ping Zhang; Li-Li Ren; Rui Tang; Hai-Xia Zhan; Guo-Hua Chen; Feng Zhang (Journal of Pest Science, 2017)

Removal of Cu(II) Ions from Aqueous Solution by Magnetic Chitosan-Tripolyphosphate Modified Silica-Coated Adsorbent: Characterization and Mechanisms - Xu Jin; Kai Li; Ping Ning; Shuangyou Bao; Lihong Tang (Water, Air, & Soil Pollution, 2017)

Interleukin-18, matrix metalloproteinase-22 and -29 are independent risk factors of human coronary heart disease - Dong-Yi Jin; Cong-Lin Liu; Jun-Nan Tang; Zhao-Zhong Zhu; Xue-Xi Xuan; Xiao-Dan Zhu; Yun-Zhe Wang; Tian-Xia Zhang; De-Liang Shen; Xiao-Fang Wang; Guo-Ping Shi; Jin-Ying Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

A new monoterpenoid indole alkaloid from Ochrosia elliptica - A-Hong Chen; Qing-Long Liu; Yan-Lei Ma; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu; Wei Xu (Natural Product Research, 2017)

Fallow associated with autumn-plough favors structure stability and storage of soil organic carbon compared to continuous maize cropping in Mollisols - Shujie Miao; Yunfa Qiao; Ping Li; Xiaozeng Han; Caixian Tang (Plant and Soil, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Decoding early myelopoiesis from dynamics of core endogenous network - Hang Su; Gaowei Wang; Ruoshi Yuan; Junqiang Wang; Ying Tang; Ping Ao; Xiaomei Zhu (Science China Life Sciences, 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

Isoquercetin Ameliorates Cerebral Impairment in Focal Ischemia Through Anti-Oxidative, Anti-Inflammatory, and Anti-Apoptotic Effects in Primary Culture of Rat Hippocampal Neurons and Hippocampal CA1 Region of Rats - Cai-Ping Wang; Yun-Wei Shi; Miao Tang; Xiao-Chuan Zhang; Yun Gu; Xin-Miao Liang; Zhi-Wei Wang; Fei Ding (Molecular Neurobiology, 2017)

Clogging development and hydraulic performance of the horizontal subsurface flow stormwater constructed wetlands: a laboratory study - Ping Tang; Bohai Yu; Yongchao Zhou; Yiping Zhang; Jin Li (Environmental Science and Pollution Research, 2017)

Novel compound heterozygous mutations in ZAP70 in a Chinese patient with leaky severe combined immunodeficiency disorder - Qing Liu; Yan-Ping Wang; Qiao Liu; Qin Zhao; Xue-Mei Chen; Xiu-Hong Xue; Li-Na Zhou; Yuan Ding; Xue-Mei Tang; Xiao-Dong Zhao; Zhi-Yong Zhang (Immunogenetics, 2017)

Relationship between the morphological structure of floral nectaries and the formation, transport, and secretion of nectar in lychee - Xi-ping Ning; Tie-xin Tang; Hong Wu (Trees, 2017)

Naringenin ameliorates hypoxia/reoxygenation-induced endoplasmic reticulum stress-mediated apoptosis in H9c2 myocardial cells: involvement in ATF6, IRE1α and PERK signaling activation - Jia-You Tang; Ping Jin; Qing He; Lin-He Lu; Ji-Peng Ma; Wei-Lun Gao; He-Ping Bai; Jian Yang (Molecular and Cellular Biochemistry, 2017)

Effects of salinity on simultaneous reduction of perchlorate and nitrate in a methane-based membrane biofilm reactor - Yin Zhang; Jia-Xian Chen; Li-Lian Wen; Youneng Tang; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Comparative Pharmacokinetics of three major bioactive components in rats after oral administration of Typhae Pollen-Trogopterus Feces drug pair before and after compatibility - Huiting Zeng; Ping Xue; Shulan Su; Xiaochen Huang; Erxin Shang; Jianming Guo; Dawei Qian; Yuping Tang; Jin-ao Duan (DARU Journal of Pharmaceutical Sciences, 2016)

Heat, water and carbon exchanges in the tall megacity of Shanghai: challenges and results - Xiangyu Ao; C. S. B. Grimmond; Yuanyong Chang; Dongwei Liu; Yuqi Tang; Ping Hu; Yadong Wang; Jun Zou; Jianguo Tan (International Journal of Climatology, 2016)
The observed surface energy balance fluxes are essential to improve model forecasting ability but such data are scarce for subtropical cities and urban areas with tall buildings. One year of eddy covariance flux data for an area within Shanghai with a wide range of building heights (8–150 m, mean by direction) are analysed by wind direction. Consideration is given to how to distinguish between local‐ and micro‐scale fluxes. At the local‐scale, median daily peaks of sensible heat flux occur in the early afternoon (winter: 87 W m −2 , spring: 205 W m −2 , summer: 292 W m −2 , autumn: 135 W m −2 ). The latent heat flux is small in winter (median daily maxima 21 W m −2 ) and slightly larger in spring, summer and autumn (49, 65, 49 W m −2 , respectively). The monthly mean daytime Bowen ratio under all‐sky conditions ranges from 2 to 4.7. At this site, with predominately impervious surface (85% buildings/pavement, 14% vegetation), the enhancement of evaporation following rainfall usually lasts for about 12 h. Consistently larger Bowen ratios at the micro‐scale than the local‐scale are attributed to roughness effects and the impact of extensive areas of dry walls. The daily median CO 2 flux is dominated by traffic emissions, with two peaks associated with morning and evening rush hours. The data provide insights into urban surface controls on momentum, energy and carbon dynamics, with implications for urban planning strategies in the context of rapid global urbanization and climate change.

Preclinical Studies of Stem Cell Transplantation in Intracerebral Hemorrhage: a Systemic Review and Meta-Analysis - Yang Hu; Na Liu; Ping Zhang; Chao Pan; Youping Zhang; Yingxin Tang; Hong Deng; Miribanu Aimaiti; Ye Zhang; Houguang Zhou; Guofeng Wu; Zhouping Tang (Molecular Neurobiology, 2016)

Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2016)

A comparison of spatial interpolation methods for soil temperature over a complex topographical region - Wei Wu; Xiao-Ping Tang; Xue-Qing Ma; Hong-Bin Liu (Theoretical and Applied Climatology, 2016)

Curdlan blocks the immune suppression by myeloid-derived suppressor cells and reduces tumor burden - Ke Rui; Jie Tian; Xinyi Tang; Jie Ma; Ping Xu; Xinyu Tian; Yungang Wang; Huaxi Xu; Liwei Lu; Shengjun Wang (Immunologic Research, 2016)

STAT3 signal that mediates the neural plasticity is involved in willed-movement training in focal ischemic rats - Qing-ping Tang; Qin Shen; Li-xiang Wu; Xiang-ling Feng; Hui Liu; Bei Wu; Xiao-song Huang; Gai-qing Wang; Zhong-hao Li; Zun-jing Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Interaction between STAT3 gene polymorphisms and smoking on Crohn’s disease susceptibility: a case–control study in a Chinese Han population - Jun-hong Li; Ning Wu; Hong-mei Yang; Hong-bing Tang; Dong-ping Bao; Jun-min Ji (Inflammation Research, 2016)

Differential transcriptome analysis of leaves of tea plant (Camellia sinensis) provides comprehensive insights into the defense responses to Ectropis oblique attack using RNA-Seq - Ya-Nan Wang; Lei Tang; Yan Hou; Ping Wang; Hua Yang; Chao-Ling Wei (Functional & Integrative Genomics, 2016)

Enhanced short-cut nitrification in an airlift reactor by CaCO3 attachment on biomass under high bicarbonate condition - Mohammad Ali; Li-Yuan Chai; Hai-Ying Wang; Chong-Jian Tang; Xiao-Bo Min; Xu Yan; Cong Peng; Yu-Xia Song; Ping Zheng (Biodegradation, 2016)

Global patterns and substrate‐based mechanisms of the terrestrial nitrogen cycle - Shuli Niu; Aimée T. Classen; Jeffrey S. Dukes; Paul Kardol; Lingli Liu; Yiqi Luo; Lindsey Rustad; Jian Sun; Jianwu Tang; Pamela H. Templer; R. Quinn Thomas; Dashuan Tian; et al. (Ecology Letters, 2016)
Nitrogen (N) deposition is impacting the services that ecosystems provide to humanity. However, the mechanisms determining impacts on the N cycle are not fully understood. To explore the mechanistic underpinnings of N impacts on N cycle processes, we reviewed and synthesised recent progress in ecosystem N research through empirical studies, conceptual analysis and model simulations. Experimental and observational studies have revealed that the stimulation of plant N uptake and soil retention generally diminishes as N loading increases, while dissolved and gaseous losses of N occur at low N availability but increase exponentially and become the dominant fate of N at high loading rates. The original N saturation hypothesis emphasises sequential N saturation from plant uptake to soil retention before N losses occur. However, biogeochemical models that simulate simultaneous competition for soil N substrates by multiple processes match the observed patterns of N losses better than models based on sequential competition. To enable better prediction of terrestrial N cycle responses to N loading, we recommend that future research identifies the response functions of different N processes to substrate availability using manipulative experiments, and incorporates the measured N saturation response functions into conceptual, theoretical and quantitative analyses.

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

Ectomycorrhizae of Tuber huidongense and T. liyuanum with Castanea mollissima and Pinus armandii - Shan-Ping Wan; Fu-Qiang Yu; Li Tang; Ran Wang; Yun Wang; Pei-Gui Liu; Xiang-Hua Wang; Yi Zheng (Mycorrhiza, 2016)

The genome of Bacillus aryabhattai T61 reveals its adaptation to Tibetan Plateau environment - Yan Yan; Lei Zhang; MengYao Yu; Jian Wang; He Tang; ZhiWei Yang; Ping Wan (Genes & Genomics, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

bmo-miR-0001 and bmo-miR-0015 down-regulate expression of Bombyx mori fibroin light chain gene in vitro - Chen Chen; Yang-yang Fan; Xin Wang; Fei Song; Tao Jiang; Ping Qian; Shun-ming Tang; Xing-jia Shen (Journal of Zhejiang University-SCIENCE B, 2016)

Genetic variations in interleukin-12B in allergic rhinitis - Ping Wei; Wei Kou; Cheng Zhang; Houyong Kang; Hongbing Yao; Xinye Tang; Wu Wang (Immunologic Research, 2016)

The complete mitochondrial genome of fall armyworm Spodoptera frugiperda (Lepidoptera:Noctuidae) - Qiu-Ning Liu; Xin-Yue Chai; Dan-Dan Bian; Bao-Ming Ge; Chun-Lin Zhou; Bo-Ping Tang (Genes & Genomics, 2016)

The roles of methanogens and acetogens in dechlorination of trichloroethene using different electron donors - Li-Lian Wen; Yin Zhang; Ya-Wei Pan; Wen-Qi Wu; Shao-Hua Meng; Chen Zhou; Youneng Tang; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2015)

Dynamic Transcriptional Regulation of Fis in Salmonella During the Exponential Phase - Hui Wang; Lei Wang; Ping Li; Yilang Hu; Wei Zhang; Bo Tang (Current Microbiology, 2015)

An improved modeling of TDR signal propagation for measuring complex dielectric permittivity - Chih-Ping Lin; Shr-Hong Tang; Chun-Hung Lin; Chih-Chung Chung (Journal of Earth Science, 2015)

Application of the APACHE II score to assess the condition of patients with critical neurological diseases - Yi Bian; Ping Zhang; Yongjie Xiong; Feng Xu; Suiqiang Zhu; Zhouping Tang; Zheng Xue (Acta Neurologica Belgica, 2015)

Two new eunicellin diterpenoids from the South China Sea gorgonian Muricella sibogae and their bioactivities - Xing-Wang Zhang; Xu-Li Tang; Hong-Rui Yuan; Dan-Qing Feng; Pei Su; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2015)

Retraction Note to: Relationships between PON1 Q192R polymorphism and clinical outcome of antiplatelet treatment after percutaneous coronary intervention: a meta-analysis - Ping Li; Shu-Hong Bu; Xiao-Tong Lu; Li-Xia Li; A-Jing Xu; Yue-Nian Tang; Jian Zhang (Molecular Biology Reports, 2015)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

Deposition morphology of non-homogeneous debris flow and its energy characteristics - An-ping Shu; Chuan Tang; Xin Zhang; Song-dong Shao; Kai Yang (Journal of Mountain Science, 2015)

Improving forest type classification using the vegetation local difference index - Chenxin Chen; Zhao Bian; Shengyang Li; Ping Tang; Honggan Wu (International Journal of Remote Sensing, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

Characterization of mineralogy and surface zeta potential of atmospheric dust fall in northwest China - Fa-Qin Dong; Wu Chen; Qun-Wei Dai; Yue-Quan Deng; Ping He; Xiao-Chun He; Jun Tang; Li-Zhu Liu; Hua He (Mineralogy and Petrology, 2015)

The effect of Bt-transgene introgression on plant growth and reproduction in wild Brassica juncea - Yong-Bo Liu; Henry Darmency; C. Neal Stewart; Wei Wei; Zhi-Xi Tang; Ke-Ping Ma (Transgenic Research, 2015)

Airborne gravimetry data sparse reconstruction via L1-norm convex quadratic programming - Ya-Peng Yang; Mei-Ping Wu; Gang Tang (Applied Geophysics, 2015)

The alleviation of acid soil stress in rice by inorganic or organic ameliorants is associated with changes in soil enzyme activity and microbial community composition - Chao Ai; Guoqing Liang; Jingwen Sun; Ping He; Shuanhu Tang; Shaohai Yang; Wei Zhou; Xiubin Wang (Biology and Fertility of Soils, 2015)

The ctnG gene encodes carbonic anhydrase involved in mycotoxin citrinin biosynthesis from Monascus aurantiacus - Yan-Ping Li; Xiao Tang; Wei Wu; Yang Xu; Zhi-Bing Huang; Qing-Hua He (Food Additives & Contaminants: Part A, 2015)

System‐wide characterization of bZIP transcription factor proteins involved in infection‐related morphogenesis of M agnaporthe oryzae - Wei Tang; Yanyan Ru; Li Hong; Qian Zhu; Rongfang Zuo; Xianxian Guo; Jingzhen Wang; Haifeng Zhang; Xiaobo Zheng; Ping Wang; Zhengguang Zhang (Environmental Microbiology, 2015)
Summary The basic leucine zipper ( bZIP ) domain‐containing transcription factors ( TFs ) function as key regulators of cellular growth and differentiation in eukaryotic organisms including fungi. We have previously identified MoAp 1 and MoAtf 1 as bZIP TFs in M agnaporthe oryzae and demonstrated that they regulate the oxidative stress response and are critical in conidiogenesis and pathogenicity. Studies of bZIP proteins could provide a novel strategy for controlling rice blast, but a systematic examination of the bZIP proteins has not been carried out. Here, we identified 19 additional bZIP TFs and characterized their functions. We found that the majority of these TFs exhibit active functions, most notably, in conidiogenesis. We showed that MoHac 1 regulates the endoplasmic reticulum stress response through a conserved unfolded protein response pathway, MoMetR controls amino acid metabolism to govern growth and differentiation, and MoBzip 10 governs appressorium function and invasive hyphal growth. Moreover, MoBzip 5 participates in appressorium formation through a pathway distinct from that MoBzip 10, and MoMeaB appears to exert a regulatory role through nutrient uptake and nitrogen utilization. Collectively, our results provide insights into shared and specific functions associated with each of these TFs and link the regulatory roles to the fungal growth, conidiation, appressorium formation, host penetration and pathogenicity.

Exploring the Wnt Pathway-Associated LncRNAs and Genes Involved in Pancreatic Carcinogenesis Driven by Tp53 Mutation - Qi Wang; He Jiang; Chen Ping; Ruizhe Shen; Tingting Liu; Juanjuan Li; Yuting Qian; Yanping Tang; Shidan Cheng; Weiyan Yao; Lifu Wang (Pharmaceutical Research, 2015)

Genetic polymorphisms of CYP2D6*10 and the effectiveness of combined tamoxifen citrate and testosterone undecanoate treatment in infertile men with idiopathic oligozoospermia - Kai-fa Tang; Yi-li Zhao; Shang-shu Ding; Qi-fei Wu; Xing-yang Wang; Jia-qi Shi; Fa Sun; Jun-ping Xing (Journal of Zhejiang University-SCIENCE B, 2015)

Clinical effect of postconditioning in ST-elevation myocardial infarction patients treated with primary percutaneous coronary intervention: a meta-analysis of randomized controlled trials - Xian-qing Hu; Jian Cheng; Biao Tang; Zhong-heng Zhang; Ke Huang; Yi-ping Yang; Yan-yan Mao; Ming Zhong; Shen-wen Fu (Journal of Zhejiang University-SCIENCE B, 2015)

Protective Effect of sRAGE on Fetal Development in Pregnant Rats with Gestational Diabetes Mellitus - Xuwen Tang; Qingxin Qin; Xiaobin Xie; Ping He (Cell Biochemistry and Biophysics, 2015)

Genetic diversity and evolution of two capsid protein genes of citrus tristeza virus isolates from China - Guan-Wei Wu; Min Tang; Guo-Ping Wang; Feng-Yin Jin; Zuo-Kun Yang; Li-Jing Cheng; Ni Hong (Archives of Virology, 2015)

Influence of PTGS1, PTGFR, and MRP4 genetic variants on intraocular pressure response to latanoprost in Chinese primary open-angle glaucoma patients - Li-chen Gao; Di Wang; Fang-qun Liu; Zheng-yu Huang; Hong-guang Huang; Gui-hua Wang; Xi Chen; Qun-zhi Shi; Li Hong; Li-ping Wu; Jie Tang (European Journal of Clinical Pharmacology, 2015)

Principal denudation processes and their contribution to fluvial suspended sediment yields in the Upper Yangtze River Basin and Volga River Basin - Golosov Valentin; Xin-bao Zhang; Xiu-bin He; Qiang Tang; Ping Zhou (Journal of Mountain Science, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

Different secondary metabolic responses to MeJA treatment in shikonin-proficient and shikonin-deficient cell lines from Arnebia euchroma (Royle) Johnst - Sheng Wang; Lan Ping Guo; Teng Xie; Jian Yang; Jin Fu Tang; Xuan Li; Xiao Wang; Lu Qi Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Gene expression pattern of insect fat body cells from in vitro challenge to cell line establishment - Huan Zhang; Qian Meng; Ping Tang; Xuan Li; Wei Zhu; Guiling Zhou; Ruihao Shu; Jihong Zhang; Qilian Qin (In Vitro Cellular & Developmental Biology - Animal, 2014)

ABI-like transcription factor gene TaABL1 from wheat improves multiple abiotic stress tolerances in transgenic plants - Dong-Bei Xu; Shi-Qing Gao; You-Zhi Ma; Zhao-Shi Xu; Chang-Ping Zhao; Yi-Miao Tang; Xue-Yin Li; Lian-Cheng Li; Yao-Feng Chen; Ming Chen (Functional & Integrative Genomics, 2014)

Diagnosing southeast tropical Atlantic SST and ocean circulation biases in the CMIP5 ensemble - Zhao Xu; Ping Chang; Ingo Richter; Who Kim; Guanglin Tang (Climate Dynamics, 2014)

A prepared anti-MSTN polyclonal antibody reverses insulin resistance of diet-induced obese rats via regulation of PI3K/Akt/mTOR&FoxO1 signal pathways - Liang Tang; Chen-tao Liu; Xu-dan Wang; Kai Luo; Di-di Zhang; Ai-ping Chi; Jing Zhang; Li-jun Sun (Biotechnology Letters, 2014)

An automatic geometric precision correction system based on hierarchical registration for HJ-1 A/B CCD images - Xiaojun Shan; Ping Tang; Changmiao Hu (International Journal of Remote Sensing, 2014)

Transcription of the Human Sodium Channel SCN1A Gene Is Repressed by a Scaffolding Protein RACK1 - Zhao-Fei Dong; Ling-Jia Tang; Guang-Fei Deng; Tao Zeng; Shu-Jing Liu; Rui-Ping Wan; Ting Liu; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2014)

Efficient Generation of Neural Stem Cell-Like Cells from Rat Adipose Derived Stem Cells After Lentiviral Transduction with Green Fluorescent Protein - Yu Zhang; Na Liu; Yingxin Tang; Erfang Yang; Shasha Dong; Mengyang Huang; Chao Pan; Youping Zhang; Ping Zhang; Hong Chen; Zhouping Tang (Molecular Neurobiology, 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

Species-Specific Bioaccumulation of Halogenated Organic Pollutants and Their Metabolites in Fish Serum from an E-Waste Site, South China - Yan-Hong Zeng; Xiao-Jun Luo; Xiao-Bo Zheng; Bin Tang; Jiang-Ping Wu; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2014)

Dysregulation of vitamin D metabolism in the brain and myocardium of rats following prolonged exposure to dexamethasone - Pei Jiang; Ying Xue; Huan-De Li; Yi-Ping Liu; Hua-Lin Cai; Mi-Mi Tang; Li-Hong Zhang (Psychopharmacology, 2014)

RETRACTED ARTICLE: Relationships between PON1 Q192R polymorphism and clinical outcome of antiplatelet treatment after percutaneous coronary intervention: a meta-analysis - Ping Li; Shu-Hong Bu; Xiao-Tong Lu; Li-Xia Li; A-Jing Xu; Yue-Nian Tang; Jian Zhang (Molecular Biology Reports, 2014)

Isolation and expression of CsFAD7 and CsFAD8, two genes encoding ω-3 fatty acid desaturase from Camellia sinensis - Qing-Ping Ma; En You; Jing Wang; Yu Wang; Zhao-Tang Ding (Acta Physiologiae Plantarum, 2014)

Differential expression patterns and a novel interaction factor of Damaged DNA Binding Protein 1A (DDB1A) and DDB1B in Arabidopsis thaliana - Pei Hou; Peng-fei Ren; De-er Zeng; Gui-rong Yu; Wei Tang; Xu Zheng; Jian-ping Yang; Yongsheng Liu (Journal of Plant Biology, 2014)

A comparative study of the atmospheric circulations associated with rainy-season floods between the Yangtze and Huaihe River Basins - Fan Ping; XiBa Tang; ShouTing Gao; ZheXian Luo (Science China Earth Sciences, 2014)

Gene–environment interactions between JAZF1 and occupational and household lead exposure in prostate cancer among African American men - Christine Neslund-Dudas; Albert M. Levin; Jennifer L. Beebe-Dimmer; Cathryn H. Bock; Nora L. Nock; Andrew Rundle; Michelle Jankowski; Richard Krajenta; Q. Ping Dou; Bharati Mitra; Deliang Tang; Timothy R. Rebbeck; et al. (Cancer Causes & Control, 2014)

Resilient and plastic strain behavior of freezing–thawing mucky clay under subway loading in Shanghai - Yiqun Tang; Jun Li; Peng Wan; Ping Yang (Natural Hazards, 2014)

A novel variant in the 3′ UTR of human SCN1A gene from a patient with Dravet syndrome decreases mRNA stability mediated by GAPDH’s binding - Tao Zeng; Zhao-Fei Dong; Shu-Jing Liu; Rui-Ping Wan; Ling-Jia Tang; Ting Liu; Qi-Hua Zhao; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Human Genetics, 2014)

Structure-based design, synthesis, and anticonvulsant activity of isatin-1-N-phenylacetamide derivatives - Chao Xie; Li-Ming Tang; Fu-Nan Li; Li-Ping Guan; Cheng-Yan Pan; Si-Hong Wang (Medicinal Chemistry Research, 2014)

Adipose-derived stem cells transfected with pEGFP-OSX enhance bone formation during distraction osteogenesis - Qing-guo Lai; Shao-long Sun; Xiao-hong Zhou; Chen-ping Zhang; Kui-feng Yuan; Zhong-jun Yang; Sheng-lei Luo; Xiao-peng Tang; Jiang-bo Ci (Journal of Zhejiang University-SCIENCE B, 2014)

Erratum to: Bacillus bingmayongensis sp. nov., isolated from the pit soil of Emperor Qin’s Terra-cotta warriors in China - Bo Liu; Guo-Hong Liu; Gui-Ping Hu; Cetin Sengonca; Nai-Quan Lin; Jian-Yang Tang; Wei-Qi Tang; Ying-Zhi Lin (Antonie van Leeuwenhoek, 2014)

Geochronology and geochemistry of the Late Triassic Longtan pluton in South China: termination of the crustal melting and Indosinian orogenesis - Liang Qiu; Dan-Ping Yan; Mei-Fu Zhou; Nicholas T. Arndt; Shuang-Li Tang; Liang Qi (International Journal of Earth Sciences, 2014)

Myocardial mitochondrial oxidative stress and dysfunction in intense exercise: regulatory effects of quercetin - Chao Gao; Xiaoqian Chen; Juan Li; Yanyan Li; Yuhan Tang; Liang Liu; Shaodan Chen; Haiyan Yu; Liegang Liu; Ping Yao (European Journal of Applied Physiology, 2014)

A method developed for determination of heptachlor and its metabolites from pork - Hai Gen Zuo; Jian Xin Zhu; Chun Rui Zhan; Guo Yan Tang; Ping Guo; Yuan Long Wei; Hai Long Zeng; Hong Yang (Environmental Monitoring and Assessment, 2014)

Effect of Zinc-Bearing Zeolite Clinoptilolite on Growth Performance, Nutrient Retention, Digestive Enzyme Activities, and Intestinal Function of Broiler Chickens - Zhigang Tang; Chao Wen; Ping Li; Tian Wang; Yanmin Zhou (Biological Trace Element Research, 2014)

A 2-D wavelet decomposition-based bag-of-visual-words model for land-use scene classification - Lijun Zhao; Ping Tang; Lianzhi Huo (International Journal of Remote Sensing, 2014)

Bacillus bingmayongensis sp. nov., isolated from the pit soil of Emperor Qin’s Terra-cotta warriors in China - Bo Liu; Guo-Hong Liu; Gui-Ping Hu; Sengonca Cetin; Nai-Quan Lin; Jian-Yang Tang; Wei-Qi Tang; Ying-Zhi Lin (Antonie van Leeuwenhoek, 2014)

Morphological and molecular evidence for a new species of Rhodotus from tropical and subtropical Yunnan, China - Li-Ping Tang; Yan-Jia Hao; Qing Cai; Bau Tolgor; Zhu L. Yang (Mycological Progress, 2014)

Electroencephalographic signals synchronize with behaviors and are sexually dimorphic during the light–dark cycle in reproductive frogs - Ping Yang; Guangzhan Fang; Fei Xue; Jianguo Cui; Steven E. Brauth; Yezhong Tang (Journal of Comparative Physiology A, 2014)

The TNF-alpha -308G/A polymorphism is associated with type 2 diabetes mellitus: an updated meta-analysis - Yuliang Zhao; Zheng Li; Ling Zhang; Yonggang Zhang; Yingying Yang; Yi Tang; Ping Fu (Molecular Biology Reports, 2014)

A simulation of the merger of convective clouds in the torrential rainfalls associated with the Meiyu front - Fan Ping; Zhexian Luo; Xiba Tang; Liang Hu (Meteorology and Atmospheric Physics, 2014)

Erratum to: Parvularcula oceanus sp. nov., isolated from deep-sea water of the Southeastern Pacific Ocean - Shuhui Li; Kai Tang; Keshao Liu; Chang-Ping Yu; Nianzhi Jiao (Antonie van Leeuwenhoek, 2014)

Parvularcula oceanus sp. nov., isolated from deep-sea water of the Southeastern Pacific Ocean - Shuhui Li; Kai Tang; Keshao Liu; Chang-Ping Yu; Nianzhi Jiao (Antonie van Leeuwenhoek, 2014)

Improving classification of woodland types using modified prior probabilities and Gaussian mixed model in mountainous landscapes - Chenxin Chen; Ping Tang; Honggan Wu (International Journal of Remote Sensing, 2013)

VEGF +936C/T and +460C/T gene polymorphisms and oral cancer risk: a meta-analysis - Su-Feng Zhao; Ping Zhan; Xu-Dong Yang; Ming-Xing Lu; Guo-Wen Sun; Yu-Xin Wang; Yin-Kai Zhang; Yu-Mei Pu; En-Yi Tang (Molecular Biology Reports, 2013)

Overweight and Obesity Associated With Increased Total Serum Calcium Level: Comparison of Cross-sectional Data in the Health Screening for Teaching Faculty - Xiao-hua Ren; Ying-shui Yao; Lian-ping He; Yue-long Jin; Wei-wei Chang; Jie Li; Yan Chen; Xiu-li Song; Hui Tang; Ling-ling Ding; Dao-xia Guo; Chao-ping Li (Biological Trace Element Research, 2013)

Improvement of enamel bond strengths for conventional and resin-modified glass ionomers: acid-etching vs. conditioning - Ling Zhang; Tian Tang; Zhen-liang Zhang; Bing Liang; Xiao-miao Wang; Bai-ping Fu (Journal of Zhejiang University-SCIENCE B, 2013)

Chitosan-functionalized silk fibroin 3D scaffold for keratocyte culture - Linan Guan; Pei Tian; Hongyan Ge; Xianling Tang; Hong Zhang; Lingling Du; Ping Liu (Journal of Molecular Histology, 2013)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Erratum to: Novel mutation c.980_983delATTA compound with c.986C>A mutation of the FRMD7 gene in a Chinese family with X-linked idiopathic congenital nystagmus - Feng-wei Song; Bin-bin Chen; Zhao-hui Sun; Li-ping Wu; Su-juan Zhao; Qi Miao; Xia-jing Tang (Journal of Zhejiang University-SCIENCE B, 2013)

Population persistence of a Tertiary relict tree Tetracentron sinense on the Ailao Mountains, Yunnan, China - Cindy Q. Tang; Ming-Chun Peng; Long-Yuan He; Masahiko Ohsawa; Chong-Yun Wang; Tian-Hua Xie; Wen-Shun Li; Jia-Ping Li; Hong-Yu Zhang; Yong Li; Xian-Ming Yang; Guo-Song Li (Journal of Plant Research, 2013)

Spatiotemporal modeling of monthly soil temperature using artificial neural networks - Wei Wu; Xiao-Ping Tang; Nai-Jia Guo; Chao Yang; Hong-Bin Liu; Yue-Feng Shang (Theoretical and Applied Climatology, 2013)

RNA interference mediated pten knock-down inhibit the formation of polycystic ovary - Jie-Xiu Ouyang; Tao Luo; Hui-Yun Sun; Jian Huang; Dan-Feng Tang; Lei Wu; Yue-Hui Zheng; Li-Ping Zheng (Molecular and Cellular Biochemistry, 2013)

Factors associated with decision time for patients with ST-segment elevation acute myocardial infarction - Lu Qian; Kang-ting Ji; Jin-liang Nan; Qin Lu; Yong-jin Zhu; Lu-ping Wang; Lian-ming Liao; Ji-fei Tang (Journal of Zhejiang University-SCIENCE B, 2013)

Effects of hydroxyapatite addition on heavy metal volatility during tannery sludge incineration - Ping Tang; Yongchao Zhou; Zhengmiao Xie (Environmental Science and Pollution Research, 2013)

Display of Human Proinsulin on the Bacillus subtilis Spore Surface for Oral Administration - Fan Feng; Ping Hu; Liang Chen; Qi Tang; Chaoqun Lian; Qin Yao; Keping Chen (Current Microbiology, 2013)

Novel mutation c.980_983delATTA compound with c.986C>A mutation of the FRMD7 gene in a Chinese family with X-linked idiopathic congenital nystagmus - Feng-wei Song; Bin-bin Chen; Zhao-hui Sun; Li-ping Wu; Su-juan Zhao; Qi Miao; Xia-jing Tang (Journal of Zhejiang University-SCIENCE B, 2013)

Ecto-5′-nucleotidase (CD73) promotes tumor angiogenesis - Li Wang; Shaoxian Tang; Yingjian Wang; Siguang Xu; Jerry Yu; Xiuling Zhi; Zhouluo Ou; Jiayin Yang; Ping Zhou; Zhimin Shao (Clinical & Experimental Metastasis, 2013)

Paracoccus siganidrum sp. nov., isolated from fish gastrointestinal tract - Ying Liu; Qing-yi Xie; Kui Hong; Lei Li; Ya-mei Zhao; Yi-li Tang; Jun-ying An; Ping-ping Zhu; Chun-hou Xu (Antonie van Leeuwenhoek, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Distribution and accumulation characteristics of heavy metals in sediments in southern sea area of Huludao City, China - Yan Wang; Ruhai Liu; Dejiang Fan; Ping Yu; Jinyu Wang; Aikun Tang (Chinese Geographical Science, 2013)

Bacterial and archaeal diversities in Y unnan and T ibetan hot springs, C hina - Zhao‐Qi Song; Feng‐Ping Wang; Xiao‐Yang Zhi; Jin‐Quan Chen; En‐Min Zhou; Feng Liang; Xiang Xiao; Shu‐Kun Tang; Hong‐Chen Jiang; Chuanlun L. Zhang; Hailiang Dong; Wen‐Jun Li (Environmental Microbiology, 2013)
Summary Thousands of hot springs are located in the north‐eastern part of the Y unnan– T ibet geothermal zone, which is one of the most active geothermal areas in the world. However, a comprehensive and detailed understanding of microbial diversity in these hot springs is still lacking. In this study, bacterial and archaeal diversities were investigated in 16 hot springs ( pH 3.2–8.6; temperature 47–96° C ) in Y unnan P rovince and T ibet, C hina by using a barcoded 16 S rRNA gene‐pyrosequencing approach. A quificae , P roteobacteria , F irmicutes , D einococcus‐ T hermus and B acteroidetes comprised the large portion of the bacterial communities in acidic hot springs. Non‐acidic hot springs harboured more and variable bacterial phyla than acidic springs. D esulfurococcales and unclassified C renarchaeota were the dominated groups in archaeal populations from most of the non‐acidic hot springs; whereas, the archaeal community structure in acidic hot springs was simpler and characterized by S ulfolobales and T hermoplasmata . The phylogenetic analyses showed that A quificae and C renarchaeota were predominant in the investigated springs and possessed many phylogenetic lineages that have never been detected in other hot springs in the world. Thus findings from this study significantly improve our understanding of microbial diversity in terrestrial hot springs.

Effects of glacier melting on socioeconomic development in the Manas River basin, China - Xiang-ling Tang; Li-Ping Xu; Zheng-Yong Zhang; Xin Lv (Natural Hazards, 2013)

Quantitative evaluation of Candia antarctica lipase B displayed on the cell surface of a Pichia pastoris based on an FS anchor system - Xing-xiang Liang; Bei-bei Wang; Yu-fei Sun; Ying Lin; Shuang-yan Han; Sui-ping Zheng; Tang-bing Cui (Biotechnology Letters, 2013)

Expression and characterization of a novel isocitrate dehydrogenase from Streptomyces diastaticus No. 7 strain M1033 - Bei-Bei Zhang; Peng Wang; Ao Wang; Wen-Cai Wang; Wang-Gang Tang; Guo-Ping Zhu (Molecular Biology Reports, 2013)

Chemotherapy plus multitargeted antiangiogenic tyrosine kinase inhibitors or chemotherapy alone in advanced NSCLC: a meta-analysis of randomized controlled trials - Yong-Ying Xiao; Ping Zhan; Dong-Mei Yuan; Hong-Bing Liu; Tang-Feng Lv; Yong Song; Yi Shi (European Journal of Clinical Pharmacology, 2013)

Maternal effects of photoperiods on glycogen metabolism related to induction of diapause in Cotesia vestalis (Hymenoptera: Braconidae) from Jilin, China - Zhong-Ping Hao; Bin Tang; Chao Chen; Yi-Peng He; Zu-Hua Shi (Applied Entomology and Zoology, 2013)

Fractal characteristics and stability of soil aggregates in karst rocky desertification areas - Yiqun Tang; Jun Li; Xiaohui Zhang; Ping Yang; Jianxiu Wang; Nianqing Zhou (Natural Hazards, 2013)

Formaldehyde Impairs Learning and Memory Involving the Disturbance of Hydrogen Sulfide Generation in the Hippocampus of Rats - Xiao-Qing Tang; Yuan-Yuan Zhuang; Ping Zhang; Heng-Rong Fang; Cheng-Fang Zhou; Hong-Feng Gu; Hui Zhang; Chun-Yan Wang (Journal of Molecular Neuroscience, 2013)

The genotypes of citrus tristeza virus isolates from China revealed by sequence analysis of multiple molecular markers - Guan-wei Wu; Song Pan; Guo-ping Wang; Min Tang; Yong Liu; Fan Yang; Ni Hong (Archives of Virology, 2013)

Biomass accumulation and partitioning, photosynthesis, and photosynthetic induction in field-grown maize (Zea mays L.) under low- and high-nitrogen conditions - Jun-Wen Chen; Zhi-Qing Yang; Ping Zhou; Mei-Rong Hai; Tian-Xiang Tang; Yan-Li Liang; Tong-Xin An (Acta Physiologiae Plantarum, 2013)

Dominantly Inherited Myotonia Congenita Resulting from a Mutation That Increases Open Probability of the Muscle Chloride Channel CLC-1 - David P. Richman; Yawei Yu; Ting-Ting Lee; Pang-Yen Tseng; Wei-Ping Yu; Ricardo A. Maselli; Chih-Yung Tang; Tsung-Yu Chen (NeuroMolecular Medicine, 2012)

Complex Evolutionary Relationships Among Four Classes of Modular RNA-Binding Splicing Regulators in Eukaryotes: The hnRNP, SR, ELAV-Like and CELF Proteins - Yue Hang Tang; Siew Ping Han; Karin S. Kassahn; Adam Skarshewski; Joseph A. Rothnagel; Ross Smith (Journal of Molecular Evolution, 2012)

Fosinopril Attenuates the Doxorubicin-induced Cardiomyopathy by Restoring the Function of Sarcoplasmic Reticulum - Ya-chen Zhang; Yong Tang; Min Zhang; Jian Chen; Qing Zhou; Ying-gang Sun; Man-tian Chen; Wei-ping Xu (Cell Biochemistry and Biophysics, 2012)

Molecular cloning and functional expression of two key carotene synthetic genes derived from Blakeslea trispora into E. coli for increased β-carotene production - Jie Sun; Xin-Xiao Sun; Ping-Wah Tang; Qi-Peng Yuan (Biotechnology Letters, 2012)

Phylogenetic resolution and systematics of the Asian tree frogs, Rhacophorus (Rhacophoridae, Amphibia) - Jia‐Tang Li; Yang Li; Robert W. Murphy; Ding‐Qi Rao; Ya‐Ping Zhang (Zoologica Scripta, 2012)
Li, J.T., Li, Y., Murphy, R.W., Rao, D.‐Q. & Zhang, Y.‐P. (2012). Phylogenetic resolution and systematics of the Asian tree frogs, Rhacophorus (Rhacophoridae, Amphibia). — Zoologica Scripta , 41 , 557–570. The treefrog genus Rhacophorus , a large genus with 80 species, has a wide range, occurring eastward from India to China, Japan, South‐east Asia, the Greater Sunda Islands and the Philippines. The phylogenetic relationships and taxonomic recognition of many species are very controversial. To stabilize the taxonomy, the phylogenetic relationships among about 52 species are investigated from 96 samples using mtDNA sequence data. Matrilineal relationships based on maximum likelihood and Bayesian inference methods resolve three well‐supported lineages (A, B and C), although the phylogenetic relationships among three lineages remain ambiguous. Analyses support recognition of two previously assigned subgenera, Leptomantis and Rhacophorus , and these correspond to lineages A and B, respectively. Given that we have three strongly supported lineages, that these lineages are morphologically distinct, and the constrained geographic distributions of these groups, we recognize each lineage as a taxon. Subgenus Leptomantis includes species mainly from Malaysia, Indonesia and the Philippines. Subgenus Rhacophorus contains a mix of species occurring in India, Indochina and southern China. Lineage C accommodates species distributed mostly in East Asia, including Japan and China. Based on genetic and morphological data from type localities, the taxonomic recognition of some species needs to be reconsidered. Rhacophorus pingbianensis and Polypedates spinus are considered as junior synonyms of Rhacophorus duboisi . Specimens of Rhacophorus rhodopus from Vietnam and Hainan, China likely represent an undescribed, cryptic species.

Determination of methylmercury in marine fish from coastal areas of Zhejiang, China - Zhu Huang; Xiao-Dong Pan; Jian-Long Han; Ping-Gu Wu; Jun Tang; Ying Tan (Food Additives & Contaminants Part B-Surveillance, 2012)

Lipoxin A4 Inhibits 5-Lipoxygenase Translocation and Leukotrienes Biosynthesis to Exert a Neuroprotective Effect in Cerebral Ischemia/Reperfusion Injury - Le Wu; Sen Miao; Lin-Bing Zou; Ping Wu; Hua Hao; Ke Tang; Pan Zeng; Jing Xiong; Hong-Hua Li; Qiang Wu; Lei Cai; Du-Yun Ye (Journal of Molecular Neuroscience, 2012)

Controlling subsidence caused by de-watering in a deep foundation pit - Jianxiu Wang; Bo Feng; Yan Liu; Lingao Wu; Yanfei Zhu; Xingsheng Zhang; Yiqun Tang; Ping Yang (Bulletin of Engineering Geology and the Environment, 2012)

Enhancement of butanol production and reducing power using a two-stage controlled-pH strategy in batch culture of Clostridium acetobutylicum XY16 - Ting Guo; Baijun Sun; Min Jiang; Hao Wu; Tengfei Du; Yan Tang; Ping Wei; Pingkai Ouyang (World Journal of Microbiology and Biotechnology, 2012)

Inference of creep mechanism in underground soil loss of karst conduits I. Conceptual model - Jie Zhou; Yiqun Tang; Ping Yang; Xiaohui Zhang; Nianqing Zhou; Jianxiu Wang (Natural Hazards, 2012)

S-nitrosylation of c-Src via NMDAR-nNOS module promotes c-Src activation and NR2A phosphorylation in cerebral ischemia/reperfusion - Li-Juan Tang; Chong Li; Shu-Qun Hu; Yong-Ping Wu; Yan-Yan Zong; Chang-Cheng Sun; Fa Zhang; Guang-Yi Zhang (Molecular and Cellular Biochemistry, 2012)

Bioleaching of heavy metals from sewage sludge by Acidithiobacillus thiooxidans—a comparative study - Ye-Ming Wen; Qing-Ping Wang; Caixian Tang; Zu-Liang Chen (Journal of Soils and Sediments, 2012)

The influence of water content on soil erosion in the desertification area of Guizhou, China - Jie Zhou; Yi-qun Tang; Xiao-hui Zhang; Tian-yu She; Ping Yang; Jian-xiu Wang (Carbonates and Evaporites, 2012)

Quantitative analysis of the microstructure of Shanghai muddy clay before and after freezing - Yi-qun Tang; Jie Zhou; Jun Hong; Ping Yang; Jian-xiu Wang (Bulletin of Engineering Geology and the Environment, 2012)

Enhanced thermal-tolerance of photosystem II by elevating root zone temperature in Prunus mira Koehne seedlings - Hai-Ping Hao; Chuang-Dao Jiang; Shou-Ren Zhang; Yu-Dan Tang; Lei Shi (Plant and Soil, 2012)

The interaction of blood proteins with brucine - Hong-Mei Zhang; Zheng-Hao Fei; Bo-Ping Tang; Jian Chen; Wei-Hua Tao; Yan-Qing Wang (Molecular Biology Reports, 2012)

H. pylori related proinflammatory cytokines contribute to the induction of miR-146a in human gastric epithelial cells - Na Li; Xiang Xu; Bin Xiao; En-Dong Zhu; Bo-sheng Li; Zhen Liu; Bin Tang; Quan-Ming Zou; Hua-Ping Liang; Xu-Hu Mao (Molecular Biology Reports, 2012)

Occurrence of an Alaskan-type complex in the Middle Tianshan Massif, Central Asian Orogenic Belt: inferences from petrological and mineralogical studies - Ben-Xun Su; Ke-Zhang Qin; Patrick Asamoah Sakyi; Sanjeewa P.K. Malaviarachchi; Ping-Ping Liu; Dong-Mei Tang; Qing-Hua Xiao; He Sun; Yu-Guang Ma; Qian Mao (International Geology Review, 2012)

Assessment of economic losses from tropical cyclone disasters based on PCA-BP - Wei-ping Lou; Hai-yan Chen; Xin-fa Qiu; Qi-yi Tang; Feng Zheng (Natural Hazards, 2012)

The role of PRKCH gene variants in coronary artery disease in a Chinese population - Jun Zhu; Jian-Jun Yan; Zheng-Ping Kuai; Wei Gao; Jian-Jin Tang; En-Zhi Jia; Zhi-Jian Yang; Lian-Sheng Wang (Molecular Biology Reports, 2012)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

Involvement of KATP/PI3K/AKT/Bcl-2 Pathway in Hydrogen Sulfide-induced Neuroprotection Against the Toxicity of 1-methy-4-phenylpyridinium Ion - Xiao-Qing Tang; Yuan-Yuan Zhuang; Li-Li Fan; Heng-Rong Fang; Cheng-Fang Zhou; Ping Zhang; Bi Hu (Journal of Molecular Neuroscience, 2012)

Effects of applied urea and straw on various nitrogen fractions in two Chinese paddy soils with differing clay mineralogy - Shao-Jun Qiu; Pei-Qin Peng; Ling Li; Ping He; Qiang Liu; Jin-Shui Wu; Peter Christie; Xiao-Tang Ju (Biology and Fertility of Soils, 2012)

Gastrodin protects against cardiac hypertrophy and fibrosis - Chunming Shu; Changgui Chen; Da-Ping Zhang; Haipeng Guo; Heng Zhou; Jing Zong; Zhouyan Bian; Xuan Dong; Jia Dai; Yan Zhang; Qizhu Tang (Molecular and Cellular Biochemistry, 2012)

Clinical characteristics of critical patients with pandemic influenza A (H1N1) virus infection in Chengdu, China - Li-hui Deng; Yi-lan Zeng; Ping Feng; Ya-ling Liu; Li-chun Wang; Yun Bai; Hong Tang (Journal of Zhejiang University-SCIENCE B, 2012)

Mutations in the NRG1 gene are associated with Hirschsprung disease - Clara Sze-Man Tang; Elly Sau-Wai Ngan; Wai-Kiu Tang; Man-Ting So; Guo Cheng; Xiao-Ping Miao; Thomas Yuk-Yu Leon; Brian Man-Chun Leung; Kenneth-Jeremy W. S. Hui; Vincent Hang-Chai Lui; Yan Chen; Ivy Hau-Yee Chan; et al. (Human Genetics, 2012)

Wood identification with PCR targeting noncoding chloroplast DNA - Xiaoshu Tang; Guangjie Zhao; Liyan Ping (Plant Molecular Biology, 2011)

Clostridium beijerinckii mutant obtained by atmospheric pressure glow discharge producing high proportions of butanol and solvent yields - Ting Guo; Yan Tang; Yong-lan Xi; Ai-yong He; Bai-jun Sun; Hao Wu; Da-feng Liang; Min Jiang; Ping-kai Ouyang (Biotechnology Letters, 2011)

3D-QSAR and docking studies on pyridopyrazinones as BRAF inhibitors - Yong Ai; Shao-Teng Wang; Chu Tang; Ping-Hua Sun; Fa-Jun Song (Medicinal Chemistry Research, 2011)

Suppression of CFTR premature termination codons and rescue of CFTR protein and function by the synthetic aminoglycoside NB54 - Steven M. Rowe; Peter Sloane; Li Ping Tang; Kyle Backer; Marina Mazur; Jessica Buckley-Lanier; Igor Nudelman; Valery Belakhov; Zsuzsa Bebok; Erik Schwiebert; Timor Baasov; David M. Bedwell (Journal of Molecular Medicine, 2011)

Seismic wavefront evolution of multiply reflected, transmitted, and converted phases in 2D/3D triangular cell model - Chao-ying Bai; Xiao-ling Li; Xiao-ping Tang (Journal of Seismology, 2011)

Occurrence and transmission of class 1 and 2 integrons among phenotypic highly ampicillin-resistant avian Escherichia coli isolates from Pakistan - Muhammad Yaqoob; Li Ping Wang; Tang Fang; Cheng-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

Polyethylenimine-cyclodextrin-tegafur conjugate shows anti-cancer activity and a potential for gene delivery - Qi-da Hu; Hui Fan; Wei-jian Lou; Qing-qing Wang; Gu-ping Tang (Journal of Zhejiang University-SCIENCE B, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Different patterns of ecosystem carbon accumulation between a young and an old-growth subtropical forest in Southern China - Xuli Tang; Ying-Ping Wang; Guoyi Zhou; Deqiang Zhang; Shen Liu; Shizhong Liu; Qianmei Zhang; Juxiu Liu; Junhua Yan (Plant Ecology, 2011)

Morphological and molecular evidences for a new species of Lignosus (Polyporales, Basidiomycota) from tropical China - Bao-Kai Cui; Li-Ping Tang; Yu-Cheng Dai (Mycological Progress, 2011)

Ds-echinoside A, a new triterpene glycoside derived from sea cucumber, exhibits antimetastatic activity via the inhibition of NF-κB-dependent MMP-9 and VEGF expressions - Qin Zhao; Zhi-dong Liu; Yong Xue; Jing-feng Wang; Hui Li; Qing-juan Tang; Yu-ming Wang; Ping Dong; Chang-hu Xue (Journal of Zhejiang University-SCIENCE B, 2011)

Using Seven Types of GM (1, 1) Model to Forecast Hourly Particulate Matter Concentration in Banciao City of Taiwan - Tzu-Yi Pai; Ching-Lin Ho; Shyh-Wei Chen; Huang-Mu Lo; Pao-Jui Sung; Shu-Wen Lin; Wei-Jia Lai; Shih-Chi Tseng; Shu-Ping Ciou; Jui-Ling Kuo; Jing-Tang Kao (Water, Air, & Soil Pollution, 2011)

The soybean GmbZIP1 transcription factor enhances multiple abiotic stress tolerances in transgenic plants - Shi-Qing Gao; Ming Chen; Zhao-Shi Xu; Chang-Ping Zhao; Liancheng Li; Hui-jun Xu; Yi-miao Tang; Xin Zhao; You-Zhi Ma (Plant Molecular Biology, 2011)

Identification of Differentially Expressed Sequence Tags in Rapidly Elongating Phyllostachys pubescens Internodes by Suppressive Subtractive Hybridization - Ming-bing Zhou; Ping Yang; Pei-jun Gao; Ding-Qin Tang (Plant Molecular Biology Reporter, 2011)

A large indel mutation of the bovine ADD1/SREBP1c gene and its effects on growth traits in some native cattle breeds from China - Yong-Zhen Huang; En-Ping Zhang; Jing Wang; Yong-Tao Huai; Liang Ma; Fu-Ying Chen; Xian-Yong Lan; Chu-Zhao Lei; Xing-Tang Fang; Ju-Qiang Wang; Hong Chen (Molecular Biology Reports, 2011)

Isolation and Identification of a Pathogen of Silkworm Bombyx mori - Heng-Ping Tao; Zhong-Yuan Shen; Feng Zhu; Xiao-Fang Xu; Xu-Dong Tang; Li Xu (Current Microbiology, 2011)

Bacillus zhanjiangensis sp. nov., isolated from an oyster in South China Sea - Yi-Guang Chen; Song-Ping Hu; Shu-Kun Tang; Jian-Wu He; Jian-Qing Xiao; Hong-Yi Zhu; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

MnHSP90 cDNA characterization and its expression during the ovary development in oriental river prawn, Macrobrachium nipponense - Weihong Zhao; Liqiao Chen; Jianguang Qin; Ping Wu; Fengying Zhang; Erchao Li; Boping Tang (Molecular Biology Reports, 2011)

A polymorphism in the visfatin gene promoter is related to decreased plasma levels of inflammatory markers in patients with coronary artery disease - Lian-Sheng Wang; Jian-Jun Yan; Na-Ping Tang; Jun Zhu; Yue-Song Wang; Qi-Ming Wang; Jian-Jin Tang; Ming-Wei Wang; En-Zhi Jia; Zhi-Jian Yang; Jun Huang (Molecular Biology Reports, 2011)

Enhanced V-ATPase activity contributes to the improved salt tolerance of transgenic tobacco plants overexpressing vacuolar Na+/H+ antiporter AtNHX1 - Shufeng Zhou; Zhiming Zhang; Qilin Tang; Hai Lan; Yinxin Li; Ping Luo (Biotechnology Letters, 2011)

Improved myocardial perfusion and cardiac function by controlled-release basic fibroblast growth factor using fibrin glue in a canine infarct model - Shao-ping Nie; Wang Xiao; Qiao Shi-bin; Zeng Qiu-tang; Jiang Ju-quan; Liu Xiao-qing; Zhu Xiang-ming; Cao Guo-xiang; Ma Chang-sheng (Journal of Zhejiang University-SCIENCE B, 2010)

Amino acid sequence analysis and identification of mutations under positive selection in hemagglutinin of 2009 influenza A (H1N1) isolates - Xiaofan Ding; Lifang Jiang; Changwen Ke; Zhan Yang; Chunliang Lei; Kaiyuan Cao; Jun Xu; Lin Xu; Xingfen Yang; Yonghui Zhang; Ping Huang; Weijun Huang; et al. (Virus Genes, 2010)

The interaction of lysozyme with caffeine, theophylline and theobromine in solution - Hong-Mei Zhang; Bo-Ping Tang; Yan-Qing Wang (Molecular Biology Reports, 2010)

Differential distributions of CSE1L/CAS and E-cadherin in the polarized and non-polarized epithelial glands of neoplastic colorectal epithelium - Wu-Ching Uen; Cheng-Jeng Tai; Shing-Chuan Shen; Woan-Ruoh Lee; Tang-Yi Tsao; Win-Ping Deng; Hung-Yi Chiou; Chung-Huei Hsu; Cheng-I Hsieh; Ching-Fong Liao; Ming-Chung Jiang (Journal of Molecular Histology, 2010)

Isolation and characterization of microsatellite markers from Lagerstroemia caudata (Lythraceae) and cross-amplification in other related species - Ming Cai; Rui Meng; Hui-Tang Pan; Yi-Ke Gao; Ming Sun; Ping Song; Xue-Feng Wang; Qi-Xiang Zhang (Conservation Genetics Resources, 2010)

Elevated high sensitive C-reactive protein and apelin levels after percutaneous coronary intervention and drug-eluting stent implantation - Xin Du; Jun-ping Kang; Jia-hui Wu; Qiang Lv; Chao-shu Tang; Chang-sheng Ma (Journal of Zhejiang University-SCIENCE B, 2010)

Two new naphthylisoquinoline alkaloids from stems and leaves of Ancistrocladus tectorius - Chun-Ping Tang; Zhen-Qiang Xin; Xi-Qiang Li; Yang Ye (Natural Product Research, 2010)

MaSERK1 Gene Expression Associated with Somatic Embryogenic Competence and Disease Resistance Response in Banana (Musa spp.) - Xia Huang; Xiao-Yan Lu; Jie-Tang Zhao; Jie-Kai Chen; Xue-Mei Dai; Wang Xiao; Ya-Ping Chen; Yun-Feng Chen; Xue-Lin Huang (Plant Molecular Biology Reporter, 2010)

Isolation and Characterization of Three MADS-box Genes from Alpinia hainanensis (Zingiberaceae) - Juan-Juan Song; Wei Ma; Yuan-Jiang Tang; Zhong-Yi Chen; Jing-Ping Liao (Plant Molecular Biology Reporter, 2010)

Association Analysis of the RET Proto-Oncogene with Hirschsprung Disease in the Han Chinese Population of Southeastern China - Cui-Ping Liu; Qian-Qian Tang; Jin-Tu Lou; Chun-Fen Luo; Xue-Wu Zhou; Dong-Mei Li; Fei Chen; Xiang Li; Ji-Cheng Li (Biochemical Genetics, 2010)

Unique evolutionary pattern of numbers of gramineous NBS–LRR genes - Jing Li; Jing Ding; Wen Zhang; Yuanli Zhang; Ping Tang; Jian-Qun Chen; Dacheng Tian; Sihai Yang (Molecular Genetics and Genomics, 2010)

Allopatric divergence and phylogeographic structure of the plateau zokor ( Eospalax baileyi ), a fossorial rodent endemic to the Qinghai–Tibetan Plateau - Li‐Zhou Tang; Liu‐Yang Wang; Zhen‐Yuan Cai; Tong‐Zuo Zhang; Hai‐Xin Ci; Gong‐Hua Lin; Jian‐Ping Su; Jian‐Quan Liu (Journal of Biogeography, 2010)
Aim Most species of temperate regions are believed to have shifted to lower latitudes or elevations during the glacial periods of the Quaternary. In this study we test whether this phylogeographic assumption is also true for the plateau zokor ( Eospalax baileyi ), a fossorial rodent endemic to the climate‐sensitive Qinghai–Tibetan Plateau (QTP), which ranges in elevation from 2600 to 4600 m. Location The QTP of western China. Methods Phylogeographic analyses were conducted based on the mitochondrial cytochrome b gene sequences of 193 individuals from 20 populations over the entire range of the species. Results A total of 54 haplotypes identified in the present study clustered into four geographically correlated clades located in the interior of the QTP (clade A) and at the plateau edge (B, C and D). Molecular calibrations suggest that the interior plateau (A) and plateau‐edge (B–D) clades diverged at 1.2 Ma and that the three plateau‐edge clades diverged between 0.85 and 0.80 Ma. These estimates are concordant with diastrophism and glaciation events in the QTP. Coalescent tests rejected both the hypothesis that all current populations originated from a single refugium at a low elevation during the Last Glacial Maximum (LGM) and the hypothesis that the two lineages diverged during the LGM. The tests instead supported the hypothesis that there were four refugia during the LGM, and that the four clades diverged prior to the late Pleistocene. Main conclusions Our results suggest that Quaternary diastrophisms and glaciations repeatedly promoted allopatric divergence of the plateau zokor into geographical clades, and that these regional clades subsequently persisted at high elevations, rather than migrating to the low‐elevation plateau edge during subsequent glacial ages.

Atrazine degradation by a simple consortium of Klebsiella sp. A1 and Comamonas sp. A2 in nitrogen enriched medium - Chunyu Yang; Yang Li; Kun Zhang; Xia Wang; Cuiqing Ma; Hongzhi Tang; Ping Xu (Biodegradation, 2010)

The effect of triptolide on CD4+ and CD8+ cells in the Peyer's patch of DA rats with collagen induced arthritis - Cheng Xiao; Linhua Zhao; Zhenli Liu; Cheng Lu; Ning Zhao; Dajian Yang; Shilin Chen; Johnny Cheuk-on Tang; Albert Chan; Ai-ping Lu (Natural Product Research, 2009)

Molecular Cloning and Characterization of an Ortholog of NPR1 Gene from Dongguan Dajiao (Musa spp. ABB) - Jie-Tang Zhao; Xia Huang; Ya-Ping Chen; Yun-Feng Chen; Xue-Lin Huang (Plant Molecular Biology Reporter, 2009)

A fast automatic recognition and location algorithm for fetal genital organs in ultrasound images - Sheng Tang; Si-ping Chen (Journal of Zhejiang University-SCIENCE B, 2009)

Necessity of Screening Water Chestnuts for Microcystins After Cyanobacterial Blooms Break Out - Fu-Gang Xiao; Xiao-Lian Zhao; Jian Tang; Xiao-Hong Gu; Jing-Ping Zhang; Wei-Min Niu (Archives of Environmental Contamination and Toxicology, 2009)

Transcriptional analysis of the hsp70 gene in a haloarchaeon Natrinema sp. J7 under heat and cold stress - Hao Zhang; Peng Cui; Lu Lin; Ping Shen; Bing Tang; Yu-Ping Huang (Extremophiles, 2009)

Dietary exposure of Hong Kong secondary school students to total mercury and methylmercury from fish intake - Anna Shiu Ping Tang; Ka Ping Kwong; Stephen Wai Cheung Chung; Yuk Yin Ho; Ying Xiao (Food Additives & Contaminants Part B-Surveillance, 2009)

Cloning and Characterization of Two Novel Crystal Protein Genes, cry54Aa1 and cry30Fa1, from Bacillus thuringiensis Strain BtMC28 - Furong Tan; Jun Zhu; Jie Tang; Xueming Tang; Shiquan Wang; Aiping Zheng; Ping Li (Current Microbiology, 2009)

Antitumor and antimetastatic activities of vesicular stomatitis virus matrix protein in a murine model of breast cancer - Wei Shi; Qingqing Tang; Xiancheng Chen; Ping Cheng; Peidu Jiang; Xiaomei Jing; Xiang Chen; Ping Chen; Yongsheng Wang; Yuquan Wei; Yanjun Wen (Journal of Molecular Medicine, 2009)

Comparative Analyses of Coding and Noncoding DNA Regions Indicate that Acropora (Anthozoa: Scleractina) Possesses a Similar Evolutionary Tempo of Nuclear vs. Mitochondrial Genomes as in Plants - I.-Ping Chen; Chung-Yu Tang; Chih-Yung Chiou; Jia-Ho Hsu; Nuwei Vivian Wei; Carden C. Wallace; Paul Muir; Henry Wu; Chaolun Allen Chen (Marine Biotechnology, 2009)

Determination of Microcystin-LR in Water from Lake Tai, China - Fu-Gang Xiao; Xiao-Lian Zhao; Jian Tang; Xiao-Hong Gu; Jing-Ping Zhang; Wei-Min Niu (Bulletin of Environmental Contamination and Toxicology, 2009)

Homology modelling and bivalent single-chain Fv construction of anti-HepG2 single-chain immunoglobulin Fv fragments from a phage display library - Ming Ni; Bing Yu; Yu Huang; Zhenjie Tang; Ping Lei; Xin Shen; Wei Xin; Huifen Zhu; Guanxin Shen (Journal of Biosciences, 2008)

Genetic diversity based on SSR markers in maize (Zea mays L.) landraces from Wuling mountain region in China - Yao Qi-Lun; Fang Ping; Kang Ke-Cheng; Pan Guang-Tang (Journal of Genetics, 2008)

Bisbenzopyrans and alkaloids from the roots of Stemona cochinchinensis - Pham-Huu Dien; Li-Gin Lin; Chun-Ping Tang; Chang-Qiang Ke; Yang Ye (Natural Product Research, 2008)

Anaerobic ammonium oxidation for treatment of ammonium-rich wastewaters - Lei Zhang; Ping Zheng; Chong-jian Tang; Jin Ren-cun (Journal of Zhejiang University-SCIENCE B, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Genetic Diversity and Systematic Evolution of Chinese Domestic Ducks Along the Yangtze-Huai River - Tang-jie Zhang; Hui-fang Li; Kuan-wei Chen; Hong Chang; Qing-ping Tang; Jing-xin Zhang (Biochemical Genetics, 2007)

A new cytotoxic cholesterol sulfate from marine sponge Halichondria rugosa - Hong-Jun Zhang; Jing-Bo Sun; Hou-Wen Lin; Zeng-Lei Wang; Hua Tang; Ping Cheng; Wan-Sheng Chen; Yang-Hua Yi (Natural Product Research, 2007)

Plant regeneration from protoplasts of Musa acuminata cv. Mas (AA) via somatic embryogenesis - Wang Xiao; Xue-Lin Huang; Xia Huang; Ya-Ping Chen; Xue-Mei Dai; Jie-Tang Zhao (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Intergeneration CAG expansion in a Wuhan juvenile-onset Huntington disease family - Yuan Liu; Yan Shen; He Li; Hui Wang; Zhen-Rong Yang; Yan Chen; Yan-Ping Tang (Neuroscience Bulletin, 2007)

Cloning of the black seabream (Acanthopagrus schlegeli) antiquitin gene and functional characterization of its promoter region - Chi-Bun Chan; Wai-Kwan Tang; Christopher H. K. Cheng; Wing-Ping Fong (Molecular and Cellular Biochemistry, 2007)

Introduction of the PPF1 gene into rice (Oryza sativa L.) results in delayed leaf senescence - Shuangcheng Li; Desuo Yin; Faqiang Wu; Shiquan Wang; Qiming Deng; Youhua Tang; Huaqiang Zhou; Ping Li (Euphytica, 2007)

An extracellular halophilic protease SptA from a halophilic archaeon Natrinema sp. J7: gene cloning, expression and characterization - Wanliang Shi; Xiao-Feng Tang; Yuping Huang; Fei Gan; Bing Tang; Ping Shen (Extremophiles, 2006)

Receptor-mediated gene delivery using polyethylenimine (PEI) coupled with polypeptides targeting FGF receptors on cells surface - Da Li; Qing-qing Wang; Gu-ping Tang; Hong-liang Huang; Fen-ping Shen; Jing-zhong Li; Hai Yu (Journal of Zhejiang University-SCIENCE B, 2006)

Effects of typical and atypical antipsychotics on glucose–insulin homeostasis and lipid metabolism in first-episode schizophrenia - Ren-Rong Wu; Jing-Ping Zhao; Zhe-Ning Liu; Jin-Guo Zhai; Xiao-Feng Guo; Wen-Bing Guo; Jing-Song Tang (Psychopharmacology, 2006)

Synthesis of Site-Specifically Dimethylated and Trimethylated Peptides Derived from Histone H3 N-Terminal Tail - Zhi-Ping Huang; Jin-Tang Du; Yu-Fen Zhao; Yan-Mei Li (International Journal of Peptide Research and Therapeutics, 2006)

Streptomyces daliensis sp. nov. from soil - Ping Xu; Wen-Jun Li; Shu-Kun Tang; Hui-Ying Gao; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2006)

Novel CACNA1S mutation causes autosomal dominant hypokalemic periodic paralysis in a Chinese family - Qiufen Wang; Mugen Liu; Chunsheng Xu; Zhaohui Tang; Yuhua Liao; Rong Du; Wei Li; Xiaoyan Wu; Xu Wang; Ping Liu; Xianqin Zhang; Jianfang Zhu; et al. (Journal of Molecular Medicine, 2005)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

Historical variation of heavy metals with respect to different chemical forms in recent sediments from Xianghai Wetlands, Northeast China - Guo-ping Wang; Jing-shuang Liu; Jie Tang (Wetlands, 2004)

A new locus for autosomal dominant Charcot-Marie-Tooth disease type2 (CMT2L) maps to chromosome 12q24 - Lu Shen; Jian-guang Tang; Guo-hua Zhao; Qian Pan; He-ping Dai; Oleg V. Evgrafov; Wei Luo; Kun Xia; Fang Cai; Qi-dong Yang; Jia-hui Xia; Bei-sha Tang; et al. (Human Genetics, 2004)

Construction, characterization and chromosomal mapping of bacterial artificial chromosome (BAC) library of Yunnan snub-nosed monkey (Rhinopithecus bieti - Huai-liang Xu; Ya-ping Qian; Wen-hui Nie; Jian-xiang Chi; Feng-tang Yang; Bing Su (Chromosome Research, 2004)

Development of mariculture and its impacts in Chinese coastal waters - Yang Yu Feng; Li Chun Hou; Nie Xiang Ping; Tang Dan Ling; Chung Ik Kyo (Reviews in Fish Biology and Fisheries, 2004)

Experimental study of trophic cascade effect of silver carp (Hypophthalmichthys molitrixon) in a subtropical lake, Lake Donghu: on plankton community and underlying mechanisms of changes of crustacean community - Min Lu; Ping Xie; Huijuan Tang; Zhaojun Shao; Liqiang Xie (Hydrobiologia, 2002)

Landscape distribution characteristics of northern foothill belts of Tianshan Mountains - Cheng Wei-ming; Zhou Cheng-hu; Tang Qi-cheng; Yao Yong-hui; Zhang Bai-ping (Journal of Geographical Sciences, 2002)

Effect of the neuroprotective agent riluzole on intracellular Ca 2+ levels in IMR32 neuroblastoma cells - Jue-Long Wang; Kam-Chung Lee; Kwong-Yui Tang; Ti Lu; Cheng-Ho Chang; Chik-Keung Chow; Wei-Chuan Chen; Warren Su; Yee-Ping Law; Chung-Ren Jan (Archives of Toxicology, 2001)

Transient inhibition of L929 cell mitosis and locomotion by argon ion laser irradiation - Karl W. Lanks; Jian-Ping Gao; Bai-Tang Lai (In Vitro Cellular & Developmental Biology - Animal, 1998)